Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Temporal and spatial transferability in telemetry-based dynamic species distribution models: The effects of algorithms and pseudo-absence techniques - Joshua C Wilson; Philip N Trathan; Hugh J Venables; Horst Bornemann; Rochelle Constantine; Daniel P Costa; Luciano Dalla Rosa; Louise Emmerson; Ari S Friedlaender; Michael E Goebel; Simon Goldsworthy; Mark A Hindell; et al. (Ecological Modelling, 2026)

Fish Assemblage Shift Following Abrupt Seagrass Loss in a Southwest Florida Tidal Creek - Kelly S. Chase; Philip W. Stevens; David A. Blewett; Courtney R. Saari; Colin P. Shea; Jeffrey E. Hill; Quenton M. Tuckett (Estuaries and Coasts, 2026)
Phase shifts can occur in ecosystems because of external stressors. Such transitions from one state (e.g., clear water, seagrass) to another (e.g., phytoplankton blooms, bare substrate) continue to be documented worldwide. In estuaries, stressors related to urban and suburban development are often implicated in phase shifts, including altered hydrology and eutrophication. Tidal creeks may be especially prone to phase shifts as their position in the landscape exposes them to the brunt of coastal development. In 2017, a precipitous seagrass decline occurred in a tidal creek downstream of coastal development in the Charlotte Harbor estuary, Florida (USA). Fisheries independent monitoring data (July 2014 to June 2022) from 21.3 m seines were used to investigate changes in fish assemblages. Multivariate analyses identified a fish assemblage shift that coincided with seagrass loss and increasing algal blooms. Reductions in seagrass-associated species (e.g., Rainwater Killifish Lucania parva ) were offset by increases in generalist and planktivorous taxa (e.g., Bay Anchovy Anchoa mitchilli ). Such changes did not occur in neighboring creeks downstream of more natural habitat. The present study is indicative of a potential phase shift. Tidal creeks serve as ‘sentinels’ for ecosystem change. Furthermore, similar patterns of seagrass loss and algal blooms are taking place in the open estuary; thus, the fish assemblage shift identified in the tidal creek may signal similar, widespread changes. Identifying shifts in biotic assemblages and predominant drivers can help guide resource planning to strengthen ecosystem resilience and recovery within Charlotte Harbor and other Florida estuaries.

Mangrove organic matter accumulated recently at Low Isles, Great Barrier Reef - Brooke M. Conroy; Jeffrey J. Kelleway; Haidee Cadd; Sarah M. Hamylton; Colin D. Woodroffe; David P. Child; Michael A.C. Hotchkis; Quan Hua; Sabika Maizma; Patricia Gadd; Debashish Mazumder; Kerrylee Rogers (Estuarine, Coastal and Shelf Science, 2026)

Exploring the effect of river spatial variability on SWOT discharge accuracy - Yushan Zhang; Michael Durand; Steve P. Coss; Renato Prata de Moraes Frasson; Elizabeth M. Prior; Colin J. Gleason (Advances in Water Resources, 2026)

Generalists circulate and specialists persist: the continuum of division of labor in harvester ant colonies - Colin M. Lynch; Xiaohui Guo; Theodore P. Pavlic; Ioulia Bespalova; Jon F. Harrison; Jennifer H. Fewell (Behavioral Ecology and Sociobiology, 2026)

Uncovering allergen presence and accumulation in glucose monitoring systems: evidence of a “sponge effect” via validated GC–MS - Asia Saorin; Sarah Watson; Colin P. Hawkes; John F. Bourke; Niamh M. O’Boyle (Analytica Chimica Acta, 2026)

A histological approach to mortuary variability in Early Bronze Age Transylvania - Nandini Subramaniam; Colin P. Quinn; Jess Beck; Horia Ciugudean; Claes Uhnér; Hannah Lau (Archaeological and Anthropological Sciences, 2026)
The shift from the Copper Age (c. 3600–2700 BCE) to the Early Bronze Age (c. 2700–2000 BCE) in Transylvania (Romania) was a period of significant changes in mortuary practices. We combine bone histology with bioarchaeological and archaeological assessments of mortuary variability to better understand the organization and diversity of funerary practices in the region. Bone histology, the study of microscopic structures of connective tissues in bone, can help disentangle complex mortuary programs. In this study we detail histological analyses of burials from two Early Bronze Age cemeteries: Meteș- La Meteșel , an upland cemetery associated with local Transylvanian communities, and Hăpria, a lowland cemetery associated with Yamnaya migrants. We identify the presence of multiple different pathways from death to burial in primary inhumations and secondary inhumations at these sites. The results here provide new insights into the complex process of cultural exchange during a time of social transformation and high human mobility.

Assessing the efficacy of coral restoration along Florida’s coral reef under the chronic persistence of stony coral tissue loss disease - William C. Sharp; Kristene T. Parsons; Erinn M. Muller; Amanda Bourque; David S. Gilliam; Diego Lirman; Colin P. Shea; Joshua D. Voss; John H. Hunt (Frontiers in Marine Science, 2026)
Stony coral tissue loss disease (SCTLD) has caused unprecedented coral mortality across Florida’s Coral Reef (FCR) since 2014, raising concerns about whether coral restoration can succeed under chronic disease conditions and whether outplanting activities may increase disease transmission risk. As the disease transitioned from epizootic outbreak to enzootic persistence, we conducted a large-scale experimental outplanting to assess coral restoration efficacy under chronic SCTLD persistence and to evaluate the relative importance of SCTLD versus non-disease drivers of restoration outcomes. From May 2021 through April 2023, we outplanted 1,165 colonies of three SCTLD-susceptible species ( Montastraea cavernosa, Orbicella faveolata , and Pseudodiploria clivosa ) sourced from land-based facilities and in-water nurseries across six regions spanning FCR and monitored survival and disease incidence. Concurrent surveys of natural coral communities assessed whether outplanting activities affected local SCTLD prevalence. Probabilities of infection per monitoring interval remained <1-2% across all species, regions, and propagation sources throughout the monitoring period. Importantly, outplanting activities did not increase SCTLD prevalence in neighboring natural coral communities. In contrast to the low and relatively uniform disease incidence, variation in coral survival was strongly structured by ecological and operational factors. The overall coral colony survival rate at the end of the study was 77.3% but was influenced by reef stratum (inshore vs. offshore reefs), geographic region, and colony source. M. cavernosa and P. clivosa exhibited higher survival at inshore sites compared to offshore sites, whereas O. faveolata showed no consistent reef stratum effect on survival. Across FCR, survival varied spatially between regions independent of latitude, suggesting local environmental drivers. Colony source effects varied by species. M. cavernosa and P. clivosa from land-based facilities exhibited significantly lower survival than colonies from in-water nurseries, whereas O. faveolata showed no significant differences between propagation sources. Our results indicate that under SCTLD-enzootic conditions, restoration outcomes are shaped more strongly by habitat suitability, geographic context, and propagation-related factors than by SCTLD itself. These findings suggest that coral restoration can proceed within SCTLD-enzootic zones without increasing disease risk to neighboring coral communities or substantially elevating SCTLD-related mortality of outplanted colonies.

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Skipped spawning in a protandric hermaphrodite: Elucidating the physiological mechanisms in common snook Centropomus undecimalis using reproductive biology and energetics - Alexis A. Trotter; Jared L. Ritch; Jessica L. Carroll; Kristin L. Cook; Gregory V. Onorato; Kristen W. Rynerson; David O. Westmark; Colin P. Shea (Journal of Fish Biology, 2026)
Recent acoustic telemetry research has demonstrated that a portion of the common snook Centropomus undecimalis population in Florida skips annual spawning; however, the details of why some individuals skip spawning are unclear. We conducted a comprehensive study of C. undecimalis reproductive biology to determine if a certain population demographic (e.g. size, age, sex, biological condition) skips spawning in a representative estuary in Florida (Tampa Bay). Reproductive parameters, specifically histological examination of ovaries and testes, analysis of reproductive hormone levels and estimates of energetics including fish condition, hepatosomatic and mesenteric fat indices, were analysed for 254 females and 210 males over two consecutive spawning seasons (2016 and 2017). The results agreed with the known reproductive biology of the species and provided a more comprehensive description of developmental patterns throughout the spawning season. Fish that skipped spawning, defined here as an individual of reproductively mature size having both undeveloped gonads and undetectable levels of primary hormone (17β‐estradiol in females, 11‐ketotestosterone in males), represented 18% of fish sampled. Skip spawning individuals were collected from both estuarine and riverine sites, and were predominately smaller and younger females that had spawned at least once previously as females. Fish that skipped spawning had a lower body condition, a lower fat index and, in particular, a lower liver index. As skipped spawning was predominately observed in younger and smaller female C. undecimalis that were energetically depleted, we suggest that the combination of sex transition from male to female, followed by participation in spawning in the next season, leads to most instances of skipped spawning for the species.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The effect of microbes on adult attraction and oviposition in the small hive beetle - Yin Xun Tan; Théotime Colin; Andrew P. Allen; Md Jamil Hossain Biswas; Ajay Narendra; Fleur Ponton (Symbiosis, 2026)

The Integration of Fire Ecology and Freshwater Ecosystems in North America: Knowledge Gaps and Research Needs - Morgan L. Piczak; Ava J. A. Sergio; Caliyena R. Brown; Waverley S. Birch; Rebecca L. Flitcroft; Meg A. Krawchuk; Colin P. R. McCarter; Jonathan W. Moore; Brendan P. Murphy; Brooke E. Penaluna; Prabha A. Rupasinghe; Victoria Steblaj; et al. (Global Change Biology, 2026)
Wildfires, unplanned fires that start and spread under the influence of weather and fuel composition, are increasing in frequency, duration, and severity across North America. While wildfires are one component of wildland fire, a broader natural process in many ecosystems, their changing behavior poses growing ecological and management challenges. Although wildfire is widely recognized as an important disturbance, empirical research quantifying its impacts on freshwater ecosystems remains limited and fragmented. As a result, our understanding of how wildfire affects imperiled freshwater systems remains underdeveloped. The objective of this review was to synthesize the existing empirical literature and identify key knowledge gaps to guide future research on wildfire–freshwater interactions across both biotic and abiotic components. At the biological scale, uncertainties remain around species‐ and community‐level responses (e.g., direct and indirect effects on biota). Freshwater habitat dimensions should also be the focus of further research, including alterations to physical structure (e.g., vegetation) and physicochemical conditions (e.g., temperature). From a management perspective, critical questions relate to fire‐informed restoration (e.g., specialized techniques, role of managed burns) and strategies for enhancing ecosystem resilience (e.g., identifying relevant indicators, links to watershed health). Understanding how land‐use change (e.g., forestry) and climate change interact to influence wildfire regimes and generate cumulative effects across landscapes is also essential in this new wildfire reality. To advance research and practice, we recommend comprehensive monitoring, standardization of methods and indicators, recognition of the role of cultural and prescribed burns, meaningful knowledge co‐production, and bridging the gap between scientific knowledge and management action.

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Non‐Correlated Variation of Leaf and Fine Root Traits in Subtropical Forest Plants - Yuzhi Zhu; Meng Li; Junyong Zheng; Yongqiang Wang; Yanghang Ren; Han Zhang; Zeyu Feng; Sandy P. Harrison; I. Colin Prentice; Yue Zhang; Lewei Jin; Shuang Sun; et al. (Ecology Letters, 2026)
Plants employ multiple strategies to adapt to their growth environment. Characterizing key dimensions in plant trait space is important for understanding functional diversity within ecosystems. Leaf and root functional traits have been studied in the context of resource economics, but whether they covary, and through which mechanisms, is still debated. We investigated this in subtropical forests by sampling root and leaf traits on individuals of co‐existing species in two communities with different resource availability. We found largely non‐correlated variation between leaf and fine root traits both across and within communities, and a clear decoupling between leaf economic spectrum and root economic space, independent of evolutionary history. Our results suggest that leaf‐root trait relationships are shaped by an interplay between microenvironmental heterogeneity that drives decoupling and shared selection pressures promoting covariation. The interplay explains the weak observed coordination and highlights the importance of environmental context in predicting above‐ and below‐ground plant functions.

Pregnancy Eating Attitudes-Questionnaire (PEA-Q): Longitudinal measurement invariance from early to late pregnancy in a community sample - Riley J. Jouppi; Colin E. Vize; Christine C. Call; Rebecca L. Emery Tavernier; Lydia B. Brown; Rachel P. Kolko Conlon; Jennifer L. Grace; Gina M. Sweeney; Michele D. Levine (Appetite, 2026)

Last Interglacial (MIS 5e) and Holocene sea surface temperature and environmental reconstructions from Yorke Peninsula, southern Australia - Tsun-You Pan; Allan R. Chivas; Colin V. Murray-Wallace; David J. Wheeler; Robert P. Bourman (Marine Geology, 2026)

Forecasting circular economy indicators: A Machine Learning study of European Union member states - Niamh McMahon; Colin Fitzpatrick; Cornelis P. Baldé; Sara Bottausci; Eoin M. Grua (Journal of Cleaner Production, 2026)

Quantifying and mapping tree cover in Alberta and Manitoba’s prairie landscapes - Elham Shafeian; Bryan J. Mood; Kenneth W. Belcher; Colin P. Laroque (International Journal of Remote Sensing, 2026)

Investigating the effects of biogenic amines on the dominance hierarchy in the small carpenter bee, Ceratina calcarata - Riya N. Miller; Sandra M. Rehan; Chelsea N. Cook; Colin S. Brent; Sarah P. Lawson (Insectes Sociaux, 2026)
Biogenic amines are highly conserved across animal species and aid in the regulation of movement, behavior, motivation, temperature, blood pressure, and endocrine secretion. Within eusocial species, such as the honey bee Apis mellifera , biogenic amines are responsible for modulating traits associated with higher levels of sociality, such as division of labor. In Ceratina calcarata , a facultatively social bee species, mothers establish a dominance hierarchy over their eldest daughter by providing them with less pollen and less protein, resulting in smaller, more submissive adults referred to as dwarf eldest daughters (DEDs). We hypothesized that this dominance hierarchy is additionally modulated by biogenic amines. To examine this hypothesis, we first compared biogenic amine levels between mothers and daughters and found significantly higher levels of dopamine, octopamine and tyramine in the mothers. To quantify the effects of these biogenic amine differences, dopamine was topically administered to C. calcarata DEDs, while the mothers were topically treated with the dopamine blocker cis-(Z)-Flupentixol dihydrochloride. Aggression helps to establish social hierarchies, so mothers and DEDs from the same nest underwent behavioral assays to assess aggressive and tolerant behaviors. When dopamine was blocked in the naturally more aggressive mothers, there was no difference in the number of aggressive interactions. Instead, treated mothers became more tolerant of DEDs, indicating dopamine plays a key role in modulating these behaviors. More work is needed to understand the different roles each biogenic amine plays in the development of a dominance hierarchy, especially in these species on the brink of eusociality.

AI-enhanced sorting enabling direct high-purity tantalum urban mining: a novel pathway from e-waste to critical materials - Dong Xia; Kok Yuen Koh; Raunaq Nayar; Colin Locoge; Nicolas M. Charpentier; Mya Mya Khin; Tien Hoa Nguyen; Guillaume Zante; Hicham Khodja; Jean-Christophe P. Gabriel (Resources, Conservation and Recycling, 2026)

Trace element accumulation in green turtles (Chelonia mydas) foraging in locations of differing chemical input - Nicole B. Rowberry; Arthur D. Barraza; Colin J. Limpus; Jason P. van de Merwe; Kimberly A. Finlayson (Regional Studies in Marine Science, 2026)

Identification of Dolly Varden (Salvelinus malma) in the Canadian Arctic east of the Mackenzie River - Spencer Y. Weinstein; Amanda Dumond; Tracey N. Loewen; James D. Reist; Matthew C. Hale; Colin P. Gallagher; Jean-Sébastien Moore; Les N. Harris; Ross F. Tallman; Robert Bajno; Zoya A. Martin; Paul M. Craig; et al. (Environmental Biology of Fishes, 2026)

Does fishery management for groupers (Teleostei: Epinephelidae) protect them effectively? Context from the IUCN's Red list of threatened species - Sean T. Fennessy; Christi Linardich; Kevin Rhodes; Joao P. Barreiros; David Pollard; Eloy Sosa-Cordero; Felicia Coleman; Alfonso Aguilar-Perera; Christopher R. Malinowski; Thierry Brulé; Pedro Afonso; Kayan Ma; et al. (Ocean & Coastal Management, 2026)

Evaluation of a copper(I)-Biquinoline complex modified electrode for electrochemical detection of nitrite in water - Natalia P. Martínez; Verónica Valladares; Colin Poblete; Jessica Honores; Elías Leiva Farías; Esteban Landaeta; Diego Guzman; Franciso Armijo; Juan Guerrero; Mauricio Isaacs (Food Chemistry, 2026)

Influence of global climate modes on wildfire occurrence in the contiguous United States under recent and future climates - Theodore R. Keeping; Theodore G. Shepherd; I. Colin Prentice; Karin van der Wiel; Sandy P. Harrison (Climate Dynamics, 2026)
Predictable modes of climate variability, such as the El Niño Southern Oscillation (ENSO), have a major influence on regional weather patterns, an important control on wildfire occurrence. Although these global climate modes have been associated with historical variability in wildfire occurrence in the United States and are used to forecast seasonal wildfire risk, precise information about the spatial pattern and magnitude of their influence is lacking and the satellite record of wildfires is too short to address these issues. Here we use wildfire occurrence model with a large ensemble of 1600 simulated years from EC-Earth3 in a recent climate (2000–2009) and a future climate corresponding to + 2 °C global warming, to characterise the impact of specific climate modes on wildfire occurrence in the contiguous US. We show that ENSO, the Indian Ocean Dipole (IOD), and the 1-year lagged Tropical North Atlantic (TNA+1) have the greatest effect on annual fire occurrence—strongly contributed by the effect of these modes on hot, dry conditions in the Great Plains and precipitation in the southwestern US. El Niño is not significantly associated with wildfire occurrence in the northwestern US, contrary to expectation, but is associated with a later (earlier) wildfire season peak in the southwestern (southeastern) US. Under future warming, the AMO and PNA become a significant influence over most of the US, and the magnitude of impact of ENSO and TNA+1 increase strongly.

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Pier pressure: 23 years of incidental sea turtle captures at recreational fishing piers along Florida’s Gulf coastline - Robby J. Brannum; Karrie Minch; Morgan Wideroff; Meghan E. Koperski; Colin P. Shea; Allen M. Foley; Robbin N. Trindell (Frontiers in Marine Science, 2025)
Incidental captures of sea turtles during fishing activities affect their populations worldwide. Previous research has documented the impacts of commercial fisheries in nearshore and offshore waters, and research-based minimization measures are now required to reduce sea turtle take. However, incidental captures of juvenile-to-adult sea turtles also occur in recreational fisheries in nearshore and inshore waters, although the magnitude and distribution of these events are poorly understood. We analyzed Florida Sea Turtle Stranding and Salvage Network (STSSN) reports between 2000 and 2022 to identify sea turtles incidentally captured by recreational anglers from fishing piers along Florida’s Gulf coastline. We used a negative binomial regression model to quantify temporal and spatial changes in the mean number of pier-captured sea turtles reported at Gulf piers over the 23-year study period. There were 452 documented incidents of loggerheads ( Caretta caretta ), green turtles ( Chelonia mydas ), and Kemp’s ridleys ( Lepidochelys kempii ) hooked at 33 different piers. Juvenile and subadult turtles of all three species were pier-captured as well as adult loggerhead and Kemp’s ridley turtles. The number of turtles for each of the three species captured varied over time, but overall the number of reported captures increased regionally over the 23-year study. Most turtles captured and recovered at recreational fishing piers were successfully rehabilitated and released back to the wild (84.7.%). The observed increases in sea turtle pier capture reports likely reflect some combination of increased turtle numbers in the nearshore environment, increased use of piers as foraging habitat, and increased reporting requirements and effort. This analysis offers insights into the complex interactions between sea turtles and pier-based recreational fishing in the Gulf and could help inform conservation efforts while supporting responsible recreational fishing practices.

Combined exposure of poly(lactic-co-glycolic acid) microplastics and global warming affects the population dynamics of a coastal copepod - Zhiyue Niu; Jana Asselman; Colin R. Janssen; Charlotte P. Linley; Karel De Schamphelaere; Gert Everaert; Ana I. Catarino (Marine Pollution Bulletin, 2025)

Forest breaks improve employees’ health and attitudes towards work - Daniel P. Longman; Yvanna Todorova; Nicolette C. Bishop; Janine K. Coates; Lewis J. James; Adelina Lintuluoto; Colin N. Shaw (Urban Forestry & Urban Greening, 2025)

The Effect of High Temperatures on the Growth and Biochemical Composition of Cultivated Palmaria Palmata (Rhodophyta) - Ilias Semmouri; Sophie Vanhercke; Andreia S. Ferreira; Jessica Knoop; Olivier De Clerck; Cláudia Nunes; Manuel A. Coimbra; Leonardo M. de Souza Mesquita; Sónia P. M. Ventura; Colin R. Janssen; Jana Asselman (Marine Biotechnology, 2025)

Dietary niches of endemic and range-expanding salmonids in the western Canadian Arctic - Darcy G. McNicholl; Colin P. Gallagher; Richard Gordon; Tyler Carmichael; Ryan McLeod; Joe Illasiak; Leona Kayotuk; Max Kotokak; Sarah Lord; Jasmine Brewster; Sarah Buckle; Cora-Lee Simpson; et al. (Environmental Biology of Fishes, 2025)
The cumulative effects of climate change are impacting Arctic species and facilitating increased interactions between Arctic and sub-Arctic species. Anadromous Arctic char Salvelinus alpinus and the northern Dolly Varden Salvelinus malma malma are endemic Arctic fishes vulnerable to the impacts of climate change, yet our understanding of the dietary niches they occupy is limited. The recent increased occurrence of sub-Arctic Pacific salmon ( Oncorhynchus spp.) in the western Canadian Arctic has raised concerns among Indigenous communities given the potential for competition with endemic fishes important for subsistence fisheries. Stable isotopes (δ 13 C and δ 15 N) were analyzed from Arctic char, Dolly Varden, and chum salmon Oncorhynchus keta , collected among four coastal Canadian Beaufort Sea locations. These fishes were captured during the summer of 2017 and 2019 during ongoing community-based fisheries monitoring programs in the Inuvialuit Settlement Region and Gwich’in Settlement Area. The trophic position of Arctic char and Dolly Varden indicates both species rely heavily on pelagic prey enriched in δ 15 N, consistent with a diet of marine forage fishes. Chum salmon occupied a trophic position > 3.0‰ below the char species, which reflects a diet comprised primarily of marine invertebrates. Isotopic niche analyses revealed chum salmon do not overlap in diet with the char species during the summer marine foraging season, and thus were unlikely to compete for prey as adults. This assessment of dietary overlap informs conservation and fisheries co-management objectives of endemic fishes as their as interactions with range-expanding species become more prevalent within a rapidly changing Arctic.

Native aspen carbon cache: quantifying carbon differences under copses in the black soil zone of the Canadian Prairies - Andrea V. Cline; Colin P. Laroque (Agroforestry Systems, 2025)

Recent Chemo-morphological coma evolution of comet 67P/Churyumov–Gerasimenko - Brian P. Murphy; Cyrielle Opitom; Colin Snodgrass; Sophie E. Deam; Léa Ferellec; Matthew Knight; Vincent Okoth; Bin Yang (Planetary and Space Science, 2025)

Role of viral coinfection in post-pandemic invasive Group A streptococcal infections in adults, a nation-wide cohort study (iGASWISS) - S. Musumeci; A. MacPhail; M. Weisser Rohacek; A. Erba; D. Goldenberger; C. Lang; E. Colin-Benoit; S. L. Leib; P. Sendi; C. Chuard; V. Erard; C. Fournier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Objective During the winter season of 2022–2023, numerous countries experienced a surge in invasive Streptococcus pyogenes (iGAS) infections. The role of viral coinfections in the post-COVID surge has not been elucidated. We report nation-wide data describing clinical presentation, microbiological characteristics, and associations with viral infection in adults during this period. Methods A multicenter retrospective cohort study was conducted across 10 hospitals in Switzerland, including adults (> 16 years old) with iGAS infection from November 2022 to February 2023. Descriptive analysis was performed. A multivariable logistic regression model was fitted to assess the impact of viral coinfection. In addition, genetic analysis was performed in available isolates. Results A total of 194 patients were included, with a median age of 50 years (interquartile range [IQR]: 37–69). 17/194 (8.8%) were immunosuppressed and 40/194 (20.6%) exhibited concomitant viral infections, predominantly Influenza A (21/40, 53%). Illness severity was high: 65/194 (33.5%) of cases necessitated admission to an intensive care unit (ICU), and the 30-day mortality was 4% ( n = 8). Among the available strains for genetic analysis ( n = 48), heterogeneity was found although ST28- emm 1 isolates (also known as M1UK) was predominant (22/48). Conclusion The post-COVID iGAS surge in Switzerland was associated with high levels of morbidity and mortality in immunocompetent adults. M1UK was predominant within the iGAS strains circulating in Switzerland during the study period and viral coinfection was a predictor for ICU admission and mortality.

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

More individuals or more groups? Incorporating sampling effort, statistical power, and model accuracy when designing experiments - Colin M. Lynch; M. Starkey; D. Montgomery; T. P. Pavlic; N. Mizumoto (Behavioral Ecology and Sociobiology, 2025)

Current Views on Addressing Nutritional Concerns in Adult Cystic Fibrosis Patients from Practicing Registered Dietitians - C. West; M. Kay; P. Davidson; L. Wright; C. Colin (Journal of the Academy of Nutrition and Dietetics, 2025)

Wave impacts on vertical cliffs: Insights from laboratory experiments and field observations - Yaxiong Shen; Colin N. Whittaker; Catriona F. Thompson; Alison C. Raby; Adam P. Young; Mark E. Dickson (Coastal Engineering, 2025)

Assessing Plastic Pollution in Kenyan Mangroves: Distribution, Sources, and Social Impact in Gazi Bay - Elissa P. B. Pelsmaekers; Colin R. Janssen; Stefano Cannicci; Cosmas Nzaka Munga; Farid Dahdouh-Guebas (Estuaries and Coasts, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Chironomid-based paleotemperature reconstruction of the North Slave Region (Northwest Territories, Canada) during the Late Holocene - Colin Robertson; Nicolas Pelletier; John P. Smol; Jesse C. Vermaire (Journal of Paleolimnology, 2025)

Below-ground carbon gradients surrounding Saskatchewan's native agricultural copses - Andrea V. Cline; Colin P. Laroque (Science of The Total Environment, 2025)

Predicting wave runup on composite beaches - Matthew P. Conlin; Gregory Wilson; Hailey Bond; Dorukhan Ardağ; Colin Arnowil (Coastal Engineering, 2025)

Combined rupture mechanisms of shallow foundations: implications in limit state design - Luca P. Argani; Alessandro Gajo; Colin C. Smith (European Journal of Environmental and Civil Engineering, 2025)

‘Domesticability’: were some species predisposed for domestication? - Anne J. Romero; Anastasia Kolesnikova; Thomas H.G. Ezard; Michael Charles; Rafal M. Gutaker; Colin P. Osborne; Mark A. Chapman (Trends in Ecology & Evolution, 2025)

Investigating chemical risk in green and loggerhead turtles foraging in Moreton Bay using species-specific cell-based bioassays - Janelle C. Kenney; Dylan White-Kiely; Jason P. van de Merwe; Colin J. Limpus; Kimberly A. Finlayson (Marine Pollution Bulletin, 2025)

Can darker window tints reduce interior light impacts to hatchling sea turtles on developed coastlines? An experimental assessment - Tonya M. Long; Rachael Anderson; Simona A. Ceriani; Christina Frederick; Meghan Koperski; Colin P. Shea; Morgan Wideroff; Robbin N. Trindell (Journal for Nature Conservation, 2025)

Late Amazonian ice near Athabasca Valles, Mars: Recent megaflood or climate change? - Colin M. Dundas; Laszlo P. Keszthelyi; Kaj E. Williams (Icarus, 2025)

A General Model for the Seasonal to Decadal Dynamics of Leaf Area - Boya Zhou; Wenjia Cai; Ziqi Zhu; Han Wang; Sandy P. Harrison; I. Colin Prentice (Global Change Biology, 2025)
Leaf phenology, represented at the ecosystem scale by the seasonal dynamics of leaf area index (LAI), is a key control on the exchanges of CO 2 , energy, and water between the land and atmosphere. Robust simulation of leaf phenology is thus important for both dynamic global vegetation models (DGVMs) and land‐surface representations in climate and Earth System models. There is no general agreement on how leaf phenology should be modeled. However, a recent theoretical advance posits a universal relationship between the time course of “steady‐state” gross primary production (GPP) and LAI—that is, the mutually consistent LAI and GPP that would pertain if weather conditions were held constant. This theory embodies the concept that leaves should be displayed when their presence is most beneficial to plants, combined with the reciprocal relationship of LAI and GPP via (a) the Beer's law dependence of GPP on LAI, and (b) the requirement for GPP to support the allocation of carbon to leaves. Here we develop a global prognostic LAI model, combining this theoretical approach with a parameter‐sparse terrestrial GPP model (the P model) that achieves a good fit to GPP derived from flux towers in all biomes and a scheme based on the P model that predicts seasonal maximum LAI as the lesser of an energy‐limited rate (maximizing GPP) and a water‐limited rate (maximizing the use of available precipitation). The exponential moving average method is used to represent the time lag between leaf allocation and modeled steady‐state LAI. The model captures satellite‐derived LAI dynamics across biomes at both site and global levels. Since this model outperforms the 15 DGVMs used in the TRENDY project, it could provide a basis for improved representation of leaf‐area dynamics in vegetation and climate models.

The Response of Carbon Uptake to Soil Moisture Stress: Adaptation to Climatic Aridity - Giulia Mengoli; Sandy P. Harrison; I. Colin Prentice (Global Change Biology, 2025)
The coupling between carbon uptake and water loss through stomata implies that gross primary production (GPP) can be limited by soil water availability through reduced leaf area and/or stomatal conductance. Ecosystem and land‐surface models commonly assume that GPP is highest under well‐watered conditions and apply a stress function to reduce GPP as soil moisture declines. Optimality considerations, however, suggest that the stress function should depend on climatic aridity: ecosystems adapted to more arid climates should use water more conservatively when soil moisture is high, but maintain unchanged GPP down to a lower critical soil‐moisture threshold. We use eddy‐covariance flux data to test this hypothesis. We investigate how the light‐use efficiency (LUE) of GPP depends on soil moisture across ecosystems representing a wide range of climatic aridity. ‘Well‐watered’ GPP is estimated using the sub‐daily P model, a first‐principles LUE model driven by atmospheric data and remotely sensed vegetation cover. Breakpoint regression is used to relate daily β(θ) (the ratio of flux data–derived GPP to modelled well‐watered GPP) to soil moisture estimated via a generic water balance model. The resulting piecewise function describing β(θ) varies with aridity, as hypothesised. Unstressed LUE, even when soil moisture is high, declines with increasing aridity index (AI). So does the critical soil‐moisture threshold. Moreover, for any AI value, there exists a soil moisture level at which β(θ) is maximised. This level declines as AI increases. This behaviour is captured by universal non‐linear functions relating both unstressed LUE and the critical soil‐moisture threshold to AI. Applying these aridity‐based functions to predict the site‐level response of LUE to soil moisture substantially improves GPP simulation under both water‐stressed and unstressed conditions, suggesting a route towards a robust, universal model representation of the effects of low soil moisture on leaf‐level photosynthesis.

Fire-Image-DenseNet (FIDN) for predicting wildfire burnt area using remote sensing data - Bo Pang; Sibo Cheng; Yuhan Huang; Yufang Jin; Yike Guo; I. Colin Prentice; Sandy P. Harrison; Rossella Arcucci (Computers & Geosciences, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Soil Nitrogen Supply Exerts Largest Influence on Leaf Nitrogen in Environments with the Greatest Leaf Nitrogen Demand - Alissar Cheaib; Elizabeth F. Waring; Risa McNellis; Evan A. Perkowski; Jason P. Martina; Eric W. Seabloom; Elizabeth T. Borer; Peter A. Wilfahrt; Ning Dong; Iain Colin Prentice; Ian J. Wright; Sally A. Power; et al. (Ecology Letters, 2025)
Accurately representing the relationships between nitrogen supply and photosynthesis is crucial for reliably predicting carbon–nitrogen cycle coupling in Earth System Models (ESMs). Most ESMs assume positive correlations amongst soil nitrogen supply, leaf nitrogen content, and photosynthetic capacity. However, leaf photosynthetic nitrogen demand may influence the leaf nitrogen response to soil nitrogen supply; thus, responses to nitrogen supply are expected to be the largest in environments where demand is the greatest. Using a nutrient addition experiment replicated across 26 sites spanning four continents, we demonstrated that climate variables were stronger predictors of leaf nitrogen content than soil nutrient supply. Leaf nitrogen increased more strongly with soil nitrogen supply in regions with the highest theoretical leaf nitrogen demand, increasing more in colder and drier environments than warmer and wetter environments. Thus, leaf nitrogen responses to nitrogen supply are primarily influenced by climatic gradients in photosynthetic nitrogen demand, an insight that could improve ESM predictions.

Forward modelling of white spruce radial growth at trailing edge demonstrates high plasticity - Bryan J. Mood; Colin P. Laroque (Science of The Total Environment, 2024)

Natural Source Zone Depletion of crude oil, gasoline, diesel and aviation gasoline petroleum in the same soil/aquifer system – An intensive intercomparison field study and simulation - John L. Rayner; Mike J. Donn; Greg B. Davis; Trevor P. Bastow; Kaveh Sookhak Lari; Colin D. Johnston; Andrew King; Andrew Furness (Science of The Total Environment, 2024)

An inception framework hypothesis for karst development in the Burren, Ireland - Robert A. Watson; Colin Bunce; David Drew; Simone Fiaschi; Caoimhe Hickey; John Walsh; Eoghan P. Holohan (Geomorphology, 2024)

Characterizing Juvenile Common Snook and Tarpon Habitat to Guide Conservation and Restoration of Coastal Wetlands - Philip W. Stevens; David A. Blewett; Corey R. Anderson; Courtney R. Saari; Colin P. Shea; Casey A. Craig; Kara R. Radabaugh (Wetlands, 2024)
To conserve or restore juvenile fish habitat, resource managers, restoration practitioners, and engineers need fine-scale information to understand what conditions they need to preserve or what specifications are needed to create new habitat. The objective of this study was to develop statistical models using a dataset of 18 coastal ponds in Southwest Florida, USA, to predict the abundance of juvenile common snook Centropomus undecimalis (hereafter snook) and presence of juvenile tarpon Megalops atlanticus , both of which are flagship species used for conservation and restoration of subtropical and tropical wetlands. Model predictors included water conditions and characteristics of vegetation, sediment, and geographic position. Modeling results indicated that juvenile snook used coastal ponds that were directly connected to tidal creeks. In contrast, juvenile tarpon were more likely to be present in coastal ponds that were separated from tidal creeks by dense mangrove forest (e.g., elevation > 0.48 m above Mean Low Water) characterized by highly organic sediment and low dissolved oxygen, to which tarpon are well adapted. Overlap between snook abundance and tarpon presence was greatest where connections between ponds and the nearest tidal creek were at a relatively low elevation (e.g., -0.12 m relative to Mean Low Water). Although these findings are most applicable to management and conservation of populations in areas along the Gulf coast of Florida (i.e., in areas of similar tidal range and coastal geomorphology), incorporating more detailed habitat surveys to better capture landscape context, geomorphology, and connectivity into fish sampling designs should be broadly applicable to estuarine fish ecology.

Herbivore kairomones affect germination speed, seedling growth, and herbivory - Brooke A. Pellegrini; Lina S. Pintado; Paige N. Souza; Santhi P. Bhavanam; Colin M. Orians; John L. Orrock; Evan L. Preisser (Oecologia, 2024)
Seeds and seedlings are particularly vulnerable to herbivory. Unlike mature plants, which can wait until herbivory is experienced to induce defense, seeds and seedlings face mortality if they wait. Slug mucus functions as a kairomone, a non-attack-related substance emitted by consumers that is detected by a prey species (in this case, plants). While snail mucus has been shown to induce defense in seedlings, it is not widely confirmed whether slugs have the same effect and whether seeds can also detect and react to such herbivore cues. We investigated how exposure to Arion subfuscus mucus affected growth and defense in Brassica nigra seeds and seedlings. Seeds exposed to slug mucus germinated 5% faster than control (water only) seeds, but the resulting seedlings weighed 16% less than control seedlings. To test whether this difference results from herbivore-exposed plants allocating energy from growth to defense, we conducted choice bioassays assessing slug preference for control seedlings versus seedlings that were either (A) exposed to mucus only as a seed; or (B) exposed to mucus as a seed and seedling. While slugs did not differentiate between control seedlings and ones exposed to herbivore cues only as a seed, they ate 88% less biomass of seedlings exposed to mucus as both seeds and seedlings. These results suggest that slug mucus induces changes in plant traits related to defense and growth/competitive ability. Future research should determine the chemical mechanisms of this induced defense.

Emigration of Juvenile Tarpon Megalops atlanticus from Ephemerally Connected Coastal Ponds - Matthew S. Bunting; Philip W. Stevens; David A. Blewett; Quenton M. Tuckett; Jeffrey E. Hill; Gregg R. Poulakis; Colin P. Shea; Courtney R. Saari (Estuaries and Coasts, 2024)
Worldwide, coastal wetlands are threatened by disrupted hydrology, urbanization, and sea-level rise. In southwest Florida, coastal wetlands include tidal creeks and coastal ponds, which are the primary habitats used by juvenile Tarpon, Megalops atlanticus , an important sport fish. Coastal ponds can occur near uplands and are ephemerally connected to the open estuary, creating conditions of variable dissolved oxygen and salinity. Juveniles can tolerate wide-ranging abiotic conditions, but little is known about how they egress from their remote nursery habitats, which often requires them to cross > 1 km of mangrove forest to reach the open estuary. The objective of this study was to (1) compare Tarpon body condition among ponds close to the open estuary versus those ponds farther away on the Cape Haze peninsula of Charlotte Harbor, Florida, and (2) using acoustic telemetry determine what factors contribute to Tarpon emigration from the ponds to open estuarine waters. We tested the hypothesis that distinct groups of Tarpon occur in isolated ponds, leading to variation in fish length and body condition, and that opportunities for emigration from these ponds hinge on high water events. No pond stood out as having Tarpon of low body condition. Factors contributing to increased probabilities of Tarpon emigration were low barometric pressure, high-water level, and Tarpon body length. Tarpon emigrated from ponds near tidal creeks during summer king tides, while tropical cyclone conditions were needed to allow for movement from ponds farther in the landscape. The juvenile Tarpon were later detected at the mouths of large rivers 30 km up-estuary. The characterizations of water levels and event criteria needed for successful Tarpon nurseries should aid in habitat conservation and the creation of Tarpon nursery habitat in restoration designs.

A genome assembly and transcriptome atlas of the inbred Babraham pig to illuminate porcine immunogenetic variation - John C. Schwartz; Colin P. Farrell; Graham Freimanis; Andrew K. Sewell; John D. Phillips; John A. Hammond (Immunogenetics, 2024)
The inbred Babraham pig serves as a valuable biomedical model for research due to its high level of homozygosity, including in the major histocompatibility complex (MHC) loci and likely other important immune-related gene complexes, which are generally highly diverse in outbred populations. As the ability to control for this diversity using inbred organisms is of great utility, we sought to improve this resource by generating a long-read whole genome assembly and transcriptome atlas of a Babraham pig. The genome was de novo assembled using PacBio long reads and error-corrected using Illumina short reads. Assembled contigs were then mapped to the porcine reference assembly, Sscrofa11.1, to generate chromosome-level scaffolds. The resulting TPI_Babraham_pig_v1 assembly is nearly as contiguous as Sscrofa11.1 with a contig N50 of 34.95 Mb and contig L50 of 23. The remaining sequence gaps are generally the result of poor assembly across large and highly repetitive regions such as the centromeres and tandemly duplicated gene families, including immune-related gene complexes, that often vary in gene content between haplotypes. We also further confirm homozygosity across the Babraham MHC and characterize the allele content and tissue expression of several other immune-related gene complexes, including the antibody and T cell receptor loci, the natural killer complex, and the leukocyte receptor complex. The Babraham pig genome assembly provides an alternate highly contiguous porcine genome assembly as a resource for the livestock genomics community. The assembly will also aid biomedical and veterinary research that utilizes this animal model such as when controlling for genetic variation is critical.

Advancing an integrated understanding of land–ocean connections in shaping the marine ecosystems of coastal temperate rainforest ecoregions - Brian P. V. Hunt; Simone Alin; Allison Bidlack; Heida L. Diefenderfer; Jennifer M. Jackson; Colleen T. E. Kellogg; Peter Kiffney; Kyra A. St. Pierre; Eddy Carmack; William C. Floyd; Eran Hood; Alexander R. Horner‐Devine; et al. (Limnology and Oceanography, 2024)
Land and ocean ecosystems are strongly connected and mutually interactive. As climate changes and other anthropogenic stressors intensify, the complex pathways that link these systems will strengthen or weaken in ways that are currently beyond reliable prediction. In this review we offer a framework of land–ocean couplings and their role in shaping marine ecosystems in coastal temperate rainforest (CTR) ecoregions, where high freshwater and materials flux result in particularly strong land–ocean connections. Using the largest contiguous expanse of CTR on Earth—the Northeast Pacific CTR (NPCTR)—as a case study, we integrate current understanding of the spatial and temporal scales of interacting processes across the land–ocean continuum, and examine how these processes structure and are defining features of marine ecosystems from nearshore to offshore domains. We look ahead to the potential effects of climate and other anthropogenic changes on the coupled land–ocean meta‐ecosystem. Finally, we review key data gaps and provide research recommendations for an integrated, transdisciplinary approach with the intent to guide future evaluations of and management recommendations for ongoing impacts to marine ecosystems of the NPCTR and other CTRs globally. In the light of extreme events including heatwaves, fire, and flooding, which are occurring almost annually, this integrative agenda is not only necessary but urgent.

Assessing South Indian Ocean tropical cyclone characteristics in HighResMIP simulations - Pardeep Pall; Alexandre S. Gagnon; Massimo A. Bollasina; Colin M. Zarzycki; Yuner Huang; Christopher T. S. Beckett; Harinaivo Ramanantoanina; Thomas P. S. Reynolds (International Journal of Climatology, 2024)
Several damaging tropical cyclones (TCs) have occurred recently over the South Indian Ocean (SIO) region, causing enormous social and economic losses. Yet, while many studies have examined SIO TC characteristics using observations and reanalysis, only a few have assessed these characteristics specifically for this region in climate models, and fewer have investigated their projections under climate change. Here we do this for a historical (1980–2010) and future (2020–2050) period, using multimodel simulations from the High Resolution Model Intercomparison Project, as well as examine biases in the historical period relative to a reanalysis (ERA5). The models have horizontal resolutions of 25–50 km, which has enabled an improved ability to represent tropical cyclones globally in previous studies. TempestExtremes software is employed to detect tropical storm and cyclone tracks. In cases where TempestExtremes cannot be applied due to a lack of requisite variables in a dataset, we instead examine extreme wind speeds in that dataset. For the historical period, we find considerable variation in model biases compared to ERA5, which itself exhibits realistic spatial patterns of tracks and their monthly distribution. Models do at least agree on positive biases in track frequency east of Madagascar and somewhat in the Mozambique Channel. However, the models and ERA5 only produce Category 3 tropical cyclones at best. Wind speeds for 25 km resolution models have much larger positive biases than for 50 km ones, suggesting the former can simulate even higher‐category tropical cyclones. Considerable intermodel variation is also found in track changes between the future and historical periods. No systematic intercategory pattern of change exists, and low signal‐to‐noise may obscure any such patterns in the limited timespan of available data. Thus, no meaningful conclusions can be drawn regarding changes in track intensity. Nevertheless, track frequency broadly decreases across models for the region, as does accumulated cyclone energy. An east‐to‐west shift in track location from east of Madagascar toward the Mozambique Channel is also implied by track frequency and wind speed changes. Our findings provide information to potentially improve storm resiliency in this vulnerable region.

Gill raker and pyloric caeca counts differ between Arctic char ( Salvelinus alpinus ) and Dolly Varden ( S. malma ) populations across their ranges - Spencer Y. Weinstein; Colin P. Gallagher; Matthew C. Hale; Tracey N. Loewen; James D. Reist; Heidi K. Swanson (Journal of Fish Biology, 2024)
Meristic characters are often used to differentiate between closely related forms, morphs, and species of fishes, and lend insight into ecology and post‐glacial recolonization in taxa with complicated or contentious phylogenies, including the genus Salvelinus . Previous studies of meristics in Salvelinus have focused mostly on individual populations. We collated data from 456 populations/systems across the North American and Russian Arctic and sub‐Arctic, and found that counts of pyloric caeca and gill rakers differed consistently between fish visually and/or genetically identified as Arctic char and Dolly Varden across their distributional ranges.

Persistent global greening over the last four decades using novel long-term vegetation index data with enhanced temporal consistency - Sungchan Jeong; Youngryel Ryu; Pierre Gentine; Xu Lian; Jianing Fang; Xing Li; Benjamin Dechant; Juwon Kong; Wonseok Choi; Chongya Jiang; Trevor F. Keenan; Sandy P. Harrison; et al. (Remote Sensing of Environment, 2024)

Species-specific bioassays reveal spatial variation in chemical contamination of green sea turtles - Dylan White-Kiely; Kimberly A. Finlayson; Colin J. Limpus; Matthew Johnson; Jason P. van de Merwe (Marine Environmental Research, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Correction: On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Assessing the risk of climate maladaptation for Canadian polar bears - L. Ruth Rivkin; Evan S. Richardson; Joshua M. Miller; Todd C. Atwood; Steven Baryluk; Erik W. Born; Corey Davis; Markus Dyck; Evelien de Greef; Kristin L. Laidre; Nicholas J. Lunn; Sara McCarthy; et al. (Ecology Letters, 2024)
The Arctic is warming four times faster than the rest of the world, threatening the persistence of many Arctic species. It is uncertain if Arctic wildlife will have sufficient time to adapt to such rapidly warming environments. We used genetic forecasting to measure the risk of maladaptation to warming temperatures and sea ice loss in polar bears ( Ursus maritimus ) sampled across the Canadian Arctic. We found evidence for local adaptation to sea ice conditions and temperature. Forecasting of genome‐environment mismatches for predicted climate scenarios suggested that polar bears in the Canadian high Arctic had the greatest risk of becoming maladapted to climate warming. While Canadian high Arctic bears may be the most likely to become maladapted, all polar bears face potentially negative outcomes to climate change. Given the importance of the sea ice habitat to polar bears, we expect that maladaptation to future warming is already widespread across Canada.

A data-driven analysis of HDPE post-consumer recyclate for sustainable bottle packaging - Philip Smith; Andy McLauchlin; Tom Franklin; Peiyao Yan; Emily Cunliffe; Tom Hasell; Vitaliy Kurlin; Colin Kerr; Jonathan Attwood; Michael P. Shaver; Tom O. McDonald (Resources, Conservation and Recycling, 2024)

The foraging ecology of green turtles (Chelonia mydas) in New Caledonia - Tyffen C. Read; Laurent Wantiez; Florent Keller; Jonathan M. Werry; Jason P. van de Merwe; Justin J. Meager; Olivier Chateau; Richard Farman; Colin J. Limpus (Marine Biology, 2024)
Green sea turtles ( Chelonia mydas ) face many threats from anthropogenic activity and are listed as Endangered on the International Union for the Conservation of Nature (IUCN) Red List of Threatened Species. They spend the majority of their lives in coastal foraging areas, and show strong fidelity to narrow foraging ranges. Understanding the foraging ecology of green turtles is therefore important for their management and conservation. Using stable isotopes analysis ( n = 200) and identification of stomach contents ( n = 21), this study investigated the foraging ecology of four distinct green turtle foraging aggregations (Goro, Isle of Pines, Ouen Island and Uo/Mato Islands) within the Grand Lagon Sud. This World Heritage Area located in New Caledonia supports regionally important nesting and foraging green turtle populations. The δ 13 C and δ 15 N values of skin samples ranged from − 19.3 to − 7.3‰ and 2.8–15.9‰, respectively. Metrics of isotopic niche and regression analyses were used to assess the degree of omnivory, trophic diversity and potential ontogenetic diet shifts in the different aggregations of foraging green turtles in this location. Each of the four sites and four age-classes had distinct isotopic niches, with evidence of omnivory and ontogenetic shifts, particular in new recruits and juveniles, and at Goro and Uo/Mato Islands. This was generally supported by the stomach contents analyses of a small number of green turtles opportunistically sampled from traditional ceremonies. This study provides important information on the foraging ecology of green turtles in New Caledonia, supporting management outcomes in this region. This collaboration with the tribes of the Grand Lagon Sud is also the first step towards the integrated management of the resource.

Holocene vegetation dynamics of the Eastern Mediterranean region: Old controversies addressed by a new analysis - Esmeralda Cruz‐Silva; Sandy P. Harrison; I. Colin Prentice; Elena Marinova (Journal of Biogeography, 2024)
Aim We reconstruct vegetation changes since 12 ky in the Eastern Mediterranean to examine four features of the regional vegetation history that are controversial: the extent of non‐analogue vegetation assemblages in the transition from the Late Glacial to the early Holocene, the synchroneity of postglacial forest expansion, the geographical extent of temperate deciduous forest during the mid‐Holocene and the timing and trigger for the re‐establishment of drought‐tolerant vegetation during the late Holocene. Location The Eastern Mediterranean–Black Sea Caspian Corridor. Taxon Vascular plants. Methods We reconstruct vegetation changes for 122 fossil pollen records using a method that accounts for within‐biome variability in pollen taxon abundance to determine the biome with which a sample has greatest affinity. Per‐biome affinity threshold values were used to identify samples that do not belong to any modern biome. We apply time series analysis and mapping to examine space and time changes. Results Sites with non‐analogue vegetation were most common between 11.5 and 9.5 ky and mostly in the Carpathians. The transition from open vegetation to forest occurred at 10.64 ± 0.65 ky across the whole region. Temperate deciduous forest was not more extensive at 6 ky; maximum expansion occurred between 5.5 and 5 ky. Expansion of forest occurred between c. 4 and 2.8 k, followed by an abrupt decrease and a subsequent recovery. This pattern is not consistent with a systematic decline of forest towards more drought‐tolerant vegetation in the late Holocene but is consistent with centennial‐scale speleothem patterns linked to variations in moisture availability. Main Conclusions We show the occurrence of non‐analogue vegetation types peaked during early Holocene, forest expansion was synchronous across the region and there was an expansion of moisture‐demanding temperate trees around 5.5 to 5 ky. There is no signal of a continuous late Holocene aridification, but changes in forest cover appear to reflect climatic rather than anthropogenic influences.

β-tubulin functions in spermatogenesis in Lygus hesperus Knight - Chan C. Heu; Kevin P. Le; Roni J. Gross; Inana X. Schutze; Dannialle M. LeRoy; Daniel Langhorst; Colin S. Brent; Jeffrey A. Fabrick; J. Joe Hull (Journal of Insect Physiology, 2024)

On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Novel host plant use by a specialist insect depends on geographic variation in both the host and herbivore species - James P. Michielini; Xianfeng Yi; Leone M. Brown; Shan Ming Gao; Colin Orians; Elizabeth E. Crone (Oecologia, 2024)
Understanding the circumstances under which insect herbivores will adopt a novel host plant is a longstanding question in basic and applied ecology. While geographic variation in host use can arise through differences in both herbivore preference and plant characteristics, there is a tendency to attribute geographic variation in host use to regional differences in herbivore preference alone. This is especially true for herbivores specialized to one or a few plant species. We compared how geographic variation in herbivore preference and host plant origin shape regional differences in host plant use by the specialized herbivore, Euphydryas phaeton . In parts of its range, E. phaeton uses only a native host, Chelone glabra , while in others, it also uses an introduced host, Plantago lanceolata . We offered female butterflies from each region the non-native host plant sourced from both regions and compared their oviposition behavior. The non-native host was almost universally rejected by butterflies in the region where only the native plant is used. In the region where butterflies use both hosts, females accepted non-native plants from their natal region twice as often as non-native plants from the other region where they are not used. Acceptance differed substantially among individual butterflies within regions but not among plants within regions. Thus, both individual preference and regional differences in both the insect and non-native host contributed to the geographic variation in different ways. These results highlight that, in addition to herbivore preference, regional differences in perceived plant suitability may be an important driver of diet breadth.

An updated review of the post-glacial history, ecology, and diversity of Arctic char (Salvelinus alpinus) and Dolly Varden (S. malma) - Spencer Y. Weinstein; Colin P. Gallagher; Matthew C. Hale; Tracey N. Loewen; Michael Power; James D. Reist; Heidi K. Swanson (Environmental Biology of Fishes, 2024)

Persistent net release of carbon dioxide and methane from an Alaskan lowland boreal peatland complex - Eugénie S. Euskirchen; Colin W. Edgar; Evan S. Kane; Mark P. Waldrop; Rebecca B. Neumann; Kristen L. Manies; Thomas A. Douglas; Catherine Dieleman; Miriam C. Jones; Merritt R. Turetsky (Global Change Biology, 2024)
Permafrost degradation in peatlands is altering vegetation and soil properties and impacting net carbon storage. We studied four adjacent sites in Alaska with varied permafrost regimes, including a black spruce forest on a peat plateau with permafrost, two collapse scar bogs of different ages formed following thermokarst, and a rich fen without permafrost. Measurements included year‐round eddy covariance estimates of net carbon dioxide (CO 2 ), mid‐April to October methane (CH 4 ) emissions, and environmental variables. From 2011 to 2022, annual rainfall was above the historical average, snow water equivalent increased, and snow‐season duration shortened due to later snow return. Seasonally thawed active layer depths also increased. During this period, all ecosystems acted as slight annual sources of CO 2 (13–59 g C m −2 year −1 ) and stronger sources of CH 4 (11–14 g CH 4 m −2 from ~April to October). The interannual variability of net ecosystem exchange was high, approximately ±100 g C m −2 year −1 , or twice what has been previously reported across other boreal sites. Net CO 2 release was positively related to increased summer rainfall and winter snow water equivalent and later snow return. Controls over CH 4 emissions were related to increased soil moisture and inundation status. The dominant emitter of carbon was the rich fen, which, in addition to being a source of CO 2 , was also the largest CH 4 emitter. These results suggest that the future carbon‐source strength of boreal lowlands in Interior Alaska may be determined by the area occupied by minerotrophic fens, which are expected to become more abundant as permafrost thaw increases hydrologic connectivity. Since our measurements occur within close proximity of each other (≤1 km 2 ), this study also has implications for the spatial scale and data used in benchmarking carbon cycle models and emphasizes the necessity of long‐term measurements to identify carbon cycle process changes in a warming climate.

Impacts of ground-level ozone on sugarcane production - Alexander W. Cheesman; Flossie Brown; Mst Nahid Farha; Thais M. Rosan; Gerd A. Folberth; Felicity Hayes; Barbara B. Moura; Elena Paoletti; Yasutomo Hoshika; Colin P. Osborne; Lucas A. Cernusak; Rafael V. Ribeiro; et al. (Science of The Total Environment, 2023)

Species tree analyses and speciation-based species delimitation support new species in the relict catfish family Diplomystidae and provide insights on recent glacial history in Patagonia - Carlos P. Muñoz-Ramírez; Nicole Colin; Cristian B. Canales-Aguirre; Aliro Manosalva; Ruby López-Rodríguez; Jeet Sukumaran; Konrad Górski (Molecular Phylogenetics and Evolution, 2023)

Effect of fuel temperature on the structure of a high-pressure liquid-fueled swirl flame - John J. Philo; Tristan T. Shahin; Colin T. McDonald; Rohan M. Gejji; Robert P. Lucht; Carson D. Slabaugh (Fuel, 2023)

Neogene uplift and deformation in the northeastern Bird’s Head Peninsula, West Papua, Indonesia: consequences of oblique plate convergence - Sukahar Eka Adi Saputra; Christopher L. Fergusson; Colin V. Murray-Wallace; Allen P. Nutman (International Geology Review, 2023)

Understanding contaminant exposure risks in nesting Loggerhead sea turtle populations - Arthur D. Barraza; Kimberly A. Finlayson; Frederic D.L. Leusch; Colin J. Limpus; Jason P. van de Merwe (Marine Pollution Bulletin, 2023)

Salinity spatial patterns in Mediterranean coastal areas: The legacy of historical water infrastructures - L. Marien; A. Crabit; B. Dewandel; B. Ladouche; P. Fleury; S. Follain; J. Cavero; V. Berteloot; F. Colin (Science of The Total Environment, 2023)

Impacts of stronger winds and less sea ice on Canadian Beaufort Sea shelf ecosystems since the late 1990s - Jade Falardeau; Anne de Vernal; Bianca Fréchette; Claude Hillaire-Marcel; Philippe Archambault; Michael Fritz; Colin P. Gallagher; George Tanski (Estuarine, Coastal and Shelf Science, 2023)

Combined rupture mechanism of shallow foundations under drained conditions - Luca P. Argani; Alessando Gajo; Colin C. Smith (Computers and Geotechnics, 2023)

Divergence in aerobic capacity and energy expenditure influence metabolic tissue mitochondrial protein synthesis rates in aged rats - Edziu Franczak; Adrianna Maurer; Vivien Csikos Drummond; Benjamin A. Kugler; Emily Wells; Madi Wenger; Frederick F. Peelor; Abby Crosswhite; Colin S. McCoin; Lauren G. Koch; Steven L. Britton; Benjamin F. Miller; et al. (GeroScience, 2023)

Micronuclei in human peripheral blood and bone marrow as genotoxicity markers: A systematic review and meta-analysis - Evangelia E. Antoniou; Martijn Rooseboom; Neslihan A. Kocabas; Colin M. North; Maurice P. Zeegers (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

The Effects of Cooling on Fine-Grained Sandstone in Relation to Wellbore Injection of Carbon Dioxide - Nikolaos Reppas; Colin T. Davie; Yilin Gui; Ben Wetenhall; Samuel P. Graham (Rock Mechanics and Rock Engineering, 2023)
In Carbon Capture and Storage (CCS) procedures, it is important to determine the stability of the wellbore during carbon dioxide (CO 2 ) injection and part of this involves assessing stresses on the rock near the wellbore due to changes in temperature and pressure. To address this, this study investigated the influence of cooling on the mechanical properties of a sandstone typical of those found in the central and southern North Sea. A series of uniaxial and triaxial compression tests was conducted on dry and saturated sandstone samples to determine the effects of cooling on the strength and stiffness under different confining pressures. The elastic modulus, shear modulus, bulk modulus and Poisson’s ratio were determined for three temperature conditions and three pressures representing different depths in a wellbore. Two methods, the International Society of Rock Mechanics (ISRM) and Wood’s (Soil behaviour and critical state soil mechanics. Cambridge University Press, Cambridge, 1990), were used to determine the mechanical properties of the rock during the Uniaxial Compressive Strength (UCS) tests. For the triaxial test, only Wood’s (1990) method was applied due to the existence of confining pressure. Microstructural analysis on thin sections of the sandstones under plane and crossed polarised light conditions in the deformed and undeformed state was conducted to elucidate deformation mechanisms and aid interpretation of experimental results. It was identified that both an increase in confinement and a reduction in temperature, increased the strength of the sandstone and reduced the Poisson’s ratio. Additionally, by decreasing the temperature, especially in the UCS test the material dilated less. This is an important outcome as expanding the results to a wellbore stability problem, brittle behaviour may be more apparent and damage may occur when sub-zero injection temperatures are applied, especially at the wellbore head, where confinement is low.

Axo-glial interactions between midbrain dopamine neurons and oligodendrocyte lineage cells in the anterior corpus callosum - Megan Caldwell; Vanessa Ayo-Jibunoh; Josue Criollo Mendoza; Katherine R. Brimblecombe; Lauren M. Reynolds; Xin Yan Zhu Jiang; Colin Alarcon; Elizabeth Fiore; Jacquelyn N. Tomaio; Greg R. Phillips; Susana Mingote; Cecilia Flores; et al. (Brain Structure and Function, 2023)
Oligodendrocyte progenitor cells (OPCs) receive synaptic innervation from glutamatergic and GABAergic axons and can be dynamically regulated by neural activity, resulting in activity-dependent changes in patterns of axon myelination. However, it remains unclear to what extent other types of neurons may innervate OPCs. Here, we provide evidence implicating midbrain dopamine neurons in the innervation of oligodendrocyte lineage cells in the anterior corpus callosum and nearby white matter tracts of male and female adult mice. Dopaminergic axon terminals were identified in the corpus callosum of DAT-Cre mice after injection of an eYFP reporter virus into the midbrain. Furthermore, fast-scan cyclic voltammetry revealed monoaminergic transients in the anterior corpus callosum, consistent with the anatomical findings. Using RNAscope, we further demonstrate that ~ 40% of Olig2 + /Pdfgra + cells and ~ 20% of Olig2 + /Pdgfra- cells in the anterior corpus callosum express Drd1 and Drd2 transcripts. These results suggest that oligodendrocyte lineage cells may respond to dopamine released from midbrain dopamine axons, which could affect myelination. Together, this work broadens our understanding of neuron-glia interactions with important implications for myelin plasticity by identifying midbrain dopamine axons as a potential regulator of corpus callosal oligodendrocyte lineage cells.

Bridging mouse and human anatomies; a knowledge-based approach to comparative anatomy for disease model phenotyping - Jesús Ruberte; Paul N. Schofield; John P. Sundberg; Alfonso Rodriguez-Baeza; Ana Carretero; Colin McKerlie (Mammalian Genome, 2023)
The laboratory mouse is the foremost mammalian model used for studying human diseases and is closely anatomically related to humans. Whilst knowledge about human anatomy has been collected throughout the history of mankind, the first comprehensive study of the mouse anatomy was published less than 60 years ago. This has been followed by the more recent publication of several books and resources on mouse anatomy. Nevertheless, to date, our understanding and knowledge of mouse anatomy is far from being at the same level as that of humans. In addition, the alignment between current mouse and human anatomy nomenclatures is far from being as developed as those existing between other species, such as domestic animals and humans. To close this gap, more in depth mouse anatomical research is needed and it will be necessary to extent and refine the current vocabulary of mouse anatomical terms.

The development of a solid lipid nanoparticle (SLN)-based lacticin 3147 hydrogel for the treatment of wound infections - Aoibhín Ryan; Pratikkumar Patel; Poonam Ratrey; Paula M. O’Connor; Julie O’Sullivan; R. Paul Ross; Colin Hill; Sarah P. Hudson (Drug Delivery and Translational Research, 2023)
Chronic wounds affect millions of people globally. This number is set to rise with the increasing incidence of antimicrobial-resistant bacterial infections, such as methicillin-resistant Staphylococcus aureus (MRSA), which impair the healing of chronic wounds. Lacticin 3147 is a two-peptide chain bacteriocin produced by Lactococcus lactis that is active against S. aureus including MRSA strains. Previously, poor physicochemical properties of the peptides were overcome by the encapsulation of lacticin 3147 into solid lipid nanoparticles. Here, a lacticin 3147 solid lipid nanoparticle gel is proposed as a topical treatment for S. aureus and MRSA wound infections. Initially, lacticin 3147’s antimicrobial activity against S. aureus was determined before encapsulation into solid lipid nanoparticles. An optimised gel formulation with the desired physicochemical properties for topical application was developed, and the lacticin-loaded solid lipid nanoparticles and free lacticin 3147 aqueous solution were incorporated into separate gels. The release of lacticin 3147 from both the solid lipid nanoparticle and free lacticin gels was measured where the solid lipid nanoparticle gel exhibited increased activity for a longer period (11 days) compared to the free lacticin gel (9 days). Both gels displayed potent activity ex vivo against S. aureus- infected pig skin with significant bacterial eradication (> 75%) after 1 h. Thus, a long-acting potent lacticin 3147 solid lipid nanoparticle gel with the required physicochemical properties for topical delivery of lacticin 3147 to the skin for the potential treatment of S. aureus -infected chronic wounds was developed. Graphical abstract

Quantification of wetland vegetation communities features with airborne AVIRIS-NG, UAVSAR, and UAV LiDAR data in Peace-Athabasca Delta - Chao Wang; Tamlin M. Pavelsky; Ethan D. Kyzivat; Fenix Garcia-Tigreros; Erika Podest; Fangfang Yao; Xiao Yang; Shuai Zhang; Conghe Song; Theodore Langhorst; Wayana Dolan; Martin R. Kurek; et al. (Remote Sensing of Environment, 2023)

Evaluating the sustainability of the 2017 US biofuel industry with an integrated techno-economic analysis and life cycle assessment - Jack P. Smith; Braden J. Limb; Colin M. Beal; Kelly R. Banta; John L. Field; Steven J. Simske; Jason C. Quinn (Journal of Cleaner Production, 2023)

Population structure of Pacific green turtles: a new perspective from microsatellite DNA variation - Suzanne E. Roden; John B. Horne; Michael P. Jensen; Nancy N. FitzSimmons; George H. Balazs; Richard Farman; Jennifer Cruce Horeg; Jessy Hapdei; Maike Heidemeyer; T. Todd Jones; Lisa M. Komoroske; Colin J. Limpus; et al. (Frontiers in Marine Science, 2023)
This study builds upon the current understanding of green turtle population genetic structure in the Pacific that has largely been based on mitochondrial DNA (mtDNA), by examining nuclear DNA (nDNA) diversity, regional connectivity, and male-mediated gene flow. A total of 1,111 nesting green turtle samples were analyzed with 10 microsatellite markers from 20 Pacific rookeries. Population differentiation (F ST ) was significant (p <0.05) in all but 8 of 190 pairwise rookery comparisons. Pairwise F ST values and discriminant analysis of principal components (DAPC) revealed a defined East-West split consistent with mtDNA studies. Additionally, isolation-by-distance was evaluated with estimated effective migration surfaces (EEMS). The data indicated structure throughout the Pacific rookeries largely in agreement with stock structure defined by mtDNA studies, except for some areas on the Central American and Australian continental shelves, providing evidence of possible male-mediated gene flow. The series of analyses performed did indicate that male-mediated gene flow has likely occurred where breeding migration corridors of separate populations overlap with courtship areas. This may occur primarily along the margins of continents, including along Mexico and Central America in the East Pacific. Our study provides an ocean-wide baseline nDNA dataset for green turtle rookeries in the Pacific and reexamines the current thinking regarding the role of male turtles in the population dynamics of management units (MU) and to what extent nuclear gene flow occurs among designated MUs.

SoJel –A 3D printed jellyfish-like robot using soft materials for underwater applications - Pawandeep Singh Matharu; Zhong Wang; John H. Costello; Sean P. Colin; Ray H. Baughman; Yonas T. Tadesse (Ocean Engineering, 2023)

Contrasting intra-individual variation in size-based trophic and habitat shifts for two coastal Arctic fish species - Harri Pettitt-Wade; Nigel E. Hussey; Colin P. Gallagher; Ellen V. Lea; Danielle L. Orrell; Lisa L. Loseto (Oecologia, 2023)
Within and among species variation in trophic and habitat shifts with body size can indicate the potential adaptive capacity of species to ecosystem change. In Arctic coastal ecosystems, which experience dramatic seasonal shifts and are undergoing rapid change, quantifying the trophic flexibility of coastal fishes with different migratory tactics has received limited attention. We examined the relationships among body length and condition (Fulton’s K, phase angle from Bioelectrical Impedance Analysis) with trophic and habitat shifts (differences in δ 15 N and δ 13 C between blood tissues with different turnover rates) of two abundant and culturally important species, anadromous Arctic char ( Salvelinus alpinus , n = 38) and sedentary Greenland cod ( Gadus ogac , n = 65) during summer in coastal marine waters near Ulukhaktok, Northwest Territories, Canada. Habitat shifts (δ 13 C) increased with length (i.e., pelagic to benthic-littoral) and crossed-equilibrium (zero) at mid-sizes for both species. Seasonal trophic shifts (δ 15 N) were generally positive (i.e., increasing trophic level) for Arctic char and negative for Greenland cod. As hypothesised, intra-individual variation in size-based trophic shifts (δ 15 N-length residuals) increased with length for Arctic char. However, there were no trends with length in Greenland cod. Our findings highlight the importance of flexibility through ontogeny and mobility for Arctic char, whereas Greenland cod were generalist to localized prey and habitat across all sizes. The significant effect of body condition (phase angle) on size-based trophic shifts in Arctic char, and size-based habitat shifts in Greenland cod, highlight the potential trade-offs of contrasting life history strategies and capacity for ontogenetic niche plasticity.

Salinity and temperature affect the symbiont profile and host condition of Florida USA blue crabs Callinectes sapidus - Erin A. Walters; Jamie Bojko; Claire E. Crowley; Ryan L. Gandy; Charles W. Martin; Colin P. Shea; Kelly S. Bateman; Grant D. Stentiford; Donald C. Behringer (Journal of Invertebrate Pathology, 2023)

Reef growth and carbonate sedimentation at the southernmost Pacific reefs - Colin D. Woodroffe; Michelle Linklater; Brendan P. Brooke; Scott L. Nichol; Quan Hua; David M. Kennedy (Marine Geology, 2023)

The Anthropocene as an epoch is distinct from all other concepts known by this term: a reply to Swindles et al. (2023) - Martin J. Head; Colin N. Waters; Jan A. Zalasiewicz; Anthony D. Barnosky; Simon D. Turner; Alejandro Cearreta; Reinhold Leinfelder; Francine M.G. McCarthy; Daniel de B. Richter; Neil L. Rose; Yoshiki Saito; Davor Vidas; et al. (Journal of Quaternary Science, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Exploring the potential effect of phospholipase A2 antibody to extend beef shelf-life in a beef liposome model system - Colin K.Y. Chun; Mary Roth; Ruth Welti; Mark P. Richards; Wei-Wen Hsu; Travis O'Quinn; Michael D. Chao (Meat Science, 2023)

Photosensitiser-incorporated microparticles for photodynamic inactivation of bacteria - Jessica V. Moore; Matthew P. Wylie; Gavin P. Andrews; Colin P. McCoy (Journal of Photochemistry and Photobiology B: Biology, 2023)

A century of mercury: Ecosystem-wide changes drive increasing contamination of a tropical seabird species in the South Atlantic Ocean - Fanny Cusset; S. James Reynolds; Alice Carravieri; David Amouroux; Océane Asensio; Roger C. Dickey; Jérôme Fort; B. John Hughes; Vitor H. Paiva; Jaime A. Ramos; Laura Shearer; Emmanuel Tessier; et al. (Environmental Pollution, 2023)

Response to Merritts et al. (2023): The Anthropocene is complex. Defining it is not - Colin N. Waters; Martin J. Head; Jan Zalasiewicz; Francine M.G. McCarthy; Scott L. Wing; Peter K. Haff; Mark Williams; Anthony D. Barnosky; Barbara Fiałkiewicz-Kozieł; Reinhold Leinfelder; J.R. McNeill; Neil L. Rose; et al. (Earth-Science Reviews, 2023)

Trophodynamics of Nekton Assemblages and Relationships with Estuarine Habitat Structure Across a Subtropical Estuary - Shannon D. Whaley; Colin P. Shea; James J. Burd; Craig W. Harmak (Estuaries and Coasts, 2023)
Understanding the spatiotemporal dynamics of trophic structures, or trophodynamics, is important for assessing the overall condition and function of estuarine ecosystems. We examined spatial and seasonal trophodynamics of nekton assemblages across the seascape of a subtropical estuary (Charlotte Harbor, FL, USA) using historical nekton data from an ongoing monitoring program. We also examined relationships between trophodynamics and the spatial distribution of vegetated habitats, such as salt marshes, mangroves, and seagrass beds, as well as their absence along hardened shorelines (seawalls or riprap) using seascape metrics (area and edge density of habitats within several search radii of sample locations). We found that nekton assemblages in shallow waters (from the shoreline to a depth of ≤ 1.5 m) transitioned from mainly planktivores in the lower Peace and Myakka Rivers to mainly benthivores (those feeding on benthic infauna, epifauna, or seagrass) in the middle and lower portions of Charlotte Harbor. Overall nekton assemblages throughout the estuary appeared to be largely sustained through benthic pathways in areas with abundant seagrass and nearby mangrove habitat, particularly during the cool-dry winter when planktivore densities were seasonally low. The dramatic seasonal decline in planktivore densities we found in the lower rivers may be related to low freshwater inflow and increased predation resulting from seasonal recruitment pulses of several omnivorous species. Trophodynamics linked with seascape metrics of estuarine habitat structure described here may be used as a spatially explicit baseline of the estuarine seascape to monitor ecosystem health as well as parameterize spatial ecosystem models used in fisheries management in Charlotte Harbor and similar subtropical estuaries.

Optimality-based modelling of wheat sowing dates globally - Shengchao Qiao; Sandy P. Harrison; I. Colin Prentice; Han Wang (Agricultural Systems, 2023)

Phenological assessment of transpiration: The stem-temp approach for determining start and end of season - Magali F. Nehemy; Zoe Pierrat; Jason Maillet; Andrew D. Richardson; Jochen Stutz; Bruce Johnson; Warren Helgason; Alan G. Barr; Colin P. Laroque; Jeffrey J. McDonnell (Agricultural and Forest Meteorology, 2023)

Comparison of tree-growth drought legacies of three shelterbelt species in the Canadian Prairies - Chloe M Canning; Bryan J Mood; Barrie Bonsal; Brooke Howat; Colin P Laroque (Agricultural and Forest Meteorology, 2023)

Testing whether reducing brown trout biomass in peatland lakes increases macro-invertebrate biomass and invertivorous waterbird occurrence - Mark H. Hancock; Daniela Klein; Robert Hughes; Paul Stagg; Paul Byrne; Trevor D. Smith; Alison MacLennan; Paul P. J. Gaffney; Colin W. Bean (Aquatic Ecology, 2023)

Migratory birds with delayed spring departure migrate faster but pay the costs - Bryant C. Dossman; Amanda D. Rodewald; Colin E. Studds; Peter P. Marra (Ecology, 2023)
Migratory birds that experience poor overwintering conditions are often late to arrive at the breeding grounds, which is known to depress individual fitness. Despite the importance of this carryover effect, few studies have investigated how individuals can modify migratory behaviors en route to reduce delays on arrival and whether accelerating migration incurs survival costs. To examine this, we used Motus Wildlife Tracking System to track individual American redstarts ( Setophaga ruticilla ) as they migrated from wintering grounds in Southwest Jamaica through Florida en route to their breeding areas. We leveraged long‐term data on spring departure timing and breeding latitude to quantify the relative departure dates (early vs. delayed) of tagged individuals, which we then related to individual migration rates and apparent annual survival. Compared to those initiating migration earlier, individuals that departed relatively late (10‐day delay) migrated at a 43% faster rate, which decreased their annual survival by 6.3%. Our results are consistent with the hypothesis that spring migrants use speed to compensate for departure delays despite incurring survival costs. This compensatory behavior may potentially underly differential survival during spring migration and may be particularly widespread across short‐lived migratory birds generally considered time‐constrained.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Quantifying and mapping species threat abatement opportunities to support national target setting - Louise Mair; Eduardo Amorim; Monira Bicalho; Thomas M. Brooks; Vincente Calfo; Renata de T. Capellão; Colin Clubbe; Marianne Evju; Eduardo P. Fernandez; Gláucia C. Ferreira; Frank Hawkins; Randall R. Jiménez; et al. (Conservation Biology, 2023)
The successful implementation of the Convention on Biological Diversity's post‐2020 Global Biodiversity Framework will rely on effective translation of targets from global to national level and increased engagement across diverse sectors of society. Species conservation targets require policy support measures that can be applied to a diversity of taxonomic groups, that link action targets to outcome goals, and that can be applied to both global and national data sets to account for national context, which the species threat abatement and restoration (STAR) metric does. To test the flexibility of STAR, we applied the metric to vascular plants listed on national red lists of Brazil, Norway, and South Africa. The STAR metric uses data on species’ extinction risk, distributions, and threats, which we obtained from national red lists to quantify the contribution that threat abatement and habitat restoration activities could make to reducing species’ extinction risk. Across all 3 countries, the greatest opportunity for reducing plant species’ extinction risk was from abating threats from agricultural activities, which could reduce species’ extinction risk by 54% in Norway, 36% in South Africa, and 29% in Brazil. Species extinction risk could be reduced by a further 21% in South Africa by abating threats from invasive species and by 21% in Brazil by abating threats from urban expansion. Even with different approaches to red‐listing among countries, the STAR metric yielded informative results that identified where the greatest conservation gains could be made for species through threat‐abatement and restoration activities. Quantifiably linking local taxonomic coverage and data collection to global processes with STAR would allow national target setting to align with global targets and enable state and nonstate actors to measure and report on their potential contributions to species conservation.

Analytical performances of the LAb-CosmOrbitrap mass spectrometer for astrobiology - L. Selliez; C. Briois; N. Carrasco; L. Thirkell; B. Gaubicher; J.-P. Lebreton; F. Colin (Planetary and Space Science, 2023)

Non-targeted proteomics reveals altered immune response in geographically distinct populations of green sea turtles (Chelonia mydas) - Stephanie Chaousis; Frederic DL. Leusch; Colin J. Limpus; Amanda Nouwens; Liesbeth J. Weijs; Antonia Weltmeyer; Adrian Covaci; Jason P. van de Merwe (Environmental Research, 2023)

Identifying priority locations to protect a wide-ranging endangered species - Natasha M. Peters; Corinne J. Kendall; Jacob G. Davies; Claire Bracebridge; Aaron Nicholas; Msafiri P. Mgumba; Colin M. Beale (Biological Conservation, 2023)

Optimality principles explaining divergent responses of alpine vegetation to environmental change - Ziqi Zhu; Han Wang; Sandy P. Harrison; Iain Colin Prentice; Shengchao Qiao; Shen Tan (Global Change Biology, 2023)
Recent increases in vegetation greenness over much of the world reflect increasing CO 2 globally and warming in cold areas. However, the strength of the response to both CO 2 and warming in those areas appears to be declining for unclear reasons, contributing to large uncertainties in predicting how vegetation will respond to future global changes. Here, we investigated the changes of satellite‐observed peak season absorbed photosynthetically active radiation ( F max ) on the Tibetan Plateau between 1982 and 2016. Although climate trends are similar across the Plateau, we identified robust divergent responses (a greening of 0.31 ± 0.14% year −1 in drier regions and a browning of 0.12 ± 0.08% year −1 in wetter regions). Using an eco‐evolutionary optimality (EEO) concept of plant acclimation/adaptation, we propose a parsimonious modelling framework that quantitatively explains these changes in terms of water and energy limitations. Our model captured the variations in F max with a correlation coefficient ( r ) of .76 and a root mean squared error of .12 and predicted the divergent trends of greening (0.32 ± 0.19% year −1 ) and browning (0.07 ± 0.06% year −1 ). We also predicted the observed reduced sensitivities of F max to precipitation and temperature. The model allows us to explain these changes: Enhanced growing season cumulative radiation has opposite effects on water use and energy uptake. Increased precipitation has an overwhelmingly positive effect in drier regions, whereas warming reduces F max in wetter regions by increasing the cost of building and maintaining leaf area. Rising CO 2 stimulates vegetation growth by enhancing water‐use efficiency, but its effect on photosynthesis saturates. The large decrease in the sensitivity of vegetation to climate reflects a shift from water to energy limitation. Our study demonstrates the potential of EEO approaches to reveal the mechanisms underlying recent trends in vegetation greenness and provides further insight into the response of alpine ecosystems to ongoing climate change.

G﻿lobal phylogeography of ridley sea turtles (Lepidochelys spp.): evolution, demography, connectivity, and conservation - Sibelle Torres Vilaça; Anelise Torres Hahn; Eugenia Naro-Maciel; F. Alberto Abreu-Grobois; Brian W. Bowen; Jaqueline C. Castilhos; Claudio Ciofi; Nancy N. FitzSimmons; Michael P. Jensen; Angela Formia; Colin J. Limpus; Chiara Natali; et al. (Conservation Genetics, 2022)
Globally distributed marine taxa are well suited for investigations of biogeographic impacts on genetic diversity, connectivity, and population demography. The sea turtle genus Lepidochelys includes the wide-ranging and abundant olive ridley ( L. olivacea ), and the geographically restricted and ‘Critically Endangered’ Kemp’s ridley ( L. kempii ). To investigate their historical biogeography, we analyzed a large dataset of mitochondrial DNA (mtDNA) sequences from olive (n = 943) and Kemp’s (n = 287) ridleys, and genotyped 15 nuclear microsatellite loci in a global sample of olive ridleys (n = 285). We found that the ridley species split ~ 7.5 million years ago, before the Panama Isthmus closure. The most ancient mitochondrial olive ridley lineage, located in the Indian Ocean, was dated to ~ 2.2 Mya. Both mitochondrial and nuclear markers revealed significant structure for olive ridleys between Atlantic (ATL), East Pacific (EP), and Indo-West Pacific (IWP) areas. However, the divergence of mtDNA clades was very recent (< 1 Mya) with low within- clade diversity, supporting a recurrent extinction-recolonization model for these ocean regions. All data showed that ATL and IWP groups were more closely related than those in the EP, with mtDNA data supporting recent recolonization of the ATL from the IWP. Individual olive ridley dispersal between the ATL, EP, and IN/IWP could be interpreted as more male- than female-biased, and genetic diversity was lowest in the Atlantic Ocean. All populations showed signs of recent expansion, and estimated time frames were concordant with their recent colonization history. Investigating species abundance and distribution changes over time is central to evolutionary biology, and this study provides a historical biogeographic context for marine vertebrate conservation and management.

Oceanic lobate ctenophores possess feeding mechanics similar to the impactful coastal species Mnemiopsis leidyi - Malaika Cordeiro; John H. Costello; Brad J. Gemmell; Kelly R. Sutherland; Sean P. Colin (Limnology and Oceanography, 2022)
Lobate ctenophores are often numerically dominant members of oceanic epipelagic and midwater ecosystems. Despite this, little is known about their trophic ecology. Multiple, co‐occurring species are often found in these ecosystems and appear to feed similarly via feeding currents that entrain prey. We quantified the hydrodynamics, morphology, and behavior of four co‐occurring, cosmopolitan lobate species ( Eurhamphaea vexilligera , Ocyropsis crystallina , Bolinopsis vitrea , and Leucothea multicornis ) to evaluate whether their feeding mechanics lead to differential feeding rates and prey selection. We compared the feeding characteristics of these four oceanic species to the coastal lobate ctenophore, Mnemiopsis leidyi , which is known as a voracious zooplanktivore. We found that despite their morphological diversity, the five lobate species used the same mechanism to generate their feeding current—the hydrodynamics of their feeding currents were similarly laminar and with very low fluid deformation rates. Despite having similar feeding current traits, the species had different in situ swimming behaviors and feeding postures. We show that these different behaviors and postures lead to different prey encounter rates and that several of the oceanic species have the potential to feed at rates similar to or greater than M. leidyi . As such, the individual and combined trophic impact of oceanic lobate ctenophores is likely to be much greater than previously predicted.

Substrate size modifies stream grazer–biofilm interactions in the presence of invertivorous fish - Ricardo J. Albariño; Gerard P. Closs; Christoph D. Matthaei; Colin R. Townsend; Daniel Zamorano (Ecology, 2022)
When herbivore abundance is controlled by predators there may be an indirect positive effect on primary producers due to reduced grazing pressure, but the potential of predation refuges to modify such trophic cascades has rarely been studied. By experimentally manipulating substrate particle size and fish predation regime, we assessed the outcome of invertebrate grazer–biofilm interactions in streams. Locations at the center of larger substrate particles were predicted to pose a higher predation risk, and therefore be subjected to a lower grazing pressure. In our 52‐day experiment in a New Zealand stream, small‐sized substrates (terracotta tiles) remained virtually free of periphyton across their entire upper surface, whereas a thick periphyton mat was formed across large tiles with only edges remaining free. In channels containing fish (either native Galaxias vulgaris or exotic Salmo trutta ), grazing on tiles was lower than in the absence of fish. A preference for grazing near to the edge of tiles was clearest in fish channels but was also evident even in the absence of fish, probably reflecting fish presence and/or fish kairomones in the stream from where the colonizing invertebrates had been derived. Total grazer density was similar across treatments with or without fish, suggesting that our results can be explained mostly by changes in the behavior of grazers. We suggest that refuge availability, interacting with grazer predator‐avoidance behavior, may produce a context‐dependent patchwork of trophic cascades in streams and other ecosystems.

Combining models for animal tracking: Defining behavioural states to understand space use for conservation - Natasha M. Peters; Colin M. Beale; Claire Bracebridge; Msafiri P. Mgumba; Corinne J. Kendall (Journal of Biogeography, 2022)
Aim Rapid advances in technology have created tools able to explore how animals differ in their use of the environment based on behaviour, which can provide insights into the ecology of endangered animals and the threats they face. Though threatened, we know little of vultures' spatial ecology. We examine the external variables that affect vultures' decisions regarding space use, specifically during foraging and feeding when they are at greatest risk for encountering threats, and use this to inform effective conservation interventions. Location Tanzania, specifically Southern Tanzanian protected area networks. Taxon Gyps africanus. Methods We tracked 26 African white‐backed vultures between 2015 and 2019 in Southern Tanzania. Using hidden Markov models to identify behaviour from raw GPS points and point process models to spatially analyse these behaviours, we tested resource selection decisions in vultures during foraging and feeding, when they are at greatest risk of poisoning. Results African white‐backed vultures are most likely to forage early in the day outside National Parks, specifically in Game Reserves and Wildlife Management Areas, but avoid areas with high livestock numbers to feed. Eastern and Western populations showed slight differences in preferences, highlighting the need for population level considerations. When not selecting for behaviour, closeness to rivers and habitat openness were more important than protected area status for predicting vulture use. Main conclusions Through combining complex analyses, we identified results which simple statistical analyses could not offer. Hidden Markov models and point process models are complementary and can be used to define specific behaviours and associated resource selection. These results provide insight into how animals use their habitat explicitly rather than describing where they spend most of their time. This adds to the growing evidence that although National Parks are important, the management of surrounding areas must be included in conservation efforts.

The Critically Endangered Hainan Gibbon (Nomascus hainanus) Population Increases but not at the Maximum Possible Rate - Guioqi Liu; Xueli Lu; Zhao Liu; Zhi Xie; Xuming Qi; Jiang Zhou; Xiaojiang Hong; Yanni Mo; Bosco P. L. Chan; Colin A. Chapman; Zhigang Jiang (International Journal of Primatology, 2022)
With the ongoing global biodiversity crisis in the Anthropocene, it is critical to understand how to save endangered species to “bend the curve” of biodiversity decline. The Hainan gibbon ( Nomascus hainanus ) is a Critically Endangered species that is endemic to Hainan Island. We performed two synchronized total count surveys in Hainan Tropic Rain Forest National Park in November and December of 2020 and 2021 by locating gibbon groups from their morning calls and conducting detailed counts in all potential habitat fragments. We compared our findings with existing data to model the population trend, and analyzed the potential and realized reproductive potentials. We found 5 groups with a total of 33 gibbons in 2020 and 35 in 2021, including 4 and 6 solitary individuals respectively. This is an increase of 169% since 2003, when there were 13 individuals with 2 groups and 2 solitary individuals. Logistic and linear curves fitted the 2003-2021 population census data equally well. Although the population is growing, it has not realized its full reproductive potential (when all adult females give births at 24-month intervals), suggesting that external factors like available habitat, as well as nutritional, physiological, and behavioral factors may be limiting the population. The gibbon’s recovery demonstrates that establishing a nature reserve with regular patrols, banning logging, curbing poaching, and environmental education have been effective. Because the Hainan gibbon population is still extremely small, carefully planned conservation actions, including an ambitious forest restoration program, will be needed to ensure the species’ continued survival.

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

An integrated approach to assessing abiotic and biotic threats to post‐fire plant species recovery: Lessons from the 2019–2020 Australian fire season - Rachael V. Gallagher; Stuart P. Allen; Berin D. E. Mackenzie; David A. Keith; Rachael H. Nolan; Libby Rumpff; Carl R. Gosper; Geoffrey Pegg; Stephen van Leeuwen; Mark K. J. Ooi; Colin J. Yates; Cory Merow; et al. (Global Ecology and Biogeography, 2022)
Aim Existing abiotic and biotic threats to plant species (e.g., disease, drought, invasive species) affect their capacity to recover post‐fire. We use a new, globally applicable framework to assess the vulnerability of 26,062 Australian plant species to a suite of active threats after the 2019–2020 fires. Location Australia. Time period 2019–2020. Major species studied Plants. Methods Spatial data for existing threats and information on species‐level susceptibility were combined with estimates of the extent of range burnt in southern Australia (> 22°S) to assign species against 10 criteria into vulnerability categories ( high , medium , low , none , data deficient ). We explore in detail results for three threats (drought, disease, feral animals), highlighting where impacts from multiple threats ranked high vulnerability may compound to reduce post‐fire recovery. Results Analysis of the full suite of 10 vulnerability criteria, which encompass a broad range of threats, revealed large numbers of species vulnerable to poor post‐fire recovery from one or more different hazards ( high vulnerability: 1,243 species; medium vulnerability: 2,450 species). Collectively, 457 plant species that burnt extensively (> 50%) across their range are highly vulnerable to poor recovery due to exposure to pre‐fire drought conditions (235 species), disease (186 species), or feral animals (97 species). Of these 457 species, 61 are vulnerable to more than one of these three threats, highlighting how a suite of interacting hazards can impact plant recovery after fire. Main conclusions While fire can renew plant populations by stimulating recruitment and resetting competitive interactions, the presence of existing threats in post‐fire landscapes jeopardizes recovery. The simultaneous impact of multiple threats that impact recovery can create a suite of hazards that contribute to declines and, potentially, extinction. Our method for rapid post‐fire vulnerability assessment can be applied to large numbers of plant species or other biota in fire affected regions globally.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

A 2019 Outbreak Investigation of Hepatitis A Virus Infections in the United States Linked to Imported Fresh Blackberries - Monica McClure; Johnson Nsubuga; Martha P. Montgomery; Erin Jenkins; Alvin Crosby; Daniela Schoelen; Colin Basler; Sumathi Ramachandran; Yulin Lin; Guo-liang Xia; Yury Khudaykov; Vilasini Suktankar; et al. (Food and Environmental Virology, 2022)

Restoring vertebrate predator populations can provide landscape‐scale biological control of established invasive vertebrates: Insights from pine marten recovery in Europe - Joshua P. Twining; Colin Lawton; Andy White; Emma Sheehy; Keziah Hobson; W. Ian Montgomery; Xavier Lambin (Global Change Biology, 2022)
Invasive species pose one of the greatest global threats to biodiversity. There has been a long history of importing coevolved natural enemies to act as biological control agents to try to suppress densities of invasive species, with historically limited success and frequent adverse impacts on native biodiversity. Our understanding of the processes and drivers of successful biological control has been focussed on invertebrates and is evidently limited and potentially ill‐suited with respect to biological control of vertebrate populations. The restoration of native vertebrate predator populations provides a promising nature‐based solution for slowing, halting, or even reversing the spread of some invasive vertebrates over spatial scales relevant to the management of wildlife populations. Here, we first review the growing literature and data from the pine marten‐red and grey squirrel system in Europe. We synthesise a multi‐decadal dataset to show that the recovery of a native predator has resulted in rapid, landscape‐scale declines of an established invasive species. We then use the model system, predator–prey interaction theory, and examples from the literature to develop ecological theory relating to natural biological control in vertebrates and evolutionary processes in native‐invasive predator–prey interactions. We find support for the hypotheses that evolutionary naivety of invasive species to native predators and lack of local refuges results in higher predation of naive compared to coevolved prey. We apply lessons learnt from the marten‐squirrel model system to examine the plausibility of specific native predator solutions to some of the Earth's most devastating invasive vertebrates. Given the evidence, we conclude that depletion of vertebrate predator populations has increased ecosystem vulnerability to invasions and thus facilitated the spread of invasive species. Therefore, restoration of vertebrate predator populations is an underappreciated, fundamental, nature‐based solution to the crisis of invasive species and should be a priority for vertebrate invasive species management globally.

Assessing the Synergistic Effects of Land Use and Climate Change on Terrestrial Biodiversity: Are Generalists Always the Winners? - Colin P. Sweeney; Marta A. Jarzyna (Current Landscape Ecology Reports, 2022)

A Resist‐Accept‐Direct decision‐support tool for walleye Sander vitreus (Mitchill) management in Wisconsin - Colin J. Dassow; Alex W. Latzka; Abigail J. Lynch; Greg G. Sass; Ralph W. Tingley; Craig P. Paukert (Fisheries Management and Ecology, 2022)
Large‐scale modelling and prediction provide insight into general influences of climate change on inland recreational fisheries; however, small‐scale dynamics and local expertise will be key in developing explicit goals for managing recreational fisheries as the climate changes. The resist‐accept‐direct (RAD) framework encompasses the entire decision space managers consider when addressing climate influences in their local system, but to decide whether to resist, accept or direct, managers need tools to understand how specific waterbodies will be influenced by climate change. Here, a decision‐support tool was developed and applied to the walleye recreational fishery in Wisconsin, USA as an example of how to link the RAD framework to real‐world management of a large recreational fishery. The tool and broadscale results described here, indicating a widespread shift away from resist strategies by mid‐century, can be used by managers to inform decisions about whether to resist, accept, or direct for specific walleye populations.

Mapping risk to plant populations from short fire intervals via relationships between maturation period and environmental productivity - Carl R. Gosper; Ben P. Miller; Rachael V. Gallagher; Janine Kinloch; Richard van Dongen; Emma Adams; Sarah Barrett; Anne Cochrane; Sarah Comer; Lachlan McCaw; Russell G. Miller; Suzanne M. Prober; et al. (Plant Ecology, 2022)

Stage-dependent niche segregation: insights from a multi-dimensional approach of two sympatric sibling seabirds - Aymeric Fromant; John P. Y. Arnould; Karine Delord; Grace J. Sutton; Alice Carravieri; Paco Bustamante; Colin M. Miskelly; Akiko Kato; Maud Brault-Favrou; Yves Cherel; Charles-André Bost (Oecologia, 2022)
Niche theory predicts that to reduce competition for the same resource, sympatric ecologically similar species should exploit divergent niches and segregate in one or more dimensions. Seasonal variations in environmental conditions and energy requirements can influence the mechanisms and the degree of niche segregation. However, studies have overlooked the multi-dimensional aspect of niche segregation over the whole annual cycle, and key facets of species co-existence still remain ambiguous. The present study provides insights into the niche use and partitioning of two morphologically and ecologically similar seabirds, the common (CDP, Pelecanoides urinatrix ) and the South Georgian diving petrel (SGDP, Pelecanoides georgicus ). Using phenology, at-sea distribution, diving behavior and isotopic data (during the incubation, chick-rearing and non-breeding periods), we show that the degree of partitioning was highly stage-dependent. During the breeding season, the greater niche segregation during chick-rearing than incubation supported the hypothesis that resource partitioning increases during energetically demanding periods. During the post breeding period, while species-specific latitudinal differences were expected (species specific water mass preference), CDP and SGDP also migrated in divergent directions. This segregation in migration area may not be only a response to the selective pressure arising from competition avoidance between sympatric species, but instead, could reflect past evolutionary divergence. Such stage-dependent and context-dependent niche segregation demonstrates the importance of integrative approaches combining techniques from different fields, throughout the entire annual cycle, to better understand the co-existence of ecologically similar species. This is particularly relevant in order to fully understand the short and long-term effects of ongoing environmental changes on species distributions and communities. This work demonstrates the need of integrative multi-dimensional approaches combining concepts and techniques from different fields to understand the mechanism and causal factors of niche segregation.

Cortico-amygdalar connectivity and externalizing/internalizing behavior in children with neurodevelopmental disorders - Hajer Nakua; Colin Hawco; Natalie J. Forde; Grace R. Jacobs; Michael Joseph; Aristotle N. Voineskos; Anne L. Wheeler; Meng-Chuan Lai; Peter Szatmari; Elizabeth Kelley; Xudong Liu; Stelios Georgiades; et al. (Brain Structure and Function, 2022)
Background Externalizing and internalizing behaviors contribute to clinical impairment in children with neurodevelopmental disorders (NDDs). Although associations between externalizing or internalizing behaviors and cortico-amygdalar connectivity have been found in clinical and non-clinical pediatric samples, no previous study has examined whether similar shared associations are present across children with different NDDs. Methods Multi-modal neuroimaging and behavioral data from the Province of Ontario Neurodevelopmental Disorders (POND) Network were used. POND participants aged 6–18 years with a primary diagnosis of autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD) or obsessive–compulsive disorder (OCD), as well as typically developing children (TDC) with T1-weighted, resting-state fMRI or diffusion weighted imaging (DWI) and parent-report Child Behavioral Checklist (CBCL) data available, were analyzed (total n = 346). Associations between externalizing or internalizing behavior and cortico-amygdalar structural and functional connectivity indices were examined using linear regressions, controlling for age, gender, and image-modality specific covariates. Behavior-by-diagnosis interaction effects were also examined. Results No significant linear associations (or diagnosis-by-behavior interaction effects) were found between CBCL-measured externalizing or internalizing behaviors and any of the connectivity indices examined. Post-hoc bootstrapping analyses indicated stability and reliability of these null results. Conclusions The current study provides evidence towards an absence of a shared linear relationship between internalizing or externalizing behaviors and cortico-amygdalar connectivity properties across a transdiagnostic sample of children with different primary NDD diagnoses and TDC. Different methodological approaches, including incorporation of multi-dimensional behavioral data (e.g., task-based fMRI) or clustering approaches may be needed to clarify complex brain-behavior relationships relevant to externalizing/internalizing behaviors in heterogeneous clinical NDD populations.

A new method based on surface‐sample pollen data for reconstructing palaeovegetation patterns - Esmeralda Cruz‐Silva; Sandy P. Harrison; Elena Marinova; I. Colin Prentice (Journal of Biogeography, 2022)
Aim Biomisation has been the most widely used technique to reconstruct past regional vegetation patterns because it does not require an extensive modern pollen dataset. However, it has well‐known limitations including its dependence on expert judgement for the assignment of pollen taxa to plant functional types (PFTs) and PFTs to biomes. Here we present a new method that combines the strengths of biomisation with those of the alternative dissimilarity‐based techniques. Location The Eastern Mediterranean‐Black Sea Caspian Corridor (EMBSeCBIO). Taxon Plants Methods Modern pollen samples, assigned to biomes based on potential natural vegetation data, are used to characterize the within‐biome means and standard deviations of the abundances of each taxon. These values are used to calculate a dissimilarity index between any pollen sample and every biome, and thus assign the sample to the most likely biome. We calculate a threshold value for each modern biome; fossil samples with scores below the threshold for all modern biomes are thus identified as non‐analogue vegetation. We applied the new method to the EMBSeCBIO region to compare its performance with existing reconstructions. Results The method captured changes in the importance of individual taxa along environmental gradients. The balanced accuracy obtained for the EMBSeCBIO region using the new method was better than obtained using biomisation (77% vs. 65%). When the method was applied to high‐resolution fossil records, 70% of the entities showed more temporally stable biome assignments than obtained using biomisation. The technique also identified likely non‐analogue assemblages in a synthetic modern dataset and in fossil records. Main conclusions The new method yields more accurate and stable reconstructions of vegetation than biomisation. It requires an extensive modern pollen dataset, but is conceptually simple, and avoids subjective choices about taxon allocations to PFTs and PFTs to biomes.

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

An opinion piece: the evolutionary and ecological consequences of changing selection pressures on marine migration in Atlantic salmon - Colin E. Adams; Louise Chavarie; Jessica R. Rodger; Hannele M. Honkanen; Davide Thambithurai; Matthew P. Newton (Journal of Fish Biology, 2022)
There are strong signals that the selection forces favouring the expression of long‐distance sea migration by Atlantic salmon ( Salmo salar ) are changing. Unlike many other behavioural traits, the costs of migration are incurred before any fitness benefits become apparent to the migrant. The expression of this behaviour has thus been shaped by selection forces over multiple generations and cannot respond to short interval (within a single generation) environmental change as many other behavioural traits can. Here we provide a framework to examine the evolutionary and ecological consequences of a sustained increase in migration cost. We argue that Atlantic salmon may have entered an evolutionary trap , where long‐distance sea migration has become maladaptive because of shifting environmental conditions. We predict that if higher migration costs (affecting survivorship and ultimately fitness) persist, then shifting selection pressures will result in continuing declines in population size. We suggest, however, that in some populations there is demonstrable capacity for evolutionary rescue responses within the species which is to be found in the variation in the expression of migration. Under a scenario of low to moderate change in the selection forces that previously promoted migration, we argue that disruptive, sex‐based selection would result in partial migration, where females retain sea migration but with anadromy loss predominantly in males. With more acute selection forces, anadromy may be strongly selected against, under these conditions both sexes may become freshwater resident. We suggest that as the migration costs appear to be higher in catchments with standing waters, then this outcome is more likely in such systems. We also speculate that as a result of the genetic structuring in this species, not all populations may have the capacity to respond adequately to change. The consequences of this for the species and its management are discussed.

Multi-taxa spatial conservation planning reveals similar priorities between taxa and improved protected area representation with climate change - Rob Critchlow; Charles A. Cunningham; Humphrey Q. P. Crick; Nicholas A. Macgregor; Michael D. Morecroft; James W. Pearce-Higgins; Tom H. Oliver; Matthew J. Carroll; Colin M. Beale (Biodiversity and Conservation, 2022)
Protected area (PA) networks have in the past been constructed to include all major habitats, but have often been developed through consideration of only a few indicator taxa or across restricted areas, and rarely account for global climate change. Systematic conservation planning (SCP) aims to improve the efficiency of biodiversity conservation, particularly when addressing internationally agreed protection targets. We apply SCP in Great Britain (GB) using the widest taxonomic coverage to date (4,447 species), compare spatial prioritisation results across 18 taxa and use projected future (2080) distributions to assess the potential impact of climate change on PA network effectiveness. Priority conservation areas were similar among multiple taxa, despite considerable differences in spatial species richness patterns; thus systematic prioritisations based on indicator taxa for which data are widely available are still useful for conservation planning. We found that increasing the number of protected hectads by 2% (to reach the 2020 17% Aichi target) could have a disproportionate positive effect on species protected, with an increase of up to 17% for some taxa. The PA network in GB currently under-represents priority species but, if the potential future distributions under climate change are realised, the proportion of species distributions protected by the current PA network may increase, because many PAs are in northern and higher altitude areas. Optimal locations for new PAs are particularly concentrated in southern and upland areas of GB. This application of SCP shows how a small addition to an existing PA network could have disproportionate benefits for species conservation.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Year-Round Movements of Sooty Terns (Onychoprion fuscatus) Nesting Within One of the Atlantic’s Largest Marine Protected Areas - S. James Reynolds; Colin P. Wearn; B. John Hughes; Roger C. Dickey; Lucy J. H. Garrett; Sean Walls; Fay T. Hughes; Nicola Weber; Sam B. Weber; Eliza H. K. Leat; Kenickie Andrews; Jaime A. Ramos; et al. (Frontiers in Marine Science, 2021)
Seabirds are among the most threatened birds as a result of acute exposure to many anthropogenic threats. Their effective conservation requires a detailed understanding of how seabirds use marine habitats. Recently, one of the largest no-take marine reserves in the Atlantic was designated in tropical waters surrounding Ascension Island, on which the largest Atlantic population of sooty terns ( Onychoprion fuscatus ) breeds. Although they are the most abundant tropical seabird, they appear to have suffered marked population declines on Ascension Island as they have elsewhere. Here, we describe year-round movements and habitat use of male and female sooty terns between 2011 and 2015. On average, birds traveled 47,000 km during their 8 months of migration, during which they remained within 2,900 km of the island. They spent most of the day and night in flight, only touching down briefly on the ocean most likely to feed. Habitat suitability models successfully predicted foraging ranges of birds and their at-sea distributions varied considerably between seasons, years and sexes. Considerable variation in range overlap between birds and the new marine protected area (MPA) suggests that similar such studies of other marine taxa are urgently needed. The range of sooty terns mainly falls in the high seas outside of the new MPA, highlighting the very large areas that many oceanic seabirds forage across and the challenges their conservation present.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Age estimation comparison between whole and thin-sectioned otoliths and pelvic fin-ray sections of long-lived lake trout, Salvelinus namaycush, from Great Bear Lake, Northwest Territories, Canada - Colin P. Gallagher; Rick J. Wastle; Julie R. Marentette; Louise Chavarie; Kimberly L. Howland (Polar Biology, 2021)
Studies to determine precision and bias of both methods and age-readers are important to evaluate reliability of age data used for developing fisheries management objectives. We assessed within-reader, between-reader, and between-method precision (coefficient of variation, CV%) and bias of age estimations for long-lived lake trout, Salvelinus namaycush, from Great Bear Lake using three readers with different levels of experience. The assessment used independent age estimates ( n = 3 per reader) from whole and transverse-sectioned otoliths (range = 1–67 years), and pelvic fin-ray sections (range = 3–26 years). We also examined between-method differences in assigned confidence scores. Within readers, age estimates from sectioned otoliths were more precise (2.6–3.0%) than whole (3.6–4.5%) otoliths. Between whole and sectioned otoliths, precision of age estimates was 5.4% and bias was low up to age 20. Age was typically under-estimated from whole otoliths compared to sections for fish ≥ 34 years. Increased reader confidence was correlated with greater precision and younger age estimates, particularly for whole otoliths, but less so for fin rays. Age was estimated with higher confidence from otolith sections than other methods. The least experienced reader estimated age with the lowest precision, and between-reader bias was evident among older ages. Age was consistently under-estimated and less precise from pelvic fins compared to sectioned otoliths, and are therefore an unsuitable non-lethal alternative. Sectioned otoliths revealed longevity was greater (67 years) than historically documented using whole otoliths (53 years) for these fish. Our findings contribute to those relying on otoliths or pelvic fin rays to estimate ages of long-lived lake trout populations, which are a key component of freshwater fauna in polar North America.

Molecular Dynamics Simulations and Experimental Results Provide Insight into Clinical Performance Differences between Sandimmune® and Neoral® Lipid-Based Formulations - Dallas B. Warren; Shadabul Haque; Mitchell P. McInerney; Karen M. Corbett; Endri Kastrati; Leigh Ford; Hywel D. Williams; Vincent Jannin; Hassan Benameur; Christopher J.H. Porter; David K. Chalmers; Colin W. Pouton (Pharmaceutical Research, 2021)

The EU chemicals strategy for sustainability: in support of the BfR position - Frank A. Barile; Sir Colin Berry; Bas Blaauboer; Alan Boobis; Herrmann M. Bolt; Christopher Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Corrado L. Galli; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2021)
The EU chemicals strategy for sustainability (CSS) asserts that both human health and the environment are presently threatened and that further regulation is necessary. In a recent Guest Editorial, members of the German competent authority for risk assessment, the BfR, raised concerns about the scientific justification for this strategy. The complexity and interdependence of the networks of regulation of chemical substances have ensured that public health and wellbeing in the EU have continuously improved. A continuous process of improvement in consumer protection is clearly desirable but any initiative directed towards this objective must be based on scientific knowledge. It must not confound risk with other factors in determining policy. This conclusion is fully supported in the present Commentary including the request to improve both, data collection and the time-consuming and bureaucratic procedures that delay the publication of regulations.

Short- and Long-Term Effectiveness of Coral Disease Treatments - Karen L. Neely; Colin P. Shea; Kevin A. Macaulay; Emily K. Hower; Michelle A. Dobler (Frontiers in Marine Science, 2021)
Since 2014, stony coral tissue loss disease (SCTLD) has led to large-scale mortality of over 20 coral species throughout the Florida Reef Tract. In 2019, in-water disease intervention strategies were implemented to treat affected corals. Two treatment strategies were employed: (1) topical application of an amoxicillin paste directly to disease margins, and (2) application of a chlorinated epoxy to disease margins as well as an adjacent “disease break” trench. Effectiveness of treatments on 2,379 lesions from 725 corals representing five species was evaluated using mixed effects logistic regression models which demonstrated substantially greater effectiveness of amoxicillin compared to chlorine-treated lesions across all species up to 3 months post-treatment. As a result of the failed chlorinated epoxy treatments, any new lesions that appeared during subsequent monitoring events were treated with amoxicillin paste, and all corals were monitored and treated as needed approximately every 2 months for up to 24 months. The health status of 1664 amoxicillin-treated corals during each monitoring event was used to model the probability of a coral being uninfected over time. Models included species and geographic regions as variables. The appearance of new lesions (reinfection rates) varied by species, and offshore sites showed greater reinfection rates than inshore sites; however, all sites and species exhibited a decreased probability of reinfection with time since initial treatment. We conclude that topical amoxicillin treatments are highly effective at halting SCTLD lesions and that through initial and follow-up treatments as needed, colonies and reef sites will progress toward a lower prevalence of SCTLD.

Pharmaceutical design of a delivery system for the bacteriocin lacticin 3147 - Aoibhín Ryan; Pratikkumar Patel; Paula M. O’Connor; R. Paul Ross; Colin Hill; Sarah P. Hudson (Drug Delivery and Translational Research, 2021)
Lacticin 3147 is a dual-acting two-peptide bacteriocin which is generally active against Gram-positive bacteria, including Listeria monocytogenes and antimicrobial-resistant bacteria such as Closteroides difficile in the colon. L. monocytogenes infections can cause life-long effects in the elderly and vulnerable and can cause severe complications in pregnant women. C. difficile causes one of the most common healthcare-associated infections and can be fatal in vulnerable groups such as the elderly. Although lacticin 3147 is degraded by intestinal proteases and has poor aqueous solubility, encapsulation of the bacteriocin could enable its use as an antimicrobial for treating these bacterial infections locally in the gastrointestinal tract. Lacticin 3147 displayed activity in aqueous solutions at a range of pH values and in gastric and intestinal fluids. Exposure to trypsin and α-chymotrypsin resulted in complete inactivation, implying that lacticin 3147 should be protected from these enzymes to achieve successful local delivery to the gastrointestinal tract. The amount of lacticin 3147 dissolved, i.e. its solution concentration, in water or buffered solutions at pH 1.6 and 7.4 was low and varied with time but increased and was stabilized in gastrointestinal fluids by the phospholipid and bile salt components present. Thus, the feasibility of a solid lipid nanoparticle (SLN) delivery system for local administration of lacticin 3147 was investigated. Bacteriocin activity was observed after encapsulation and release from a lipid matrix. Moreover, activity was seen after exposure to degrading enzymes. Further optimization of SLN delivery systems could enable the successful pharmaceutical development of active lacticin 3147 as an alternative to traditional antibiotics. Graphical abstract

Molecular Mechanisms of Coral Persistence Within Highly Urbanized Locations in the Port of Miami, Florida - Ewelina T. Rubin; Ian C. Enochs; Colin Foord; Anderson B. Mayfield; Graham Kolodziej; Isabelle Basden; Derek P. Manzello (Frontiers in Marine Science, 2021)
Healthy coral communities can be found on artificial structures (concrete walls and riprap) within the Port of Miami (PoM), Florida. These communities feature an unusually high abundance of brain corals, which have almost entirely vanished from nearby offshore reefs. These corals appear to be thriving in very low-quality waters influenced by dense ship and boat traffic, dredging, and numerous residential and industrial developments. The PoM basin is part of Biscayne Bay, an estuarine environment that experiences frequent freshwater input, high nutrient loading, hypoxia, and acidification. To investigate if there is a molecular basis behind the ability of these corals to persist within these highly “urbanized” waters, we compared whole transcriptome expression profiles from 25 PoM Pseudodiploria strigosa colonies against six conspecifics from a nearby offshore reef. We found that the urban corals exhibited higher expression of (1) transcripts encoding pattern-recognition receptors which may allow these corals to better sense and detect food particles and pathogenic invaders; (2) digestive and degradation-associated enzymes, which may suggest an elevated capacity for heterotrophy and pathogen digestion; and (3) transcripts related to innate immunity, defense, and cellular detoxification, which may collectively protect against pathogenic organisms and water pollution impacts. Large ribosomal subunit rRNA gene mapping revealed that P. strigosa colonies from the PoM sites predominantly hosted heat-tolerant endosymbionts from the genus Durusdinium while offshore conspecifics’ communities were dominated by symbionts in the genus Breviolum . These findings reveal transcriptomic plasticity and molecular mechanisms contributing to the persistence of these corals within a highly urbanized habitat.

Freshwater early life growth influences partial migration in populations of Dolly Varden (Salvelinus malma malma) - Christie M. Morrison; Colin P. Gallagher; Keith B. Tierney; Kimberly L. Howland (Polar Biology, 2021)
Populations of northern Dolly Varden ( Salvelinus malma malma ) exhibit partial seaward migration, yet little is known about this phenomenon in Dolly Varden populations. Our study analyzed data from three different Dolly Varden populations in the western Canadian Arctic in order to determine if: (1) differences in size-at-first seaward migration exist between fish that migrate at early and late ages among populations inhabiting different river systems, and (2) annual growth influences anadromous or resident life history choice. Otolith strontium analysis and back-calculation were used to determine age- and size-at-first seaward migration, respectively. Differences in age- and size-at-first seaward migration were determined across river system and migration age. Back-calculated fish lengths were compared using a mixed effect model to determine how early growth influences migratory tactics (early or late aged smolt, or resident). Our results indicate that fish exhibiting faster early growth migrated in earlier years and at smaller sizes than slower growing fish, however size- and age-at first seaward migration varied by river system. Faster growing Dolly Varden tended to become either residents or early smolts, while slower growth was associated with smolting later in life. This is contrary to life history theory where the fastest growing fish in a population should mature as a resident. Our results indicate factors other than growth may be influencing life history ‘decisions’ in Dolly Varden. Future work on growth efficiencies and metabolic rates is needed to assess how they affect migratory behaviours.

Strong differences in migratory connectivity patterns among species of Neotropical‐Nearctic migratory birds revealed by combining stable isotopes and abundance in a Bayesian assignment analysis - Colin E. Studds; Joseph M. Wunderle; Peter P. Marra (Journal of Biogeography, 2021)
Aim Conservation planning for migratory species requires knowing how populations are connected throughout the annual cycle. We measured migratory connectivity for five migratory songbird species by combining stable‐hydrogen isotopes in feathers (δ 2 H F ) with citizen science data on breeding range abundance. Location Caribbean Basin and North America. Taxa Neotropical migratory birds: Mniotilta varia , Setophaga ruticilla , Seiurus aurocapilla , Setophaga americana , and Setophaga discolor . Methods We analyzed δ 2 H F in feathers grown on North American breeding grounds and sampled at 20 Caribbean Basin sites across most of the non‐breeding range of each species. We made Bayesian assignments to breeding origin by combining δ 2 H F values and North American Breeding Bird Survey abundance data. For each species, we used cluster analysis to group Caribbean sites into non‐breeding regions that shared birds with similar breeding ground assignment probabilities. We then mapped assignment probabilities for the non‐breeding regions of each species onto breeding ground δ 2 H F surfaces and estimated the strength of migratory connectivity. Results Apart from some general similarities, the five species demonstrated different patterns of migratory connectivity. Species with larger non‐breeding ranges exhibited stronger migratory connectivity compared to those with smaller non‐breeding ranges. Despite geographical overlap, birds from each non‐breeding region had mostly unique breeding ground origins. Main conclusions The contrasting patterns of migratory connectivity shown by the five species suggest that geographic distribution during the non‐breeding period is a poor indicator of breeding ground origin. Our results indicate that full annual cycle conservation planning, which requires migratory connectivity information, should proceed on a species‐specific basis.

Lipophilic Salts and Lipid-Based Formulations: Enhancing the Oral Delivery of Octreotide - Peng Li; Leigh Ford; Shadabul Haque; Mitchell P. McInerney; Hywel D. Williams; Peter J. Scammells; Philip E. Thompson; Vincent Jannin; Christopher J. H. Porter; Hassan Benameur; Colin W. Pouton (Pharmaceutical Research, 2021)

Orchid bees (Apidae, Euglossini) from Oil Palm Plantations in Eastern Amazon Have Larger but Not Asymmetrical Wings - Thaline de Freitas Brito; Nelson S. Pinto; Colin C. Phifer; Jessie L. Knowlton; Felipe A. L. Contrera; Márcia M. Maués; Daniel P. Silva (Neotropical Entomology, 2021)

Impact of changes in controlled drugs legislation on benzodiazepine receptor agonist prescribing in Ireland: a repeated cross-sectional study - Cathal A. Cadogan; Colin P. Bradley; Kathleen Bennett (European Journal of Clinical Pharmacology, 2021)
Purpose To examine the impact of new controlled drugs legislation introduced in May 2017 on benzodiazepine receptor agonist (BZRA) prescribing in Ireland. Methods A repeated cross-sectional analysis was conducted using publically available monthly pharmacy claims data from the General Medical Services (GMS) database. The study population comprised all GMS-eligible individuals aged ≥ 16 years from January 2016 to September 2019. Monthly prevalence rates of individuals receiving BZRA prescriptions per 10,000 eligible population were calculated and trends examined over time. Segmented linear regression of prevalence rates was used to examine changes before and after introduction of the legislation stratified by gender and age groups. Regression coefficients (β) and 95% confidence intervals (CIs) for monthly change were calculated. Results Pre-legislation (January 2016 to April 2017), there was a significant monthly decline in benzodiazepine prevalence rate (β = − 1.18; 95% CI − 1.84, − 0.51; p < 0.001) but no significant change in Z-drug prescribing. Post-legislation (May 2017 to September 2019), increases in prevalence rates were observed for benzodiazepines (β = 1.04; 95% CI 0.17, 1.92; p = 0.021) and Z-drugs (β = 1.04; 95% CI 0.26, 1.83; p = 0.010). Post-legislation trends showed increases in BZRA prevalence rates among the youngest subgroup (16–44 years), with variable changes in the middle-aged subgroup (45–64 years) and no changes in the oldest subgroup (≥ 65 years). Conclusions This study indicates that introduction of new legislation had limited impact on BZRA prescribing on the main public health scheme in Ireland. Interventions targeting specific population subgroups may be required to achieve sustained reductions in prescribing.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Low dispersal and ploidy differences in a grass maintain photosynthetic diversity despite gene flow and habitat overlap - Jill K. Olofsson; Emma V. Curran; Florence Nyirenda; Matheus E. Bianconi; Luke T. Dunning; Vanja Milenkovic; Graciela Sotelo; Oriane Hidalgo; Robyn F. Powell; Marjorie R. Lundgren; Ilia J. Leitch; Patrik Nosil; et al. (Molecular Ecology, 2021)
Geographical isolation facilitates the emergence of distinct phenotypes within a single species, but reproductive barriers or selection are needed to maintain the polymorphism after secondary contact. Here, we explore the processes that maintain intraspecific variation of C 4 photosynthesis, a complex trait that results from the combined action of multiple genes. The grass Alloteropsis semialata includes C 4 and non‐C 4 populations, which have coexisted as a polyploid series for more than 1 million years in the miombo woodlands of Africa. Using population genomics, we show that there is genome‐wide divergence for the photosynthetic types, but the current geographical distribution does not reflect a simple habitat displacement scenario as the genetic clusters overlap, being occasionally mixed within a given habitat. Despite evidence of recurrent introgression between non‐C 4 and C 4 groups, in both diploids and polyploids, the distinct genetic lineages retain their identity, potentially because of selection against hybrids. Coupled with strong isolation by distance within each genetic group, this selection created a geographical mosaic of photosynthetic types. Diploid C 4 and non‐C 4 types never grew together, and the C 4 type from mixed populations constantly belonged to the hexaploid lineage. By limiting reproductive interactions between photosynthetic types, the ploidy difference probably allows their co‐occurrence, reinforcing the functional diversity within this species. Together, these factors enabled the persistence of divergent physiological traits of ecological importance within a single species despite gene flow and habitat overlap.

Marine Important Bird and Biodiversity Areas for Penguins in Antarctica, Targets for Conservation Action - Jonathan Handley; Marie-Morgane Rouyer; Elizabeth J. Pearmain; Victoria Warwick-Evans; Katharina Teschke; Jefferson T. Hinke; Heather Lynch; Louise Emmerson; Colin Southwell; Gary Griffith; César A. Cárdenas; Aldina M. A. Franco; et al. (Frontiers in Marine Science, 2021)
Global targets for area-based conservation and management must move beyond threshold-based targets alone and must account for the quality of such areas. In the Southern Ocean around Antarctica, a region where key biodiversity faces unprecedented risks from climate change and where there is a growing demand to extract resources, a number of marine areas have been afforded enhanced conservation or management measures through two adopted marine protected areas (MPAs). However, evidence suggests that additional high quality areas could benefit from a proposed network of MPAs. Penguins offer a particular opportunity to identify high quality areas because these birds, as highly visible central-place foragers, are considered indicator species whose populations reflect the state of the surrounding marine environment. We compiled a comprehensive dataset of the location of penguin colonies and their associated abundance estimates in Antarctica. We then estimated the at-sea distribution of birds based on information derived from tracking data and through the application of a modified foraging radius approach with a density decay function to identify some of the most important marine areas for chick-rearing adult penguins throughout waters surrounding Antarctica following the Important Bird and Biodiversity Area (IBA) framework. Additionally, we assessed how marine IBAs overlapped with the currently adopted and proposed network of key management areas (primarily MPAs), and how the krill fishery likely overlapped with marine IBAs over the past five decades. We identified 63 marine IBAs throughout Antarctic waters and found that were the proposed MPAs to be adopted, the permanent conservation of high quality areas for penguin species would increase by between 49 and 100% depending on the species. Furthermore, our data show that, despite a generally contracting range of operation by the krill fishery in Antarctica over the past five decades, a consistently disproportionate amount of krill is being harvested within marine IBAs compared to the total area in which the fishery operates. Our results support the designation of the proposed MPA network and offer additional guidance as to where decision-makers should act before further perturbation occurs in the Antarctic marine ecosystem.

An assessment of chlorophyll preservation in lake sediments using multiple analytical techniques applied to the annually laminated lake sediments of Nylandssjön - Johan Rydberg; Colin A. Cooke; Julie Tolu; Alexander P. Wolfe; Rolf D. Vinebrooke (Journal of Paleolimnology, 2020)
Chlorophyll is frequently used as a proxy for autochthonous production in lakes. This use of chlorophyll concentrations in sediments to infer historical changes in lake primary production relies heavily on the assumption that preservation is sufficient to reflect the productivity in a meaningful way. In this study, we use a series of freeze cores from a lake with annually laminated sediments to assess how reliable down-core trends in chlorophyll are, and to what extent chlorophyll is degraded in the sediment. A striking consistency in the down-core chlorophyll trends in four sediment cores collected in different years (1983, 1992, 2002 and 2010) shows that the sediment preserves a consistent chlorophyll signal over longer timescales. However, there are also clear signs that diagenetic processes within the sediment affect the chlorophyll concentration in sediment layers younger than 10–15 years. This implies that care is needed when interpreting chlorophyll trends in recent sediments. Further, our data show that high-performance liquid chromatography (HPLC) and visible reflectance spectroscopy (VRS) detect similar chlorophyll concentrations for recently dried samples. A third analytical technique, pyrolysis–gas chromatography/mass spectrometry, which provides semi-quantitative values for chlorophyll, also produce a temporal trend that is highly correlated with data from the two quantitative techniques. For samples that have been stored dried at room temperature for several years there is, however, a large discrepancy between the two quantitative techniques. The VRS method is more robust with regards to degradation during storage, while HPLC results demonstrate clear storage effects.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

High silicon concentrations in grasses are linked to environmental conditions and not associated with C 4 photosynthesis - William H. Brightly; Sue E. Hartley; Colin P. Osborne; Kimberley J. Simpson; Caroline A. E. Strömberg (Global Change Biology, 2020)
The uptake and deposition of silicon (Si) as silica phytoliths is common among land plants and is associated with a variety of functions. Among these, herbivore defense has received significant attention, particularly with regard to grasses and grasslands. Grasses are well known for their high silica content, a trait which has important implications ranging from defense to global Si cycling. Here, we test the classic hypothesis that C 4 grasses evolved stronger mechanical defenses than C 3 grasses through increased phytolith deposition, in response to extensive ungulate herbivory (“C 4 ‐grazer hypothesis”). Despite mixed support, this hypothesis has received broad attention, even outside the realm of plant biology. Because C 3 and C 4 grasses typically dominate in different climates, with the latter more abundant in hot, dry regions, we also investigated the effects of water availability and temperature on Si deposition. We compiled a large dataset of grasses grown under controlled environmental conditions. Using phylogenetically informed generalized linear mixed models and character evolution models, we evaluated whether photosynthetic pathway or growth condition influenced Si concentration. We found that C 4 grasses did not show consistently elevated Si concentrations compared with C 3 grasses. High temperature treatments were associated with increased concentration, especially in taxa adapted to warm regions. Although the effect was less pronounced, reduced water treatment also promoted silica deposition, with slightly stronger response in dry habitat species. The evidence presented here rejects the “C 4 ‐grazer hypothesis.” Instead, we propose that the tendency for C 4 grasses to outcompete C 3 species under hot, dry conditions explains previous observations supporting this hypothesis. These findings also suggest a mechanism via which anthropogenic climate change may influence silica deposition in grasses and, by extension, alter the important ecological and geochemical processes it affects.

Screening method for the detection of residues of amphenicol antibiotics in bovine milk by optical biosensor - Colin S. Thompson; Imelda M. Traynor; Terence L. Fodey; P. Barnes; Dermot V. Faulkner; Steven R.H. Crooks (Food Additives & Contaminants: Part A, 2020)

Shelterbelt systems establishment in Saskatchewan, Canada: a multi-criteria fuzzy logic approach to land suitability mapping - Beyhan Y. Amichev; Colin P. Laroque; Kenneth W. Belcher; Murray J. Bentham; Ken C. J. Van Rees (New Forests, 2020)

Preparing interdisciplinary leadership for a sustainable future - Christopher G. Boone; Steward T. A. Pickett; Gabriele Bammer; Kamal Bawa; Jennifer A. Dunne; Iain J. Gordon; David Hart; Jessica Hellmann; Alison Miller; Mark New; Jean P. Ometto; Ken Taylor; et al. (Sustainability Science, 2020)

Agricultural intensification is causing rapid habitat change in the Tonle Sap Floodplain, Cambodia - Simon P. Mahood; Colin M. Poole; James E. M. Watson; Richard A. MacKenzie; Sahadev Sharma; Stephen T. Garnett (Wetlands Ecology and Management, 2020)

Influence of the composition and diversity of tree fodder grazed on the selection and voluntary intake by cattle in a tropical forest - S. Albores-Moreno; J. A. Alayón-Gamboa; A. Morón-Ríos; P. N. Ortiz-Colin; J. Ventura-Cordero; P. G. González-Pech; G. E. Mendoza-Arroyo; J. C. Ku-Vera; G. Jiménez-Ferrer; A. T. Piñeiro-Vázquez (Agroforestry Systems, 2020)

Shelterbelt removals in Saskatchewan, Canada: implications for long-term carbon sequestration - Beyhan Y. Amichev; Colin P. Laroque; Ken C. J. Van Rees (Agroforestry Systems, 2020)

Frontiers in modelling social–ecological dynamics of recreational fisheries: A review and synthesis - Christopher T. Solomon; Colin J. Dassow; Carolyn M. Iwicki; Olaf P. Jensen; Stuart E. Jones; Greg G. Sass; Ashley Trudeau; Brett T. van Poorten; Dane Whittaker (Fish and Fisheries, 2020)
Recreational fisheries are culturally and economically important around the world. Recent research emphasizes that understanding and managing these systems requires a social–ecological perspective. We systematically reviewed quantitative social–ecological models of marine and freshwater recreational fisheries to summarize their conceptualization of social, ecological, and social–ecological dynamics and identify research frontiers. From a candidate set of 626 studies published between 1975 and 2018, 49 met criteria for inclusion in our review. These studies, though diverse in terms of focal species and processes considered, were geographically limited to a few locations and ignored large regions of the globe where recreational fishing is important. There were also important gaps in the social and ecological processes that were included in published models. Reflecting on these patterns in the context of previous conceptual frameworks, we define five key frontiers for future work: 1) exploring the implications of social and behavioural processes like heuristics, social norms, and information sharing for angler decisions and fishery dynamics; 2) modelling governance with more realistic complexity; 3) incorporating ideas from resilience thinking and complex adaptive systems, including slow variables, destabilizing feedbacks, surprises and diversity; 4) considering key ideas in fisheries systems, including spatial and temporal effort dynamics, catch hyperstability, and stocking; and 5) thinking synthetically about the models that we use to describe social–ecological dynamics in recreational fisheries, via explicit comparisons and formal integration with data. Exploration of these frontiers, while remembering the distinction between model complexity and model usefulness, will improve our ability to understand and sustain recreational fisheries.

The climatic space of European pollen taxa - Dongyang Wei; I. Colin Prentice; Sandy P. Harrison (Ecology, 2020)
Pollen data are widely used to reconstruct past climate changes, using relationships between modern pollen abundance in surface samples and climate at the surface‐sample sites as a calibration. Visualization of modern pollen data in multidimensional climate space provides a way to establish that taxon abundances are well behaved before using them in climate reconstructions. Visualization is also helpful for ecological interpretation of variations in pollen abundance in space and time. Here, we present Generalized Additive Models for the distribution of 195 European pollen and pteridophyte spore taxa in a bioclimate space defined by seasonal temperatures (as mean temperature of the coldest month and annual growing degree days) and an annual moisture index. These models can be used to explore the realized climate niche of pollen taxa and to build statistical models for palaeoclimate reconstruction. The data set is released under a Creative Commons BY license. When using the data set, we kindly request that you cite this article.

Incorporating connectivity into conservation planning for the optimal representation of multiple species and ecosystem services - Sara H. Williams; Sarah A. Scriven; David F. R. P. Burslem; Jane K. Hill; Glen Reynolds; Agnes L. Agama; Frederick Kugan; Colin R. Maycock; Eyen Khoo; Alexander Y. L. Hastie; John B. Sugau; Reuben Nilus; et al. (Conservation Biology, 2020)
Conservation planning tends to focus on protecting species’ ranges or landscape connectivity but seldom both—particularly in the case of diverse taxonomic assemblages and multiple planning goals. Therefore, information on potential trade‐offs between maintaining landscape connectivity and achieving other conservation objectives is lacking. We developed an optimization approach to prioritize the maximal protection of species’ ranges, ecosystem types, and forest carbon stocks, while also including habitat connectivity for range‐shifting species and dispersal corridors to link protected area. We applied our approach to Sabah, Malaysia, where the state government mandated an increase in protected‐area coverage of approximately 305,000 ha but did not specify where new protected areas should be. Compared with a conservation planning approach that did not incorporate the 2 connectivity features, our approach increased the protection of dispersal corridors and elevational connectivity by 13% and 21%, respectively. Coverage of vertebrate and plant species’ ranges and forest types were the same whether connectivity was included or excluded. Our approach protected 2% less forest carbon and 3% less butterfly range than when connectivity features were not included. Hence, the inclusion of connectivity into conservation planning can generate large increases in the protection of landscape connectivity with minimal loss of representation of other conservation targets.

Human exposure to synthetic endocrine disrupting chemicals (S-EDCs) is generally negligible as compared to natural compounds with higher or comparable endocrine activity: how to evaluate the risk of the S-EDCs? - Herman Autrup; Frank A. Barile; Sir Colin Berry; Bas J. Blaauboer; Alan Boobis; Herrmann Bolt; Christopher J. Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2020)
Theoretically, both synthetic endocrine disrupting chemicals (S-EDCs) and natural (exogenous and endogenous) endocrine disrupting chemicals (N-EDCs) can interact with endocrine receptors and disturb hormonal balance. However, compared to endogenous hormones, S-EDCs are only weak partial agonists with receptor affinities several orders of magnitude lower. Thus, to elicit observable effects, S-EDCs require considerably higher concentrations to attain sufficient receptor occupancy or to displace natural hormones and other endogenous ligands. Significant exposures to exogenous N-EDCs may result from ingestion of foods such as soy-based diets, green tea and sweet mustard. While their potencies are lower as compared to natural endogenous hormones, they usually are considerably more potent than S-EDCs. Effects of exogenous N-EDCs on the endocrine system were observed at high dietary intakes. A causal relation between their mechanism of action and these effects is established and biologically plausible. In contrast, the assumption that the much lower human exposures to S-EDCs may induce observable endocrine effects is not plausible. Hence, it is not surprising that epidemiological studies searching for an association between S-EDC exposure and health effects have failed. Regarding testing for potential endocrine effects, a scientifically justified screen should use in vitro tests to compare potencies of S-EDCs with those of reference N-EDCs. When the potency of the S-EDC is similar or smaller than that of the N-EDC, further testing in laboratory animals and regulatory consequences are not warranted.

Xentry-Gap19 inhibits Connexin43 hemichannel opening especially during hypoxic injury - Frazer P. Coutinho; Colin R. Green; Monica L. Acosta; Ilva D. Rupenthal (Drug Delivery and Translational Research, 2020)

Host Range Expansion of an Endemic Insect Herbivore is Associated With High Nitrogen and Low Fibre Content in Exotic Pasture Plants - Sylvester R. Atijegbe; Sarah Mansfield; Colin M. Ferguson; Susan P. Worner; Michael Rostás (Journal of Chemical Ecology, 2020)

Assessment of uncertainty in multi‐model means of downscaled South Florida precipitation for projected (2019–2099) climate - Johnna M. Infanti; Ben P. Kirtman; Nicholas G. Aumen; John Stamm; Colin Polsky (International Journal of Climatology, 2020)
South Florida resource management, particularly the Everglades restoration effort, is beginning to consider projections of precipitation from multiple climate models for decision‐making. Because precipitation changes can significantly affect the Everglades ecosystem, characterization of precipitation projection uncertainty is important for resource management decisions, and reduction of uncertainty is desired for better decision‐making. Though uncertainty of precipitation projections has been characterized for many regions, uncertainty has not been sufficiently quantified for South Florida. This study builds upon prior results for projected Florida precipitation by considering recent climate model simulations, seasonal and spatial information, and uncertainty quantification and reduction. We identify the multi‐model mean change in South Florida precipitation and characterize the uncertainty of 37 statistically downscaled Coupled Model Intercomparison Project Phase 5 models. For 2019–2045, there is a likely (over 60% of ensemble members) increase in South Florida annual mean precipitation owing to a likely to very likely (near 90% of ensemble members) increase in dry season (November, December, and January) precipitation, while wet season (June, July, and August) shows a more likely than not (over 50% of ensemble members) decrease in precipitation in the southern region and increase in precipitation in the northern region of South Florida. As South Florida agencies are on the verge of including precipitation projections in their upcoming planning horizon, this information will aid South Florida climate data users in decisions influenced by future rainfall.

The global distribution of grass functional traits within grassy biomes - Emma C. Jardine; Gavin H. Thomas; Elisabeth J. Forrestel; Caroline E. R. Lehmann; Colin P. Osborne (Journal of Biogeography, 2020)
Aim The sorting of functional traits along environmental gradients is an important driver of community and landscape scale patterns of functional diversity. However, the significance of environmental factors in driving functional gradients within biomes and across continents remains poorly understood. Here, we evaluate the relationship of soil nutrients and climate to leaf traits in grasses (Poaceae) that are hypothesized to reflect different strategies of resource use along gradients of resource availability. Location Global. Taxon Poaceae. Methods We made direct measurements on herbarium specimens to compile a global dataset of functional traits and realized environmental niche for 279 grass species that are common in grassland and savanna biomes. We examined the strength and direction of correlations between pairwise trait combinations and measured the distribution of traits in relation to gradients of soil properties and climate, while accounting for phylogenetic relatedness. Results Leaf trait variation among species follows two orthogonal axes. One axis represents leaf size and plant height, and we showed positive scaling relationships between these size‐related traits. The other axis corresponds to economic traits associated with resource acquisition and allocation, including leaf tensile strength (LTS), specific leaf area (SLA) and leaf nitrogen content (LNC). Global‐scale variation in LNC was primarily correlated with soil nutrients, while LTS, SLA and size‐related traits showed weak relationships to environment. However, most of the trait variation occurred within different vegetation types, independent of large‐scale environmental gradients. Main conclusions Our work provides evidence among grasses for relationships at the global scale between leaf economic traits and soil fertility, and for an influence of aridity on traits related to plant size. However, large unexplained variance and strong phylogenetic signal in the model residuals imply that at this scale the evolution of functional traits is driven by factors beyond contemporary environmental or climatic conditions.

PATHBIO: an international training program for precision mouse phenotyping - Jesus Ruberte; Paul N. Schofield; Cord Brakebusch; Peter Vogel; Yann Herault; Guillem Gracia; Colin McKerlie; Martin Hrabĕ de Angelis; Michael Hagn; John P. Sundberg (Mammalian Genome, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Medication reconciliation: time to save? A cross-sectional study from one acute hospital - Elaine K. Walsh; Ann Kirby; Patricia M. Kearney; Colin P. Bradley; Aoife Fleming; Kieran A. O’Connor; Ciaran Halleran; Timothy Cronin; Elaine Calnan; Patricia Sheehan; Laura Galvin; Derina Byrne; et al. (European Journal of Clinical Pharmacology, 2019)

Anthropogenic modifications to fire regimes in the wider Serengeti‐Mara ecosystem - James R. Probert; Catherine L. Parr; Ricardo M. Holdo; T. Michael Anderson; Sally Archibald; Colin J. Courtney Mustaphi; Andrew P. Dobson; Jason E. Donaldson; Grant C. Hopcraft; Gareth P. Hempson; Thomas A. Morrison; Colin M. Beale (Global Change Biology, 2019)
Fire is a key driver in savannah systems and widely used as a land management tool. Intensifying human land uses are leading to rapid changes in the fire regimes, with consequences for ecosystem functioning and composition. We undertake a novel analysis describing spatial patterns in the fire regime of the Serengeti‐Mara ecosystem, document multidecadal temporal changes and investigate the factors underlying these patterns. We used MODIS active fire and burned area products from 2001 to 2014 to identify individual fires; summarizing four characteristics for each detected fire: size, ignition date, time since last fire and radiative power. Using satellite imagery, we estimated the rate of change in the density of livestock bomas as a proxy for livestock density. We used these metrics to model drivers of variation in the four fire characteristics, as well as total number of fires and total area burned. Fires in the Serengeti‐Mara show high spatial variability—with number of fires and ignition date mirroring mean annual precipitation. The short‐term effect of rainfall decreases fire size and intensity but cumulative rainfall over several years leads to increased standing grass biomass and fuel loads, and, therefore, in larger and hotter fires. Our study reveals dramatic changes over time, with a reduction in total number of fires and total area burned, to the point where some areas now experience virtually no fire. We suggest that increasing livestock numbers are driving this decline, presumably by inhibiting fire spread. These temporal patterns are part of a global decline in total area burned, especially in savannahs, and we caution that ecosystem functioning may have been compromised. Land managers and policy formulators need to factor in rapid fire regime modifications to achieve management objectives and maintain the ecological function of savannah ecosystems.

Meat, eggs, full-fat dairy, and nutritional boogeymen: Does the way in which animals are raised affect health differently in humans? - Christopher P. Haskins; George Henderson; Colin E. Champ (Critical Reviews in Food Science and Nutrition, 2019)

Phylogeny and ecological processes influence grass coexistence at different spatial scales within the steppe biome - Hui Liu; Colin P. Osborne; Deyi Yin; Robert P. Freckleton; Gaoming Jiang; Meizhen Liu (Oecologia, 2019)

Growth and reproductive characteristics of rarely observed resident female Dolly Varden (Salvelinus malma malma) in North America - Colin P. Gallagher; Christie M. Morrison; Ellen V. Lea; Norman M. Halden; Kimberly L. Howland (Hydrobiologia, 2019)

Impacts of Channel Morphodynamics on Fish Habitat Utilization - Parna Parsapour-Moghaddam; Colin P. Brennan; Colin D. Rennie; Chris K. Elvidge; Steven J. Cooke (Environmental Management, 2019)

Retention of Nitrate-N in Mineral Soil Organic Matter in Different Forest Age Classes - Colin B. Fuss; Gary M. Lovett; Christine L. Goodale; Scott V. Ollinger; Ashley K. Lang; Andrew P. Ouimette (Ecosystems, 2019)

Re-analysis of archaeobotanical remains from pre- and early agricultural sites provides no evidence for a narrowing of the wild plant food spectrum during the origins of agriculture in southwest Asia - Michael Wallace; Glynis Jones; Michael Charles; Emily Forster; Eleanor Stillman; Vincent Bonhomme; Alexandra Livarda; Colin P. Osborne; Mark Rees; Georg Frenck; Catherine Preece (Vegetation History and Archaeobotany, 2019)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Evidence from plutonic xenoliths for magma differentiation, mixing and storage in a volatile-rich crystal mush beneath St. Eustatius, Lesser Antilles - George F. Cooper; Jon D. Blundy; Colin G. Macpherson; Madeleine C. S. Humphreys; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2019)

Long‐term dietary shift and population decline of a pelagic seabird—A health check on the tropical Atlantic? - S. James Reynolds; B. John Hughes; Colin P. Wearn; Roger C. Dickey; Judith Brown; Nicola L. Weber; Sam B. Weber; Vitor H. Paiva; Jaime A. Ramos (Global Change Biology, 2019)
In the face of accelerating ecological change to the world's oceans, seabirds are some of the best bio‐indicators of marine ecosystem function. However, unravelling ecological changes that pre‐date modern monitoring programmes remains challenging. Using stable isotope analysis of feathers and regurgitants collected from sooty terns ( Onychoprion fuscatus ) nesting at a major Atlantic colony, we reconstructed a long‐term dietary time series from 1890 to the present day and show that a significant dietary shift occurred during the second half of the twentieth century coinciding with an apparent population collapse of approximately 84%. After correcting for the “Suess Effect,” δ 13 C in feathers declined by ~1.5‰ and δ 15 N by ~2‰ between the 1890s and the present day, indicating that birds changed their diets markedly over the period of population decline. Isotopic niches were equally wide before and after the population collapse but isotopic mixing models suggest that birds have grown ever more reliant on nutrient‐poor squid and invertebrates as teleost fish have declined in availability. Given that sooty terns rely heavily on associations with sub‐surface predators such as tuna to catch fish prey, the rapid expansion of industrialized fisheries for these species over the same period seems a plausible mechanism. Our results suggest that changes to marine ecosystems over the past 60 years have had a dramatic impact on the ecology of the most abundant seabird of tropical oceans, and highlight the potentially pervasive consequences of large predatory fish depletion on marine ecosystem function.

Comparing abundance‐based and tag‐based estimates of coho salmon marine survival - Sean M. Cochran; Seth Ricker; Colin Anderson; Sean P. Gallagher; Darren M. Ward (Fisheries Management and Ecology, 2019)
Obtaining reliable estimates of marine survival is essential for understanding anadromous salmon population dynamics. Two common approaches to estimating marine survival are (a) dividing abundance of returning adult salmon abundance by abundance of smolts from the same cohort, or (b) tagging a portion of the migrating smolts and estimating the return rate of tagged adults. This study compared these two approaches to estimating marine survival for coho salmon, Oncorhynchus kisutch (Walbaum), across multiple years in three California streams. Abundance‐based survival estimates were higher than tag‐based estimates; average estimates for the two techniques differed from 1.5‐fold to 7.4‐fold across streams. One likely cause for these divergent estimates is migration of juveniles from natal habitat before smolt trapping begins, resulting in an underestimate of smolt abundance and an overestimate of marine survival rate for the abundance‐based method. Estimates of marine survival obtained from abundance estimates and tag returns are not directly comparable.

Global photosynthetic capacity is optimized to the environment - Nicholas G. Smith; Trevor F. Keenan; I. Colin Prentice; Han Wang; Ian J. Wright; Ülo Niinemets; Kristine Y. Crous; Tomas F. Domingues; Rossella Guerrieri; F. Yoko Ishida; Jens Kattge; Eric L. Kruger; et al. (Ecology Letters, 2019)

Evidence gaps and biodiversity threats facing the marine environment of the United Kingdom’s Overseas Territories - Bethan C. O’Leary; Philip Fieldhouse; Colin J. McClean; Adriana E. S. Ford; Polly Burns; Julie P. Hawkins; Callum M. Roberts (Biodiversity and Conservation, 2019)

C 4 anatomy can evolve via a single developmental change - Marjorie R. Lundgren; Luke T. Dunning; Jill K. Olofsson; Jose J. Moreno‐Villena; Jacques W. Bouvier; Tammy L. Sage; Roxana Khoshravesh; Stefanie Sultmanis; Matt Stata; Brad S. Ripley; Maria S. Vorontsova; Guillaume Besnard; et al. (Ecology Letters, 2019)
C 4 photosynthesis is a complex trait that boosts productivity in warm environments. Paradoxically, it evolved independently in numerous plant lineages, despite requiring specialised leaf anatomy. The anatomical modifications underlying C 4 evolution have previously been evaluated through interspecific comparisons, which capture numerous changes besides those needed for C 4 functionality. Here, we quantify the anatomical changes accompanying the transition between non‐C 4 and C 4 phenotypes by sampling widely across the continuum of leaf anatomical traits in the grass Alloteropsis semialata . Within this species, the only trait that is shared among and specific to C 4 individuals is an increase in vein density, driven specifically by minor vein development that yields multiple secondary effects facilitating C 4 function. For species with the necessary anatomical preconditions, developmental proliferation of veins can therefore be sufficient to produce a functional C 4 leaf anatomy, creating an evolutionary entry point to complex C 4 syndromes that can become more specialised.

Reef Shark Science – Key Questions and Future Directions - Michelle R. Heupel; Yannis P. Papastamatiou; Mario Espinoza; Madeline E. Green; Colin A. Simpfendorfer (Frontiers in Marine Science, 2019)

Unravelling the complexity of magma plumbing at Mount St. Helens: a new trace element partitioning scheme for amphibole - Madeleine C. S. Humphreys; George F. Cooper; Jing Zhang; Matthew Loewen; Adam J. R. Kent; Colin G. Macpherson; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2019)

Shifting global Larix distributions: Northern expansion and southern retraction as species respond to changing climate - Steven D. Mamet; Carissa D. Brown; Andrew J. Trant; Colin P. Laroque (Journal of Biogeography, 2019)
Aim Recent and rapid warming is reorganizing terrestrial vegetation, creating novel species assemblages, and shifting range limits. Relative to the evergreen species that currently dominate much of the boreal forest landscape, Larix (larch) distributions may be particularly responsive to climatic change due to their deciduous habit, and quick growth and reproduction. Here, we amassed data from 83 studies to describe and explain observed patterns of Larix range shifts under contemporary climate change. Location Northern hemisphere. Taxon Species of the genus Larix , deciduous gymnosperms. Methods With 181 observations of Larix range limit dynamics, we used five distribution parameters (tree line advance, stand infilling, tree line recession, stand thinning, no response) and their determinants (climate, land use change, natural disturbance) to describe and explain observed patterns of Larix range shifts under contemporary climate change. We ran a redundancy analysis on the matrix of five distribution parameters considered with other climatic and nonclimatic parameters as explanatory variables. We also characterized the climatic niche of Larix species (temperature and precipitation) and how the niche has changed during the 20th century. Results Of 173 sites studied over the full distribution of Larix , 63% experienced Larix population increases, 18% had population decreases, and no response was detected at 19% of sites. Latitudinal Larix tree lines in Siberia and North America appear to be infilling and shifting their distributions northward, whereas Larix recession and thinning was more common in southern regions, suggesting southern populations may be experiencing greater drought stress than their northern counterparts. Climatic niches of most Larix species shifted towards warmer and wetter conditions, with tree line advance/forest infilling in cool/dry climate space, and recession/thinning in warm/dry space. Main conclusions Northern expansion is underway or seems imminent for boreal Larix species, primarily L. laricina in North America. Retraction in southern regions and disappearance of some mountainous populations may be inevitable due to their narrow ecological niches. Species restricted to mountainous habitats may expand locally, though will likely not contribute to broad scale range expansion. These changes will depend on suitable climate, disturbance, and dispersal mechanisms.

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Comments on “a framework for assessing readiness for tiger reintroductions” - Dale G. Miquelle; Colin M. Poole; Simon P. Mahood; Henry Travers; Matt Linkie; J. Goodrich; Joe Walston; Kenserey Rotha; Alan Rabinowtiz (Biodiversity and Conservation, 2018)

Effects of habitat type change on taxonomic and functional composition of orchid bees (Apidae: Euglossini) in the Brazilian Amazon - Thaline F. Brito; Felipe A. L. Contrera; Colin C. Phifer; Jessie L. Knowlton; Leandro S. Brasil; Márcia M. Maués; Daniel P. Silva (Journal of Insect Conservation, 2018)

Groundwater sustainability and groundwater/surface-water interaction in arid Dunhuang Basin, northwest China - Jingjing Lin; Rui Ma; Yalu Hu; Ziyong Sun; Yanxin Wang; Colin P. R. McCarter (Hydrogeology Journal, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Drought timing and local climate determine the sensitivity of eastern temperate forests to drought - Loïc D'Orangeville; Justin Maxwell; Daniel Kneeshaw; Neil Pederson; Louis Duchesne; Travis Logan; Daniel Houle; Dominique Arseneault; Colin M. Beier; Daniel A. Bishop; Daniel Druckenbrod; Shawn Fraver; et al. (Global Change Biology, 2018)
Projected changes in temperature and drought regime are likely to reduce carbon (C) storage in forests, thereby amplifying rates of climate change. While such reductions are often presumed to be greatest in semi‐arid forests that experience widespread tree mortality, the consequences of drought may also be important in temperate mesic forests of Eastern North America ( ENA ) if tree growth is significantly curtailed by drought. Investigations of the environmental conditions that determine drought sensitivity are critically needed to accurately predict ecosystem feedbacks to climate change. We matched site factors with the growth responses to drought of 10,753 trees across mesic forests of ENA , representing 24 species and 346 stands, to determine the broad‐scale drivers of drought sensitivity for the dominant trees in ENA . Here we show that two factors—the timing of drought, and the atmospheric demand for water (i.e., local potential evapotranspiration; PET )—are stronger drivers of drought sensitivity than soil and stand characteristics. Drought‐induced reductions in tree growth were greatest when the droughts occurred during early‐season peaks in radial growth, especially for trees growing in the warmest, driest regions (i.e., highest PET ). Further, mean species trait values (rooting depth and ψ 50 ) were poor predictors of drought sensitivity, as intraspecific variation in sensitivity was equal to or greater than interspecific variation in 17 of 24 species. From a general circulation model ensemble, we find that future increases in early‐season PET may exacerbate these effects, and potentially offset gains in C uptake and storage in ENA owing to other global change factors.

Impact of soil pedogenesis on the diversity and composition of fungal communities across the California soil chronosequence of Mendocino - P. E. Courty; M. Buée; J. J. T. Tech; D. Brulé; Y. Colin; J. H. J. Leveau; S. Uroz (Mycorrhiza, 2018)

Offshore ocean dispersal of adult Dolly Varden Salvelinus malma in the Beaufort Sea - Michael B. Courtney; Brendan Scanlon; Randy J. Brown; Audun H. Rikardsen; Colin P. Gallagher; Andrew C. Seitz (Polar Biology, 2018)

Retracing the history and planning the future of the red squirrel (Sciurus vulgaris) in Ireland using non-invasive genetics - Denise B. O’Meara; Allan D. McDevitt; David O’Neill; Andrew P. Harrington; Peter Turner; William Carr; Michael Desmond; Colin Lawton; Ferdia Marnell; Sarah Rubalcava; Emma Sheehy; David P. Sleeman; et al. (Mammal Research, 2018)

Primate population dynamics: variation in abundance over space and time - Colin A. Chapman; Sarah Bortolamiol; Ikki Matsuda; Patrick A. Omeja; Fernanda P. Paim; Rafael Reyna-Hurtado; Raja Sengupta; Kim Valenta (Biodiversity and Conservation, 2018)

Pathogen spillover during land conversion - Christina L. Faust; Hamish I. McCallum; Laura S. P. Bloomfield; Nicole L. Gottdenker; Thomas R. Gillespie; Colin J. Torney; Andrew P. Dobson; Raina K. Plowright (Ecology Letters, 2018)
Pathogen spillover from wildlife to domestic animals and humans, and the reverse, has caused significant epidemics and pandemics worldwide. Although pathogen emergence has been linked to anthropogenic land conversion, a general framework to disentangle underlying processes is lacking. We develop a multi‐host model for pathogen transmission between species inhabiting intact and converted habitat. Interspecies contacts and host populations vary with the proportion of land converted; enabling us to quantify infection risk across a changing landscape. In a range of scenarios, the highest spillover risk occurs at intermediate levels of habitat loss, whereas the largest, but rarest, epidemics occur at extremes of land conversion. This framework provides insights into the mechanisms driving disease emergence and spillover during land conversion. The finding that the risk of spillover is highest at intermediate levels of habitat loss provides important guidance for conservation and public health policy.

Going through the motions: incorporating movement analyses into disease research - Eric R. Dougherty; Dana P. Seidel; Colin J. Carlson; Orr Spiegel; Wayne M. Getz (Ecology Letters, 2018)
Though epidemiology dates back to the 1700s, most mathematical representations of epidemics still use transmission rates averaged at the population scale, especially for wildlife diseases. In simplifying the contact process, we ignore the heterogeneities in host movements that complicate the real world, and overlook their impact on spatiotemporal patterns of disease burden. Movement ecology offers a set of tools that help unpack the transmission process, letting researchers more accurately model how animals within a population interact and spread pathogens. Analytical techniques from this growing field can also help expose the reverse process: how infection impacts movement behaviours, and therefore other ecological processes like feeding, reproduction, and dispersal. Here, we synthesise the contributions of movement ecology in disease research, with a particular focus on studies that have successfully used movement‐based methods to quantify individual heterogeneity in exposure and transmission risk. Throughout, we highlight the rapid growth of both disease and movement ecology and comment on promising but unexplored avenues for research at their overlap. Ultimately, we suggest, including movement empowers ecologists to pose new questions, expanding our understanding of host–pathogen dynamics and improving our predictive capacity for wildlife and even human diseases.

Pyrodiversity interacts with rainfall to increase bird and mammal richness in African savannas - Colin M. Beale; Colin J. Courtney Mustaphi; Thomas A. Morrison; Sally Archibald; T. Michael Anderson; Andrew P. Dobson; Jason E. Donaldson; Gareth P. Hempson; James Probert; Catherine L. Parr (Ecology Letters, 2018)
Fire is a fundamental process in savannas and is widely used for management. Pyrodiversity, variation in local fire characteristics, has been proposed as a driver of biodiversity although empirical evidence is equivocal. Using a new measure of pyrodiversity (Hempson et al .), we undertook the first continent‐wide assessment of how pyrodiversity affects biodiversity in protected areas across African savannas. The influence of pyrodiversity on bird and mammal species richness varied with rainfall: strongest support for a positive effect occurred in wet savannas (> 650 mm/year), where species richness increased by 27% for mammals and 40% for birds in the most pyrodiverse regions. Range‐restricted birds were most increased by pyrodiversity, suggesting the diversity of fire regimes increases the availability of rare niches. Our findings are significant because they explain the conflicting results found in previous studies of savannas. We argue that managing savanna landscapes to increase pyrodiversity is especially important in wet savannas.

C 4 photosynthesis evolved in warm climates but promoted migration to cooler ones - Teera Watcharamongkol; Pascal‐Antoine Christin; Colin P. Osborne (Ecology Letters, 2018)
C 4 photosynthesis is considered an adaptation to warm climates, where its functional benefits are greatest and C 4 plants achieve their highest diversity and dominance. However, whether inherent physiological barriers impede the persistence of C 4 species in cool environments remains debated. Here, we use large grass phylogenetic and geographical distribution data sets to test whether (1) temperature influences the rate of C 4 origins, (2) photosynthetic types affect the rate of migration among climatic zones, and (3) C 4 evolution changes the breadth of the temperature niche. Our analyses show that C 4 photosynthesis in grasses originated in tropical climates, and that C 3 grasses were more likely to colonise cold climates. However, migration rates among tropical and temperate climates were higher in C 4 grasses. Therefore, while the origins of C 4 photosynthesis were concentrated in tropical climates, its physiological benefits across a broad temperature range expanded the niche into warmer climates and enabled diversification into cooler environments.

Geographically distributed hybrid testing & collaboration between geotechnical centrifuge and structures laboratories - Mobin Ojaghi; Ignacio Lamata Martínez; Matt S. Dietz; Martin S. Williams; Anthony Blakeborough; Adam J. Crewe; Colin A. Taylor; S. P. Gopal Madabhushi; Stuart K. Haigh (Earthquake Engineering and Engineering Vibration, 2018)

Resilience in moving water: Effects of turbulence on the predatory impact of the lobate ctenophore Mnemiopsis leidyi - Cornelia Jaspers; John H. Costello; Kelly R. Sutherland; Brad Gemmell; Kelsey N. Lucas; Jennifer Tackett; Kara Dodge; Sean P. Colin (Limnology and Oceanography, 2018)
Despite its delicate morphology, the lobate ctenophore Mnemiopsis leidyi thrives in coastal ecosystems as an influential zooplankton predator. Coastal ecosystems are often characterized as energetic systems with high levels of natural turbulence in the water column. To understand how natural wind‐driven turbulence affects the feeding ecology of M. leidyi , we used a combination of approaches to quantify how naturally and laboratory generated turbulence affects the behavior, feeding processes and feeding impact of M. leidyi . Experiments using laboratory generated turbulence demonstrated that turbulence can reduce M. leidyi feeding rates on copepods and Artemia nauplii by > 50%. However, detailed feeding data from the field, collected during highly variable surface conditions, showed that wind‐driven turbulence did not affect the feeding rates or prey selection of M. leidyi . Additional laboratory experiments and field observations suggest that the feeding process of M. leidyi is resilient to wind‐driven turbulence because M. leidyi shows a behavioral response to turbulence by moving deeper in the water column. Seeking refuge in deeper waters enables M. leidyi to maintain high feeding rates even under high turbulence conditions generated by wind driven mixing. As a result, M. leidyi exerted a consistently high predatory impact on prey populations during highly variable and often energetic wind‐driven mixing conditions. This resilience adds to our understanding of how M. leidyi can thrive in a wide spectrum of environments around the world. The limits to this resilience also set boundaries to its range expansion into novel areas.

Using growth rates to estimate age of the sea turtle barnacle Chelonibia testudinaria - Sophie A. Doell; Rod M. Connolly; Colin J. Limpus; Ryan M. Pearson; Jason P. van de Merwe (Marine Biology, 2017)

Species definitions and conservation: a review and case studies from African mammals - Colin P. Groves; F. P. D. Cotterill; Spartaco Gippoliti; Jan Robovský; Christian Roos; Peter J. Taylor; Dietmar Zinner (Conservation Genetics, 2017)

Mapping of mangrove extent and zonation using high and low tide composites of Landsat data - Kerrylee Rogers; Leo Lymburner; Rafaela Salum; Brendan P. Brooke; Colin D. Woodroffe (Hydrobiologia, 2017)

Exposure to predators reduces collective foraging aggressiveness and eliminates its relationship with colony personality composition - Colin M. Wright; James L. L. Lichtenstein; Graham A. Montgomery; Lauren P. Luscuskie; Noa Pinter-Wollman; Jonathan N. Pruitt (Behavioral Ecology and Sociobiology, 2017)

The transcriptional landscape of seasonal coat colour moult in the snowshoe hare - Mafalda S. Ferreira; Paulo C. Alves; Colin M. Callahan; João P. Marques; L. Scott Mills; Jeffrey M. Good; José Melo‐Ferreira (Molecular Ecology, 2017)
Seasonal coat colour change is an important adaptation to seasonally changing environments but the evolution of this and other circannual traits remains poorly understood. In this study, we use gene expression to understand seasonal coat colour moulting in wild snowshoe hares ( Lepus americanus ). We used hair colour to follow the progression of the moult, simultaneously sampling skin from three moulting stages in hares collected during the peak of the spring moult from white winter to brown summer pelage. Using RNA sequencing, we tested whether patterns of expression were consistent with predictions based on the established phases of the hair growth cycle. We found functionally consistent clustering across skin types, with 766 genes differentially expressed between moult stages. “White” pelage showed more differentially expressed genes that were upregulated relative to other skin types, involved in the transition between late telogen (quiescent stage) and the onset of anagen (proliferative stage). Skin samples from transitional “intermediate” and “brown” pelage were transcriptionally similar and resembled the regressive transition to catagen (regressive stage). We also detected differential expression of several key circadian clock and pigmentation genes, providing important means to dissect the bases of alternate seasonal colour morphs. Our results reveal that pelage colour is a useful biomarker for seasonal change but that there is a consistent lag between the main gene expression waves and change in visible coat colour. These experiments establish that developmental sampling from natural populations of nonmodel organisms can provide a crucial resource to dissect the genetic basis and evolution of complex seasonally changing traits.

Photochemically Controlled Drug Dosing from a Polymeric Scaffold - Louise Donnelly; John G. Hardy; Sean P. Gorman; David S. Jones; Nicola J. Irwin; Colin P. McCoy (Pharmaceutical Research, 2017)

Does Resource Availability Affect the Diet and Behavior of the Vulnerable Squirrel Monkey, Saimiri vanzolinii? - Fernanda P. Paim; Colin A. Chapman; Helder L. de Queiroz; Adriano P. Paglia (International Journal of Primatology, 2017)

Effects of Inundation by the 14th November, 2016 Kaikōura Tsunami on Banks Peninsula, Canterbury, New Zealand - Emily M. Lane; Jose Borrero; Colin N. Whittaker; Jo Bind; Catherine Chagué-Goff; James Goff; Derek Goring; Jo Hoyle; Christof Mueller; William L. Power; Catherine M. Reid; James H. Williams; et al. (Pure and Applied Geophysics, 2017)

Assessing conservation risks to populations of an anadromous Arctic salmonid, the northern Dolly Varden (Salvelinus malma malma), via estimates of effective and census population sizes and approximate Bayesian computation - Les N. Harris; Friso P. Palstra; Robert Bajno; Colin P. Gallagher; Kimberly L. Howland; Eric B. Taylor; James D. Reist (Conservation Genetics, 2017)

Hard-shell mating in Neohelice granulata: the role of ecdysone in female receptivity and mate attraction - María P. Sal Moyano; Tomás Luppi; Daniel A. Medesani; Colin L. McLay; Enrique M. Rodríguez (Journal of Comparative Physiology A, 2017)

Yield responses of wild C 3 and C 4 crop progenitors to subambient CO 2 : a test for the role of CO 2 limitation in the origin of agriculture - Jennifer Cunniff; Glynis Jones; Michael Charles; Colin P. Osborne (Global Change Biology, 2017)
Limitation of plant productivity by the low partial pressure of atmospheric CO 2 ( C a ) experienced during the last glacial period is hypothesized to have been an important constraint on the origins of agriculture. In support of this hypothesis, previous work has shown that glacial C a limits vegetative growth in the wild progenitors of both C 3 and C 4 founder crops. Here, we present data showing that glacial C a also reduces grain yield in both crop types. We grew four wild progenitors of C 3 (einkorn wheat and barley) and C 4 crops (foxtail and broomcorn millets) at glacial and postglacial C a , measuring grain yield and the morphological and physiological components contributing to these yield changes. The C 3 species showed a significant increase in unthreshed grain yield of ~50% with the glacial to postglacial increase in C a , which matched the stimulation of photosynthesis, suggesting that increases in photosynthesis are directly translated into yield at subambient levels of C a . Increased yield was controlled by a higher rate of tillering, leading to a larger number of tillers bearing fertile spikes, and increases in seed number and size. The C 4 species showed smaller, but significant, increases in grain yield of 10–15%, arising from larger seed numbers and sizes. Photosynthesis was enhanced by C a in only one C 4 species and the effect diminished during development, suggesting that an indirect mechanism mediated by plant water relations could also be playing a role in the yield increase. Interestingly, the C 4 species at glacial C a showed some evidence that photosynthetic capacity was upregulated to enhance carbon capture. Development under glacial C a also impacted negatively on the subsequent germination and viability of seeds. These results suggest that the grain production of both C 3 and C 4 crop progenitors was limited by the atmospheric conditions of the last glacial period, with important implications for the origins of agriculture.

Lesion recovery and the bacterial microbiome in two Caribbean gorgonian corals - Kartick P. Shirur; Colin R. Jackson; Tamar L. Goulet (Marine Biology, 2016)

Genome biogeography reveals the intraspecific spread of adaptive mutations for a complex trait - Jill K. Olofsson; Matheus Bianconi; Guillaume Besnard; Luke T. Dunning; Marjorie R. Lundgren; Helene Holota; Maria S. Vorontsova; Oriane Hidalgo; Ilia J. Leitch; Patrik Nosil; Colin P. Osborne; Pascal‐Antoine Christin (Molecular Ecology, 2016)
Physiological novelties are often studied at macro‐evolutionary scales such that their micro‐evolutionary origins remain poorly understood. Here, we test the hypothesis that key components of a complex trait can evolve in isolation and later be combined by gene flow. We use C 4 photosynthesis as a study system, a derived physiology that increases plant productivity in warm, dry conditions. The grass Alloteropsis semialata includes C 4 and non‐C 4 genotypes, with some populations using laterally acquired C 4 ‐adaptive loci, providing an outstanding system to track the spread of novel adaptive mutations. Using genome data from C 4 and non‐C 4 A. semialata individuals spanning the species’ range, we infer and date past migrations of different parts of the genome. Our results show that photosynthetic types initially diverged in isolated populations, where key C 4 components were acquired. However, rare but recurrent subsequent gene flow allowed the spread of adaptive loci across genetic pools. Indeed, laterally acquired genes for key C 4 functions were rapidly passed between populations with otherwise distinct genomic backgrounds. Thus, our intraspecific study of C 4 ‐related genomic variation indicates that components of adaptive traits can evolve separately and later be combined through secondary gene flow, leading to the assembly and optimization of evolutionary innovations.

Prey capture by the cosmopolitan hydromedusae, Obelia spp., in the viscous regime - Kelly R. Sutherland; Brad J. Gemmell; Sean P. Colin; John H. Costello (Limnology and Oceanography, 2016)

Paradigms for parasite conservation - Eric R. Dougherty; Colin J. Carlson; Veronica M. Bueno; Kevin R. Burgio; Carrie A. Cizauskas; Christopher F. Clements; Dana P. Seidel; Nyeema C. Harris (Conservation Biology, 2016)
Parasitic species, which depend directly on host species for their survival, represent a major regulatory force in ecosystems and a significant component of Earth's biodiversity. Yet the negative impacts of parasites observed at the host level have motivated a conservation paradigm of eradication, moving us farther from attainment of taxonomically unbiased conservation goals. Despite a growing body of literature highlighting the importance of parasite‐inclusive conservation, most parasite species remain understudied, underfunded, and underappreciated. We argue the protection of parasitic biodiversity requires a paradigm shift in the perception and valuation of their role as consumer species, similar to that of apex predators in the mid‐20th century. Beyond recognizing parasites as vital trophic regulators, existing tools available to conservation practitioners should explicitly account for the unique threats facing dependent species. We built upon concepts from epidemiology and economics (e.g., host‐density threshold and cost‐benefit analysis) to devise novel metrics of margin of error and minimum investment for parasite conservation. We define margin of error as the risk of accidental host extinction from misestimating equilibrium population sizes and predicted oscillations, while minimum investment represents the cost associated with conserving the additional hosts required to maintain viable parasite populations. This framework will aid in the identification of readily conserved parasites that present minimal health risks. To establish parasite conservation, we propose an extension of population viability analysis for host–parasite assemblages to assess extinction risk. In the direst cases, ex situ breeding programs for parasites should be evaluated to maximize success without undermining host protection. Though parasitic species pose a considerable conservation challenge, adaptations to conservation tools will help protect parasite biodiversity in the face of an uncertain environmental future.

A comparison of different structures and methods for estimating age of northern-form Dolly Varden Salvelinus malma malma from the Canadian Arctic - Colin P. Gallagher; Kimberly L. Howland; Rick J. Wastle (Polar Biology, 2016)

Dietary shift in juvenile coral trout (Plectropomus maculatus) following coral reef degradation from a flood plume disturbance - Colin K. C. Wen; Mary C. Bonin; Hugo B. Harrison; David H. Williamson; Geoffrey P. Jones (Coral Reefs, 2016)

What have we learnt from palaeoclimate simulations? - Sandy P. Harrison; Patrick J. Bartlein; I. Colin Prentice (Journal of Quaternary Science, 2016)
There has been a gradual evolution in the way that palaeoclimate modelling and palaeoenvironmental data are used together to understand how the Earth System works, from an initial and largely descriptive phase through explicit hypothesis testing to diagnosis of underlying mechanisms. Analyses of past climate states are now regarded as integral to the evaluation of climate models, and have become part of the toolkit used to assess the likely realism of future projections. Palaeoclimate assessment has demonstrated that changes in large‐scale features of climate that are governed by the energy and water balance show consistent responses to changes in forcing in different climate states, and these consistent responses are reproduced by climate models. However, state‐of‐the‐art models are still largely unable to reproduce observed changes in climate at a regional scale reliably. While palaeoclimate analyses of state‐of‐the‐art climate models suggest an urgent need for model improvement, much work is also needed on extending and improving palaeoclimate reconstructions and quantifying and reducing both numerical and interpretative uncertainties.

Remembering Jerry Lwanga: A Perspective from His Colleagues - Tony L. Goldberg; Samuel Angedakin; Gilbert M. Isabirye Basuta; Michelle Brown; Thomas M. Butynski; Colin A. Chapman; Lauren Chapman; Sholly Gunter; Innocent Kato; Jean-Michel Krief; Sabrina Krief; Joanna E. Lambert; et al. (International Journal of Primatology, 2016)

Drones as tools for monitoring beach topography changes in the Ligurian Sea (NW Mediterranean) - Elisa Casella; Alessio Rovere; Andrea Pedroncini; Colin P. Stark; Marco Casella; Marco Ferrari; Marco Firpo (Geo-Marine Letters, 2016)

Development and applications of a DNA labeling method with magnetic nanoparticles to study the role of horizontal gene transfer events between bacteria in soil pollutant bioremediation processes - J. Pivetal; M. Frénéa-Robin; N. Haddour; C. Vézy; L. F. Zanini; G. Ciuta; N. M. Dempsey; F. Dumas-Bouchiat; G. Reyne; S. Bégin-Colin; D. Felder-Flesh; C. Ghobril; et al. (Environmental Science and Pollution Research, 2015)

Variation in the post‐copulatory guarding behavior of Neohelice granulata (Brachyura, Grapsoidea, Varunidae) in two different habitats - María P. Sal Moyano; María A. Gavio; Colin L. McLay; Tomás Luppi (Marine Ecology, 2015)
Crab guarding behaviors are influenced by the biological and physical characteristics that each population experiences in a particular habitat. We studied post‐copulatory guarding behavior and the factors affecting it, such as the presence of burrows, female receptivity duration, operational sex ratio ( OSR ) and male size, in two different populations of Neohelice granulata : Mar Chiquita coastal lagoon ( MCL ) and San Antonio Oeste ( SAO ). Laboratory experiments showed that post‐copulatory guarding duration varied between the study areas. In MCL , it depended upon the presence of burrows and female receptivity duration, whereas it was independent of the OSR and male size. In SAO , it was dependent upon the OSR and female receptivity duration, whereas it was independent of the presence of burrows and male size. Thus, N . granulata males display different reproductive strategies related to their post‐copulatory guarding behavior pattern in different habitats. These strategies are related to the fact that this species constructs and defends a burrow that provides shelter and a place to mate, something that other varunids do not have.

Photosynthetic innovation broadens the niche within a single species - Marjorie R. Lundgren; Guillaume Besnard; Brad S. Ripley; Caroline E. R. Lehmann; David S. Chatelet; Ralf G. Kynast; Mary Namaganda; Maria S. Vorontsova; Russell C. Hall; John Elia; Colin P. Osborne; Pascal‐Antoine Christin (Ecology Letters, 2015)
Adaptation to changing environments often requires novel traits, but how such traits directly affect the ecological niche remains poorly understood. Multiple plant lineages have evolved C 4 photosynthesis, a combination of anatomical and biochemical novelties predicted to increase productivity in warm and arid conditions. Here, we infer the dispersal history across geographical and environmental space in the only known species with both C 4 and non‐C 4 genotypes, the grass Alloteropsis semialata . While non‐C 4 individuals remained confined to a limited geographic area and restricted ecological conditions, C 4 individuals dispersed across three continents and into an expanded range of environments, encompassing the ancestral one. This first intraspecific investigation of C 4 evolutionary ecology shows that, in otherwise similar plants, C 4 photosynthesis does not shift the ecological niche, but broadens it, allowing dispersal into diverse conditions and over long distances. Over macroevolutionary timescales, this immediate effect can be blurred by subsequent specialisation towards more extreme niches.

An assessment of age and growth of violet cod (Antimora rostrata) in the Ross Sea, Antarctica - Peter L. Horn; Colin P. Sutton (Polar Biology, 2015)

Winter feeding ecology and the importance of cannibalism in juvenile and adult burbot (Lota lota) from the Mackenzie Delta, Canada - Colin P. Gallagher; Terry A. Dick (Hydrobiologia, 2015)

A recessive homozygous p.Asp92Gly SDHD mutation causes prenatal cardiomyopathy and a severe mitochondrial complex II deficiency - Charlotte L. Alston; Camilla Ceccatelli Berti; Emma L. Blakely; Monika Oláhová; Langping He; Colin J. McMahon; Simon E. Olpin; Iain P. Hargreaves; Cecilia Nolli; Robert McFarland; Paola Goffrini; Maureen J. O’Sullivan; et al. (Human Genetics, 2015)

Botanic gardens can positively influence visitors’ environmental attitudes - Sophie J. Williams; Julia P. G. Jones; James M. Gibbons; Colin Clubbe (Biodiversity and Conservation, 2015)

MAGIC populations in crops: current status and future prospects - B. Emma Huang; Klara L. Verbyla; Arunas P. Verbyla; Chitra Raghavan; Vikas K. Singh; Pooran Gaur; Hei Leung; Rajeev K. Varshney; Colin R. Cavanagh (Theoretical and Applied Genetics, 2015)

Climate-driven changes in lakes from the Peruvian Andes - Neal Michelutti; Colin A. Cooke; William O. Hobbs; John P. Smol (Journal of Paleolimnology, 2015)

Cross-fostering by foreign conspecific queens and slave-making workers influences individual- and colony-level personality - Carl N. Keiser; Colin M. Wright; Nishant Singh; Joseph A. DeShane; Andreas P. Modlmeier; Jonathan N. Pruitt (Behavioral Ecology and Sociobiology, 2015)

Biogeographically distinct controls on C 3 and C 4 grass distributions: merging community and physiological ecology - Daniel M. Griffith; T. Michael Anderson; Colin P. Osborne; Caroline A. E. Strömberg; Elisabeth J. Forrestel; Christopher J. Still (Global Ecology and Biogeography, 2015)
Aim C 4 photosynthesis is an adaptation that maintains efficient carbon assimilation in high‐light, high‐temperature conditions. Due to the importance of C 4 grasses for carbon and surface energy fluxes, numerous models have been proposed to describe their spatial distribution and forecast their responses to climate change. These models often rely on broad climatic predictors (e.g. temperature and precipitation) but fail to integrate other ecologically relevant factors like disturbance and competition, which may modify realized C 3 / C 4 grass distributions. Here, we present a combined evaluation of the contribution of ecological factors and climatic predictors to realized C 3 / C 4 grass distributions. We consider multiple biogeographic regions of N orth A merica using a multisource database of over 40,000 vegetation plots. Location The conterminous U nited S tates of A merica ( USA ). Methods We identified a comprehensive pool of climatic models in the literature and used information theoretic criteria to select a primary climatic predictor of C 3 and C 4 grass distributions. Subsequently, the best model was combined with ecological predictors (e.g. fire, tree cover) using a multiple regression framework and tested within eight regions. Results Surprisingly, grass‐dominated communities across the USA exist largely in C 3 ‐ or C 4 ‐dominated states. Transitions between C 3 / C 4 dominance were best explained by models that integrated temperature and precipitation with ecological factors that varied according to region. For some regions, like E astern T emperate F orests, local ecological factors were comparable in strength to broad‐scale climatic predictors of C 3 / C 4 abundance. Main conclusion Local ecological factors modify C 3 / C 4 grass responses to broad‐scale climatic drivers in ways that manifest at regional scales. In E astern T emperate F orests, for example, C 4 grass abundances are maintained below climatic expectations where tree cover creates light limitation but above expectations where frequent fires reduce tree cover. Thus, local ecological factors, which vary among biogeographic regions, contribute to large‐scale climate disequilibrium.

Beaver-mediated methane emission: The effects of population growth in Eurasia and the Americas - Colin J. Whitfield; Helen M. Baulch; Kwok P. Chun; Cherie J. Westbrook (Ambio, 2015)

Mapping and quantification of planted tree and shrub shelterbelts in Saskatchewan, Canada - Beyhan Y. Amichev; Murray J. Bentham; Darrel Cerkowniak; John Kort; Suren Kulshreshtha; Colin P. Laroque; Joseph M. Piwowar; Ken C. J. Van Rees (Agroforestry Systems, 2015)

Connectivity of wood thrush breeding, wintering, and migration sites based on range‐wide tracking - Calandra Q. Stanley; Emily A. McKinnon; Kevin C. Fraser; Maggie P. Macpherson; Garth Casbourn; Lyle Friesen; Peter P. Marra; Colin Studds; T. Brandt Ryder; Nora E. Diggs; Bridget J. M. Stutchbury (Conservation Biology, 2015)
Many migratory animals are experiencing rapid population declines, but migration data with the geographic scope and resolution to quantify the complex network of movements between breeding and nonbreeding regions are often lacking. Determining the most frequently used migration routes and nonbreeding regions for a species is critical for understanding population dynamics and making effective conservation decisions. We tracked the migration of individual Wood Thrushes (Hylocichla mustelina) (n = 102) from across their range with light‐level geolocators and, for the first time, quantified migration routes and wintering regions for distinct breeding populations. We identified regional and species‐level migratory connectivity networks for this declining songbird by combining our tracking results with range‐wide breeding abundance estimates and forest cover data. More than 50% of the species occupied the eastern wintering range (Honduras to Costa Rica), a region that includes only one‐third of all wintering habitat and that is undergoing intensive deforestation. We estimated that half of all Wood Thrushes in North America migrate south through Florida in fall, whereas in spring approximately 73% funnel northward through a narrow span along the central U.S. Gulf Coast (88–93°W). Identifying migratory networks is a critical step for conservation of songbirds and we demonstrated with Wood Thrushes how it can highlight conservation hotspots for regional populations and species as a whole. Conectividad de Sitios de Reproducción, Invierno y Migración del Zorzal con Base en Rastreo de Cobertura Amplia

Big and aerial invaders: dominance of exotic spiders in burned New Zealand tussock grasslands - Jagoba Malumbres-Olarte; Barbara I. P. Barratt; Cor J. Vink; Adrian M. Paterson; Robert H. Cruickshank; Colin M. Ferguson; Diane M. Barton (Biological Invasions, 2014)

Landscape scale impacts of culling upon a European grey squirrel population: can trapping reduce population size and decrease the threat of squirrelpox virus infection for the native red squirrel? - Pia Schuchert; Craig M. Shuttleworth; Colin J. McInnes; David. J. Everest; Steven P. Rushton (Biological Invasions, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

A compendium of cell and natural unit biovolumes for >1200 freshwater phytoplankton species - Colin T. Kremer; Jacob P. Gillette; Lars G. Rudstam; Pål Brettum; Robert Ptacnik (Ecology, 2014)
Cell size determination is a critical part of sampling phytoplankton communities, as size is both a fundamental trait determining species' ecological niches and a quantity necessary for generating unbiased estimates of community composition. The sizes of algal cells span orders of magnitude, driving variation in growth parameters, sinking rates, herbivore defense, and biogeochemical roles. Size variation occurs at both intra‐ and interspecific levels. Many central questions in community and ecosystem ecology require estimating and comparing the relative abundances of species. Cell counts provide insufficient estimates, due to interspecific variation in cell size, as they over‐estimate the importance of abundant, small species. While cell size (or biovolume) estimation has become standard practice in limnology, many older data sets lack this information, limiting their interpretation and utility. To address these challenges, and advance the study of freshwater phytoplankton communities, we have compiled a database of >260 000 algal biovolume estimates, spanning ∼400 genera and ∼1200 species. This represents the most extensive, standardized, and taxonomically diverse data set of its kind, drawing on both publicly and privately held sources. Estimates of the sizes of colonies or filaments are included, where applicable. With these data researchers will be able to account for intra‐ and interspecific variation in cell size, enabling new and improved analyses of classic data sets.

Whole-genome QTL analysis for MAGIC - Arūnas P. Verbyla; Andrew W. George; Colin R. Cavanagh; Klara L. Verbyla (Theoretical and Applied Genetics, 2014)

Endospore surface properties of commonly used Bacillus anthracis surrogates vary in aqueous solution - Colin P. White; Jonathan Popovici; Darren A. Lytle; Eugene W. Rice (Antonie van Leeuwenhoek, 2014)

Scientific Correspondence - Colin P. Groves; M. M. Bahir (Marine Mammal Science, 2014)

Detection of Mycobacterium avium subspecies paratuberculosis in patients with Crohn’s disease is unrelated to the presence of single nucleotide polymorphisms rs2241880 (ATG16L1) and rs10045431 (IL12B) - James P. Dalton; Alan Desmond; Fergus Shanahan; Colin Hill (Medical Microbiology and Immunology, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Physiological advantages of C 4 grasses in the field: a comparative experiment demonstrating the importance of drought - Samuel H. Taylor; Brad S. Ripley; Tarryn Martin; Leigh‐Ann De‐Wet; F. Ian Woodward; Colin P. Osborne (Global Change Biology, 2014)

Oligoamides of 2-amino-5-alkylthiazole 4-carboxylic acids: anti-trypanosomal compounds - Stuart Lang; Abedawn I. Khalaf; David Breen; Judith K. Huggan; Carol J. Clements; Simon P. MacKay; Colin J. Suckling (Medicinal Chemistry Research, 2014)

Microbial diversity in Los Azufres geothermal field (Michoacán, Mexico) and isolation of representative sulfate and sulfur reducers - Elcia M. S. Brito; Norberto Villegas-Negrete; Irene A. Sotelo-González; César A. Caretta; Marisol Goñi-Urriza; Claire Gassie; Florence Hakil; Yannick Colin; Robert Duran; Felix Gutiérrez-Corona; Hilda A. Piñón-Castillo; Germán Cuevas-Rodríguez; et al. (Extremophiles, 2014)

Mechanisms driving an unusual latitudinal diversity gradient for grasses - Vernon Visser; W. Derek Clayton; David A. Simpson; Robert P. Freckleton; Colin P. Osborne (Global Ecology and Biogeography, 2014)
Aim For most higher‐order taxa, species diversity peaks sharply in the moist tropics and declines rapidly at higher latitudes. However, the mechanisms driving this latitudinal gradient are numerous, remain uncertain and are even undocumented in some important major clades such as the grasses. Grasses are a cosmopolitan, important plant family with more than 11,000 species world‐wide. Our aims were: to investigate the latitudinal distributions of species richness for different grass lineages, and the grass family as a whole; and to test hypotheses proposed in general for the latitudinal diversity gradient or specifically as determinants of grass species richness patterns at the global scale. Location Global. Methods We used the most comprehensive global database of grass distributions currently available to calculate species richness for 340 political regions of the world. Using generalized additive models we used these data to model the latitudinal gradients of species richness for different grass lineages and for the grass family as a whole. We constructed multiple regression models to include climatic, productivity, topographic, habitat and geographic variables. Results An unusual, shallow latitudinal diversity gradient arises because different grass lineages exhibit contrasting latitudinal patterns. This reflects differential specialization of grass lineages to arid and cool environments, the legacy of historical effects, most notably the Gondwanan origin of the grasses, and a strong association between grasses and topographically heterogeneous, mountainous regions. Main conclusions The grasses are one of the relatively few higher‐order lineages that exhibits an atypical latitudinal gradient; this has arisen because of climatic specialization of particular grass lineages to cold and arid environments. Key additional roles have been inferred for historical biogeography and topographical heterogeneity in determining global patterns of grass species richness. These mechanisms have generally been under‐appreciated and are probably important for many other lineages.

The recurrent assembly of C4 photosynthesis, an evolutionary tale - Pascal-Antoine Christin; Colin P. Osborne (Photosynthesis Research, 2013)

The involvement of gibberellin signalling in the effect of soil resistance to root penetration on leaf elongation and tiller number in wheat - Mauricio A. Coelho Filho; Ellen H. Colebrook; David P. A. Lloyd; Colin P. Webster; Sacha J. Mooney; Andrew L. Phillips; Peter Hedden; William R. Whalley (Plant and Soil, 2013)

Making decisions to conserve species under climate change - Luke P. Shoo; Ary A. Hoffmann; Stephen Garnett; Robert L. Pressey; Yvette M. Williams; Martin Taylor; Lorena Falconi; Colin J. Yates; John K. Scott; Diogo Alagador; Stephen E. Williams (Climatic Change, 2013)

Winter rainfall predicts phenology in widely separated populations of a migrant songbird - Ann E. McKellar; Peter P. Marra; Susan J. Hannon; Colin E. Studds; Laurene M. Ratcliffe (Oecologia, 2013)

Evaluating the suitability of nine shelterbelt species for dendrochronological purposes in the Canadian Prairies - Emma L. Davis; Colin P. Laroque; Ken Van Rees (Agroforestry Systems, 2013)

Forest water use and water use efficiency at elevated CO 2 : a model‐data intercomparison at two contrasting temperate forest FACE sites - Martin G. De Kauwe; Belinda E. Medlyn; Sönke Zaehle; Anthony P. Walker; Michael C. Dietze; Thomas Hickler; Atul K. Jain; Yiqi Luo; William J. Parton; I. Colin Prentice; Benjamin Smith; Peter E. Thornton; et al. (Global Change Biology, 2013)
Predicted responses of transpiration to elevated atmospheric CO 2 concentration ( eCO 2 ) are highly variable amongst process‐based models. To better understand and constrain this variability amongst models, we conducted an intercomparison of 11 ecosystem models applied to data from two forest free‐air CO 2 enrichment ( FACE ) experiments at Duke University and Oak Ridge National Laboratory. We analysed model structures to identify the key underlying assumptions causing differences in model predictions of transpiration and canopy water use efficiency. We then compared the models against data to identify model assumptions that are incorrect or are large sources of uncertainty. We found that model‐to‐model and model‐to‐observations differences resulted from four key sets of assumptions, namely (i) the nature of the stomatal response to elevated CO 2 (coupling between photosynthesis and stomata was supported by the data); (ii) the roles of the leaf and atmospheric boundary layer (models which assumed multiple conductance terms in series predicted more decoupled fluxes than observed at the broadleaf site); (iii) the treatment of canopy interception (large intermodel variability, 2–15%); and (iv) the impact of soil moisture stress (process uncertainty in how models limit carbon and water fluxes during moisture stress). Overall, model predictions of the CO 2 effect on WUE were reasonable (intermodel μ = approximately 28% ± 10%) compared to the observations (μ = approximately 30% ± 13%) at the well‐coupled coniferous site (Duke), but poor (intermodel μ = approximately 24% ± 6%; observations μ = approximately 38% ± 7%) at the broadleaf site (Oak Ridge). The study yields a framework for analysing and interpreting model predictions of transpiration responses to eCO 2 , and highlights key improvements to these types of models.

A study into the sexual dimorphisms of the Ampullae of Lorenzini in the lesser-spotted catshark, Scyliorhinus canicula (Linnaeus, 1758) - Neil Crooks; Colin P. Waring (Environmental Biology of Fishes, 2013)

Infection-Responsive Drug Delivery from Urinary Biomaterials Controlled by a Novel Kinetic and Thermodynamic Approach - Nicola J. Irwin; Colin P. McCoy; David S. Jones; Sean P. Gorman (Pharmaceutical Research, 2013)

Photosynthetic acclimation and resource use by the C 3 and C 4 subspecies of A lloteropsis semialata in low CO 2 atmospheres - Brad S. Ripley; Jennifer Cunniff; Colin P. Osborne (Global Change Biology, 2013)
During the past 25 Myr, partial pressures of atmospheric CO 2 ( C a ) imposed a greater limitation on C 3 than C 4 photosynthesis. This could have important downstream consequences for plant nitrogen economy and biomass allocation. Here, we report the first phylogenetically controlled comparison of the integrated effects of subambient C a on photosynthesis, growth and nitrogen allocation patterns, comparing the C 3 and C 4 subspecies of A lloteropsis semialata . Plant size decreased more in the C 3 than C 4 subspecies at low C a , but nitrogen pool sizes were unchanged, and nitrogen concentrations increased across all plant partitions. The C 3, but not C 4 subspecies, preferentially allocated biomass to leaves and increased specific leaf area at low C a . In the C 3 subspecies, increased leaf nitrogen was linked to photosynthetic acclimation at the interglacial C a , mediated via higher photosynthetic capacity combined with greater stomatal conductance. Glacial C a further increased the biochemical acclimation and nitrogen concentrations in the C 3 subspecies, but these were insufficient to maintain photosynthetic rates. In contrast, the C 4 subspecies maintained photosynthetic rates, nitrogen‐ and water‐use efficiencies and plant biomass at interglacial and glacial C a with minimal physiological adjustment. At low C a , the C 4 carbon‐concentrating mechanism therefore offered a significant advantage over the C 3 type for carbon acquisition at the whole‐plant scale, apparently mediated via nitrogen economy and water loss. A limiting nutrient supply damped the biomass responses to C a and increased the C 4 advantage across all C a treatments. Findings highlight the importance of considering leaf responses in the context of the whole plant, and show that carbon limitation may be offset at the expense of greater plant demand for soil resources such as nitrogen and water. Results show that the combined effects of low CO 2 and resource limitation benefit C 4 plants over C 3 plants in glacial–interglacial environments, but that this advantage is lessened under anthropogenic conditions.

Bayesian modelling the retreat of the Irish Sea Ice Stream - Richard C. Chiverrell; Ian M. Thrasher; Geoffrey S. P. Thomas; Andreas Lang; James D. Scourse; Katrien J. J. van Landeghem; Danny Mccarroll; Chris D. Clark; Colm Ó Cofaigh; David J. A. Evans; Colin K. Ballantyne (Journal of Quaternary Science, 2013)
We present an 8000‐year history spanning 650 km of ice margin retreat for the largest marine‐terminating ice stream draining the former British–Irish Ice Sheet. Bayesian modelling of the geochronological data shows the ISIS expanded 34.0–25.3 ka, accelerating into the Celtic Sea to reach maximum limits 25.3–24.5 ka before a collapse with rapid marginal retreat to the northern Irish Sea Basin (ISB). This retreat was rapid and driven by climatic warming, sea‐level rise, mega‐tidal amplitudes and reactivation of meridional circulation in the North Atlantic. The retreat, though rapid, is uneven, with the stepped retreat pattern possibly a function of the passage of the ice stream between normal and adverse ice bed gradients and changing ice stream geometry. Initially, wide calving margins and adverse slopes encouraged rapid retreat (∼550 m a −1 ) that slowed (∼100 m a −1 ) at the topographic constriction and bathymetric high between southern Ireland and Wales before rates increased (∼200 m a −1 ) across adverse bed slopes and wider and deeper basin configuration in the northern ISB. These data point to the importance of the ice bed slope and lateral extent in predicting the longer‐term (>1000 a) patterns and rates of ice‐marginal retreat during phases of rapid collapse, which has implications for the modelling of projected rapid retreat of present‐day ice streams. Copyright © 2013 John Wiley & Sons, Ltd.

Biofortification of zinc in wheat grain by the application of sewage sludge - Steve P. McGrath; Brian J. Chambers; Matthew J. Taylor; Colin H. Carlton-Smith (Plant and Soil, 2012)

Phylogenetic niche conservatism in C4 grasses - Hui Liu; Erika J. Edwards; Robert P. Freckleton; Colin P. Osborne (Oecologia, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Controlled Nucleation of Lipid Nanoparticles - Juliane Nguyen; Colin L. Walsh; J. P. Michael Motion; Emily K. Perttu; Francis Szoka (Pharmaceutical Research, 2012)

Influence of climate oscillations on dentinal deposition in teeth of Commerson's dolphin - Natalia A. Dellabianca; Aleta A. Hohn; R. Natalie P. Goodall; Jorge L. Pousa; Colin D. MacLeod; Mauricio Lima (Global Change Biology, 2012)
Effects of climatic oscillations on populations in marine environments are produced mainly through the lower trophic levels. Marine mammals, as top predators, are affected indirectly by these fluctuations, showing variations in their survival, growth and reproduction. The main objective of this study was to determine whether we could detect the effect of climatic oscillations on Commerson's dolphins ( Cephalorhynchus c. commersonii ) off Tierra del Fuego, Argentina, by examining the presence and proportion of anomalous dentinal growth layer groups ( GLG s). The relative deposition of anomalous GLG s was determined using calendar years from 1960 to 2005, and related to the Southern Annular Mode ( SAM ) and El Niño Southern Oscillation ( ENSO ) events, and to mean annual sea surface temperatures ( SST ). Then, growth parameters between animals that did and did not show anomalous dentinal growth layer patterns in one or more of their GLG s were compared. The presence of anomalous GLG s was related to the SAM , increasing in frequency with negative values of the SAM . No relationship was found among anomalous GLG s, ENSO , and SST . There were no significant differences in growth parameters between animals with and without anomalous GLG s. Using recording structures such as teeth provided a unique way of reconstructing time series to evaluate the effects of these climatic patterns on a top predator species in an area where no similar studies have been conducted, primarily due to a lack of suitable long‐term data sets.

Predator-induced vertical behavior of a ctenophore - Josefin Titelman; Lars Johan Hansson; Trygve Nilsen; Sean P. Colin; John H. Costello (Hydrobiologia, 2012)

Plant growth rates and seed size: a re‐evaluation - Lindsay A. Turnbull; Christopher D. Philipson; Drew W. Purves; Rebecca L. Atkinson; Jennifer Cunniff; Anne Goodenough; Yann Hautier; Jennie Houghton; Toby R. Marthews; Colin P. Osborne; Cloé Paul-Victor; Karen E. Rose; et al. (Ecology, 2012)
Small‐seeded plant species are often reported to have high relative growth rate or RGR. However, because RGR declines as plants grow larger, small‐seeded species could achieve higher RGR simply by virtue of their small size. In contrast, size‐standardized growth rate or SGR factors out these size effects. Differences in SGR can thus only be due to differences in morphology, allocation, or physiology. We used nonlinear regression to calculate SGR for comparison with RGR for 10 groups of species spanning a wide range of life forms. We found that RGR was negatively correlated with seed mass in nearly all groups, but the relationship between SGR and seed mass was highly variable. We conclude that small‐seeded species only sometimes possess additional adaptations for rapid growth over and above their general size advantage.

Refugia: identifying and understanding safe havens for biodiversity under climate change - Gunnar Keppel; Kimberly P. Van Niel; Grant W. Wardell‐Johnson; Colin J. Yates; Margaret Byrne; Ladislav Mucina; Antonius G. T. Schut; Stephen D. Hopper; Steven E. Franklin (Global Ecology and Biogeography, 2012)
Aim Identifying and protecting refugia is a priority for conservation under projected anthropogenic climate change, because of their demonstrated ability to facilitate the survival of biota under adverse conditions. Refugia are habitats that components of biodiversity retreat to, persist in and can potentially expand from under changing environmental conditions. However, the study and discussion of refugia has often been ad hoc and descriptive in nature. We therefore: (1) provide a habitat‐based concept of refugia, and (2) evaluate methods for the identification of refugia. Location Global. Methods We present a simple conceptual framework for refugia and examine the factors that describe them. We then demonstrate how different disciplines are contributing to our understanding of refugia, and the tools that they provide for identifying and quantifying refugia. Results Current understanding of refugia is largely based on Quaternary phylogeographic studies on organisms in North America and Europe during significant temperature fluctuations. This has resulted in gaps in our understanding of refugia, particularly when attempting to apply current theory to forecast anthropogenic climate change. Refugia are environmental habitats with space and time dimensions that operate on evolutionary time‐scales and have facilitated the survival of biota under changing environmental conditions for millennia. Therefore, they offer the best chances for survival under climate change for many taxa, making their identification important for conservation under anthropogenic climate change. Several methods from various disciplines provide viable options for achieving this goal. Main conclusions The framework developed for refugia allows the identification and description of refugia in any environment. Various methods provide important contributions but each is limited in scope; urging a more integrated approach to identify, define and conserve refugia. Such an approach will facilitate better understanding of refugia and their capacity to act as safe havens under projected anthropogenic climate change.

An Atlantic infaunal engineer is established in the Northeast Pacific: Clymenella torquata (Polychaeta: Maldanidae) on the British Columbia and Washington Coasts - Megan E. Mach; Colin D. Levings; P. Sean McDonald; Kai M. A. Chan (Biological Invasions, 2012)

Phylogenetic assessment of culture collection strains of Thiobacillus thioparus, and definitive 16S rRNA gene sequences for T. thioparus, T. denitrificans, and Halothiobacillus neapolitanus - Rich Boden; David Cleland; Peter N. Green; Yoko Katayama; Yoshihito Uchino; J. Colin Murrell; Donovan P. Kelly (Archives of Microbiology, 2012)

Environmental factors determining the phylogenetic structure of C 4 grass communities - Vernon Visser; F. Ian Woodward; Rob P. Freckleton; Colin P. Osborne (Journal of Biogeography, 2012)
Aim To determine how the distribution of species richness is associated with environmental factors for the four major C 4 grass lineages in South Africa, as a means to explore the mechanisms responsible. Location South Africa, Lesotho and Swaziland. Methods The geographical distributions of species richness for four major C 4 grass lineages (Aristidoideae, Chloridoideae, Andropogoneae and Paniceae) were sourced from a recently published flora that divided the study region into different vegetation types. Mean values of potential environmental correlates were calculated for each vegetation type, and the relative importances of these were determined using single‐ and multiple‐predictor generalized linear models, with and without control for spatial autocorrelation. Model selection of the multiple‐predictor generalized linear models was conducted using an Akaike’s information criterion–information theoretic approach. Association with wet, intermediate or dry, shady or open, and disturbed or undisturbed habitats was also determined for each C 4 grass clade using habitat data for all the grass species, and analysed using chi‐square tests of independence. Results Andropogoneae and Paniceae are most species‐rich in areas of high precipitation and in mesic habitats. Andropogoneae are associated with high fire frequencies. Species richness in Andropogoneae decreases and in Paniceae increases in relation to livestock density. Chloridoideae species richness is relatively constant across South Africa, but is highest where there are infrequent fires, high temperatures and basic soils, and in mesic and disturbed habitats. Aristidoideae are most species‐rich in arid regions and in habitats with high temperatures, and are associated with disturbed habitats. Main conclusions Environmental variables other than precipitation, including temperature, fire frequency and grazing pressure, are strongly associated with the contrasting distributions of species richness for the various C 4 grass clades in South Africa. Our results suggest that ecological sorting is an important determinant of phylogenetic patterns in the species richness of these C 4 grass lineages.

A radical approach to beating hypoxia: depressed free radical release from heart fibres of the hypoxia-tolerant epaulette shark (Hemiscyllum ocellatum) - Anthony J. R. Hickey; Gillian M. C. Renshaw; Ben Speers-Roesch; Jeffrey G. Richards; Yuxiang Wang; Anthony P. Farrell; Colin J. Brauner (Journal of Comparative Physiology B, 2012)

Why are some biodiversity policies implemented and others ignored? Lessons from the uptake of the Global Strategy for Plant Conservation by botanic gardens - Sophie J. Williams; Julia P. G. Jones; Colin Clubbe; Suzanne Sharrock; James M. Gibbons (Biodiversity and Conservation, 2012)

Contrasting sedimentation rates in Lake Illawarra and St Georges Basin, two large barrier estuaries on the southeast coast of Australia - Craig R. Sloss; Brian G. Jones; Brendan P. Brooke; Henk Heijnis; Colin V. Murray-Wallace (Journal of Paleolimnology, 2011)

Factors affecting survival of Listeria monocytogenes and Listeria innocua in soil samples - Heather P. McLaughlin; Pat G. Casey; Jeni Cotter; Cormac G. M. Gahan; Colin Hill (Archives of Microbiology, 2011)

Expression of the bifunctional Bacillus subtilis TatAd protein in Escherichia coli reveals distinct TatA/B-family and TatB-specific domains - James P. Barnett; Janna Lawrence; Sharon Mendel; Colin Robinson (Archives of Microbiology, 2011)

Estimation of Mussel Population Response to Hydrologic Alteration in a Southeastern U.S. Stream - James T. Peterson; Jason M. Wisniewski; Colin P. Shea; C. Rhett Jackson (Environmental Management, 2011)

Shallow and deep lunge feeding of humpback whales in fjords of the West Antarctic Peninsula - Colin Ware; Ari S. Friedlaender; Douglas P. Nowacek (Marine Mammal Science, 2011)
Humpback whales ( Megaptera novaeangliae ) belong to the class of marine mammals known as rorquals that feed through extraordinarily energetic lunges during which they engulf large volumes of water equal to as much as 70% of their body mass. To understand the kinematics of humpback lunge feeding, we attached high‐resolution digital recording tags incorporating accelerometers, magnetometers, pressure and sound recording to whales feeding on euphausiids in fjords of the West Antarctic Peninsula. Instances of near vertical lunges gave us the unique opportunity to use the signal from the accelerometer to obtain a fine scale record of the body accelerations involved in lunging. We found that lunges contain extreme accelerations reaching 2.5 m/s 2 in certain instances, which are then followed by decelerations. When animals are intensively feeding the inter‐lunge interval is similar for both deep and shallow lunges suggesting a biomechanical constraint on lunges. However, the number of lunges per dive varies from one for shallow feeding (

miRNAs Stem Cell Reprogramming for Neuronal Induction and Differentiation - Claire Perruisseau-Carrier; Marcin Jurga; Nico Forraz; Colin P. McGuckin (Molecular Neurobiology, 2011)

Pre-Colombian Mercury Pollution Associated with the Smelting of Argentiferous Ores in the Bolivian Andes - Colin A. Cooke; Prentiss H. Balcom; Charles Kerfoot; Mark B. Abbott; Alexander P. Wolfe (Ambio, 2011)

Ligand-Binding Mass Spectrometry to Study Biotransformation of Fusion Protein Drugs and Guide Immunoassay Development: Strategic Approach and Application to Peptibodies Targeting the Thrombopoietin Receptor - Michael P. Hall; Colin Gegg; Kenneth Walker; Christopher Spahr; Robert Ortiz; Vimal Patel; Steven Yu; Liana Zhang; Hsieng Lu; Binodh DeSilva; Jean W. Lee (The AAPS Journal, 2010)

MC1R genotype may modify the effect of sun exposure on melanoma risk in the GEM study - Anne Kricker; Bruce K. Armstrong; Chris Goumas; Peter Kanetsky; Richard P. Gallagher; Colin B. Begg; Robert C. Millikan; Terence Dwyer; Stefano Rosso; Loraine D. Marrett; Nancy E. Thomas; Marianne Berwick (Cancer Causes & Control, 2010)

Genetic tools to support the conservation of the endangered smalltooth sawfish, Pristis pectinata - Kevin A. Feldheim; Demian D. Chapman; Colin A. Simpfendorfer; Vincent P. Richards; Mahmood S. Shivji; Tonya R. Wiley; Gregg R. Poulakis; John K. Carlson; Rowena Eng; Skyler Sagarese (Conservation Genetics Resources, 2010)

Oxidation of dimethylsulfide to tetrathionate by Methylophaga thiooxidans sp. nov.: a new link in the sulfur cycle - Rich Boden; Donovan P. Kelly; J. Colin Murrell; Hendrik Schäfer (Environmental Microbiology, 2010)
Summary A new pathway of dimethylsulfide (DMS) metabolism was identified in a novel species of Gammaproteobacteria , Methylophaga thiooxidans sp. nov., in which tetrathionate (S 4 O 6 2− ) was the end‐product of DMS oxidation. Inhibitor evidence indicated that DMS degradation was initiated by demethylation, catalysed by a corrinoid demethylase. Thiosulfate was an intermediate, which was oxidized to tetrathionate by a cytochrome‐linked thiosulfate dehydrogenase. Thiosulfate oxidation was coupled to ATP synthesis, and M. thiooxidans could also use exogenous thiosulfate as an energy source during chemolithoheterotrophic growth on DMS or methanol. Cultures grown on a variety of substrates oxidized thiosulfate, indicating that thiosulfate oxidation was constitutive. The observations have relevance to interactions among sulfur‐metabolizing bacteria in the marine environment. The production of tetrathionate from an organosulfur precursor is previously undocumented and represents a potential step in the biogeochemical sulfur cycle, providing a ‘shunt’ across the cycle.

Resource allocation for efficient environmental management - Michael A. McCarthy; Colin J. Thompson; Cindy Hauser; Mark A. Burgman; Hugh P. Possingham; Melinda L. Moir; Thanawat Tiensin; Marius Gilbert (Ecology Letters, 2010)
Ecology Letters (2010) Abstract Environmental managers must decide how to invest available resources. Researchers have previously determined how to allocate conservation resources among regions, design nature reserves, allocate funding to species conservation programs, design biodiversity surveys and monitoring programs, manage species and invest in greenhouse gas mitigation schemes. However, these issues have not been addressed with a unified theory. Furthermore, uncertainty is prevalent in environmental management, and needs to be considered to manage risks. We present a theory for optimal environmental management, synthesizing previous approaches to the topic and incorporating uncertainty. We show that the theory solves a diverse range of important problems of resource allocation, including distributing conservation resources among the world’s biodiversity hotspots; surveillance to detect the highly pathogenic avian influenza H5N1 virus in Thailand; and choosing survey methods for the insect order Hemiptera. Environmental management decisions are similar to decisions about financial investments, with trade‐offs between risk and reward.

Sponge and dough bread making: genetic and phenotypic relationships with wheat quality traits - Colin R. Cavanagh; Julian Taylor; Oscar Larroque; Neil Coombes; Arunas P. Verbyla; Zena Nath; Ibrahim Kutty; Lynette Rampling; Barbara Butow; Jean-Philippe Ral; Sandor Tomoskozi; Gabor Balazs; et al. (Theoretical and Applied Genetics, 2010)

First record of Skrjabingylus petrowi (Nematode: Metastrongyloidea) in a pine marten Martes martes from Ireland - Peter Stuart; Conall J. Hawkins; D. P. Sleeman; Colin Lawton (European Journal of Wildlife Research, 2010)

The influence of vegetation type, soil properties and precipitation on the composition of soil mite and microbial communities at the landscape scale - Uffe N. Nielsen; Graham H. R. Osler; Colin D. Campbell; David F. R. P. Burslem; René van der Wal (Journal of Biogeography, 2010)
Aim We used a landscape‐scale study of birch invasion onto heather moorland to determine the consistency of changes in vegetation type and soil properties and in the community composition of five soil organism groups. Our aim was to determine whether the degree to which soil organisms respond to natural changes and/or induced changes (e.g. changes in land‐use type and climate) in habitat is consistent across trophic and taxonomic groups in the context of conservation policies for birch woodland and heather moorland. Location Mainland Scotland. Methods We sampled mesostigmatid mites, oribatid mites, fungi, bacteria and archaea in adjacent patches of birch woodland (dominated by Betula pubescens ) and heather moorland (dominated by Calluna vulgaris ) at 12 sites for which annual rainfall ranged between 713 and 2251 mm. Differences in community composition were visualized using non‐metric multidimensional scaling based on Bray–Curtis dissimilarities. The factors contributing to differences between habitats within sites were explored using general linear models and those among sites using redundancy analysis. Results The communities of all groups differed between habitats within sites, but only the oribatid mites and fungi differed consistently between habitats across sites. Within sites, dissimilarity in fungal communities was positively related to the difference in C. vulgaris cover between habitats, whereas dissimilarities in bacteria and archaea were positively related to differences in soil pH and C:N ratio between habitats, respectively. Main conclusions The influence of vegetation type and soil properties differed between groups of soil organisms, albeit in a predictable manner, across the 12 sites. Organisms directly associated with plants (fungi), and organisms with microhabitat and resource preferences (Oribatida) were strongly responsive to changes in habitat type. The response of organisms not directly associated with plants (bacteria, archaea) depended on differences in soil properties, while organisms with less clear microhabitat and resource preferences (Mesostigmata) were not strongly responsive to either vegetation type or soil properties. These results show that it is possible to predict the impact of habitat change on specific soil organisms depending on their ecology. Moreover, the community composition of all groups was related to variation in precipitation within the study area, which shows that external factors, such as those caused by climate change, can have a direct effect on belowground communities.

Geochemical and Sr–O isotopic constraints on magmatic differentiation at Gede Volcanic Complex, West Java, Indonesia - Heather Katherine Handley; Colin G. Macpherson; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2010)

Aggregation and spawning of the humphead wrasse Cheilinus undulatus (Pisces: Labridae): general aspects of spawning behaviour - P. L. Colin (Journal of Fish Biology, 2010)
The humphead wrasse Cheilinus undulatus formed resident spawning aggregations daily after high tide at specific locations along the seaward edge of the Palau barrier reef. The location and extent of one aggregation site remained consistent for 6 years with no physical features distinguishing it from adjacent areas. Spawning was documented most months and probably occurred year round with possible seasonal and lunar variation. Spawning males arrived first at the site, followed by females and potentially small primary males. The aggregation female to male sex ratio was estimated to be between 6:1 and 10:1. A maximum of 15 males and 100–150 females were observed at the site. A male courtship posture with the anal fin pointed, the caudal fin folded down and the dorsal fin folded against the body was maintained while swimming a few metres off the bottom in view of females. When ready to spawn females rose up as the posturing male passed and the pair released gametes in a relatively sedate fashion near the surface along the shelf break. No attempted predation on spawning adults was seen. Egg predation after spawning was uncommon. On days with early to mid‐day high tides the spawning period started 2·0–2·5 h after high tide when the speed of lagoon–ocean tidal currents peaked and lasted c. 1 h. On days with later afternoon high tides, spawning occurred sooner after high tide and before current speeds peaked. Other fishes with planktonic eggs spawned at the site as pairs or small groups in a rough succession after high tide with C. undulatus , the last species to spawn.

Sub-lingual oral fistulas in Sooty Terns (Onychoprion fuscata) - S. James Reynolds; Graham R. Martin; Colin P. Wearn; B. John Hughes (Journal of Ornithology, 2009)

A novel extended family of stromal thioredoxins - Peter Cain; Michael Hall; Wolfgang P. Schröder; Thomas Kieselbach; Colin Robinson (Plant Molecular Biology, 2009)

The type locality of Pan troglodytes vellerosus (Gray, 1862), and implications for the nomenclature of West African chimpanzees - John F. Oates; Colin P. Groves; Paulina D. Jenkins (Primates, 2009)

Lemur Diversity in Madagascar - Russell A. Mittermeier; Jörg U. Ganzhorn; William R. Konstant; Kenneth Glander; Ian Tattersall; Colin P. Groves; Anthony B. Rylands; Andreas Hapke; Jonah Ratsimbazafy; Mireya I. Mayor; Edward E. Louis; Yves Rumpler; et al. (International Journal of Primatology, 2008)

Glasgow Lake: an early-warning sentinel of lake acidification in Cape Breton Highlands National Park (Nova Scotia, Canada) - Alexandra M. Gerber; Brian K. Ginn; Colin J. Whitfield; Peter J. Dillon; Brian F. Cumming; John P. Smol (Hydrobiologia, 2008)

Plasma vitamins E and A and risk of bladder cancer: a case–control analysis - Dong Liang; Jie Lin; H. Barton Grossman; Jing Ma; Bo Wei; Colin P. Dinney; Xifeng Wu (Cancer Causes & Control, 2008)

Revealing the uncultivated majority: combining DNA stable‐isotope probing, multiple displacement amplification and metagenomic analyses of uncultivated Methylocystis in acidic peatlands - Yin Chen; Marc G. Dumont; Josh D. Neufeld; Levente Bodrossy; Nancy Stralis‐Pavese; Niall P. McNamara; Nick Ostle; Maria J. I. Briones; J. Colin Murrell (Environmental Microbiology, 2008)
Summary Peatlands represent an enormous carbon reservoir and have a potential impact on the global climate because of the active methanogenesis and methanotrophy in these soils. Uncultivated methanotrophs from seven European peatlands were studied using a combination of molecular methods. Screening for methanotroph diversity using a particulate methane monooxygenase‐based diagnostic gene array revealed that Methylocystis ‐related species were dominant in six of the seven peatlands studied. The abundance and methane oxidation activity of Methylocystis spp. were further confirmed by DNA stable‐isotope probing analysis of a sample taken from the Moor House peatland (England). After ultracentrifugation, 13 C‐labelled DNA, containing genomic DNA of these Methylocystis spp., was separated from 12 C DNA and subjected to multiple displacement amplification (MDA) to generate sufficient DNA for the preparation of a fosmid metagenomic library. Potential bias of MDA was detected by fingerprint analysis of 16S rRNA using denaturing gradient gel electrophoresis for low‐template amplification (0.01 ng template). Sufficient template (1–5 ng) was used in MDA to circumvent this bias and chimeric artefacts were minimized by using an enzymatic treatment of MDA‐generated DNA with S1 nuclease and DNA polymerase I. Screening of the metagenomic library revealed one fosmid containing methanol dehydrogenase and two fosmids containing 16S rRNA genes from these Methylocystis ‐related species as well as one fosmid containing a 16S rRNA gene related to that of Methylocella / Methylocapsa . Sequencing of the 14 kb methanol dehydrogenase‐containing fosmid allowed the assembly of a gene cluster encoding polypeptides involved in bacterial methanol utilization ( mxaFJGIRSAC ). This combination of DNA stable‐isotope probing, MDA and metagenomics provided access to genomic information of a relatively large DNA fragment of these thus far uncultivated, predominant and active methanotrophs in peatland soil.

Velasco Reef: a sunken atoll with unusual “remnant” beds of the seagrass Thalassodendron ciliatum - P. L. Colin (Coral Reefs, 2008)

ORIGINAL ARTICLE: Mammals of Borneo – small size on a large island - Shai Meiri; Erik Meijaard; Serge A. Wich; Colin P. Groves; Kristofer M. Helgen (Journal of Biogeography, 2008)
Aim Island mammals have featured prominently in models of the evolution of body size. Most of these models examine size evolution across a wide range of islands in order to test which island characteristics influence evolutionary pathways. Here, we examine the mammalian fauna of a single island, Borneo, where previous work has detected that some mammal species have evolved a relatively small size. We test whether Borneo is characterized by smaller mammals than adjacent areas, and examine possible causes for the different trajectories of size evolution between different Bornean species. Location Sundaland: Borneo, Sumatra, Java and the Malay/Thai Peninsula. Methods We compared the mammalian body size frequency distributions in the four areas to examine whether the large mammal fauna of Borneo is more depauperate than elsewhere. We measured specimens belonging to 54 mammal species that are shared between Borneo and any of the other areas in order to determine whether there is an intraspecific tendency for Bornean mammals to evolve small body size. Using data on diet, body size and geographical ranges we examine factors that are thought to influence body size. Results Borneo has fewer large mammals than the other areas, but this is not statistically significant. Large Bornean mammals are significantly smaller than their conspecifics in the other regions, while there are no differences between the body sizes of mammals on Sumatra, Java and the Malay/Thai Peninsula. The finding that large mammals show the greatest size difference between Borneo and elsewhere contrasts with some models of size evolution on islands of different areas. Diet does not correlate with the degree of size reduction. Sunda region endemics show a weaker tendency to be small on Borneo than do widespread species. Main conclusions We suggest that soil quality may drive size evolution by affecting primary productivity. On Borneo, where soils are generally poor in nutrients, this may both limit biomass and cause mammals to be reduced in body size. We hypothesize that widespread species respond to low resource abundance by reducing in size, while endemic elements of the fauna have had longer to adjust to local conditions by altering their behaviour, physiology and/or ecology, and are thus similar in size across the region.

Exploring gene-environment interactions in Parkinson’s disease - Colin C. McCulloch; Denise M. Kay; Stewart A. Factor; Ali Samii; John G. Nutt; Donald S. Higgins; Alida Griffith; John W. Roberts; Berta C. Leis; Jennifer S. Montimurro; Cyrus P. Zabetian; Haydeh Payami (Human Genetics, 2008)

Response of wild C 4 crop progenitors to subambient CO 2 highlights a possible role in the origin of agriculture - JENNIFER CUNNIFF; COLIN P. OSBORNE; BRAD S. RIPLEY; MICHAEL CHARLES; GLYNIS JONES (Global Change Biology, 2008)
The synchronous origin of agriculture in at least four independent climatic regions at the end of the last glacial period (c10 kyr bp ) points to a global limitation for crop domestication. One hypothesis proposes that a rapid carbon dioxide (CO 2 ) increase from 18 Pa to ∼27 Pa during deglaciation caused significant increases in the growth rates of wild crop progenitors, thereby removing a productivity barrier to their successful domestication. However, early C 4 crops present a challenge to this hypothesis, because they were among the first domesticates, but have a carbon‐concentrating mechanism that offsets the limitation of photosynthesis by CO 2 . We investigated the CO 2 ‐limitation hypothesis using the wild progenitors of five C 4 founder crops from four independent centres of domestication. Plants were grown in controlled environment chambers at glacial (18 Pa), postglacial (28 Pa) and current ambient (38 Pa) CO 2 levels, and photosynthesis, transpiration and biomass were measured. An increase in CO 2 from glacial to postglacial levels caused a significant gain in vegetative biomass of up to 40%, but the equivalent rise in CO 2 from postglacial to modern levels generally had no effect on biomass. Investigation into the underlying mechanisms showed C 4 photosynthesis to be limited more by glacial than postglacial CO 2 levels, matching theoretical expectations. Moreover, the increase in CO 2 from glacial to postglacial levels caused a reduction in the transpiration rate via decreases in stomatal conductance of ∼35%. In combination, these physiological changes conferred a large improvement in water‐use efficiency at the postglacial CO 2 partial pressure compared with the glacial level. Our data, therefore, provide experimental support for the CO 2 ‐limitation hypothesis, suggesting that these key physiological changes could have greatly enhanced the productivity of wild crop progenitors after deglaciation.

The rainfall intensity–duration control of shallow landslides and debris flows: an update - Fausto Guzzetti; Silvia Peruccacci; Mauro Rossi; Colin P. Stark (Landslides, 2008)

Maintenance of high pollen dispersal in Eucalyptus wandoo, a dominant tree of the fragmented agricultural region in Western Australia - Margaret Byrne; Carole P. Elliott; Colin J. Yates; David J. Coates (Conservation Genetics, 2008)

Diversity of the active methanotrophic community in acidic peatlands as assessed by mRNA and SIP‐PLFA analyses - Yin Chen; Marc G. Dumont; Niall P. McNamara; Paul M. Chamberlain; Levente Bodrossy; Nancy Stralis‐Pavese; J. Colin Murrell (Environmental Microbiology, 2008)
Summary The active methanotroph community was investigated for the first time in heather ( Calluna )‐covered moorlands and Sphagnum / Eriophorum ‐covered UK peatlands. Direct extraction of mRNA from these soils facilitated detection of expression of methane monooxygenase genes, which revealed that particulate methane monooxygenase and not soluble methane monooxygenase was probably responsible for CH 4 oxidation in situ , because only pmoA transcripts (encoding a subunit of particulate methane monooxygenase) were readily detectable. Differences in methanotroph community structures were observed between the Calluna ‐covered moorland and Sphagnum / Eriophorum ‐covered gully habitats. As with many other Sphagnum ‐covered peatlands, the Sphagnum / Eriophorum ‐covered gullies were dominated by Methylocystis . Methylocella and Methylocapsa ‐related species were also present. Methylobacter ‐related species were found as demonstrated by the use of a pmoA ‐based diagnostic microarray. In Calluna ‐covered moorlands, in addition to Methylocella and Methylocystis , a unique group of peat‐associated type I methanotrophs ( Gammaproteobacteria ) and a group of uncultivated type II methanotrophs ( Alphaproteobacteria ) were also found. The pmoA sequences of the latter were only distantly related to Methylocapsa and also to the RA‐14 group of methanotrophs, which are believed to be involved in oxidation of atmospheric concentrations of CH 4 . Soil samples were also labelled with 13 CH 4 , and subsequent analysis of the 13 C‐labelled phospholipid fatty acids (PLFAs) showed that 16:1ω7, 18:1ω7 and 18:1ω9 were the major labelled PLFAs. The presence of 13 C‐labelled 18:1ω9, which was not a major PLFA of any extant methanotrophs, indicated the presence of novel methanotrophs in this peatland.

Craniodental Characters in the Taxonomy of Propithecus - Colin P. Groves; Kristofer M. Helgen (International Journal of Primatology, 2007)

Bladder cancer angiogenesis and metastasis—translation from murine model to clinical trial - Peter C. Black; Colin P. N. Dinney (Cancer and Metastasis Reviews, 2007)

Ambient UV, personal sun exposure and risk of multiple primary melanomas - Anne Kricker; Bruce K. Armstrong; Chris Goumas; Melisa Litchfield; Colin B. Begg; Amanda J. Hummer; Loraine D. Marrett; Beth Theis; Robert C. Millikan; Nancy Thomas; Hoda Anton Culver; Richard P. Gallagher; et al. (Cancer Causes & Control, 2007)

Rational Design of a Dual-Mode Optical and Chemical Prodrug - Colin P. McCoy; Clare Rooney; David S. Jones; Sean P. Gorman; Mark Nieuwenhuyzen (Pharmaceutical Research, 2006)

The origin of the savanna biome - DAVID J. BEERLING; COLIN P. OSBORNE (Global Change Biology, 2006)
Savannas are a major terrestrial biome, comprising of grasses with the C 4 photosynthetic pathway and trees with the C 3 type. This mixed grass–tree biome rapidly appeared on the ecological stage 8 million years ago with the near‐synchronous expansion of C 4 grasses around the world. We propose a new hypothesis for this global event based on a systems analysis that integrates recent advances in how fire influences cloud microphysics, climate and savanna ecology in a low carbon dioxide (CO 2 ) world. We show that fire accelerates forest loss and C 4 grassland expansion through multiple positive feedback loops that each promote drought and more fire. A low CO 2 atmosphere amplifies this cycle by limiting tree recruitment, allowing the ingress of C 4 grasses to greatly increase ecosystem flammability. Continued intensification of land use could enhance or moderate the network of feedbacks that have initiated, promoted and sustained savannas for millions of years. We suggest these alterations will overprint the effects of anthropogenic atmospheric change in coming decades.

A genetic test for recruitment enhancement in Chesapeake Bay oysters, Crassostrea virginica, after population supplementation with a disease tolerant strain - Matthew P. Hare; Standish K. Allen; Paulette Bloomer; Mark D. Camara; Ryan B. Carnegie; Jenna Murfree; Mark Luckenbach; Donald Meritt; Cheryl Morrison; Kennedy Paynter; Kimberly S. Reece; Colin G. Rose (Conservation Genetics, 2006)

Model‐based uncertainty in species range prediction - Richard G. Pearson; Wilfried Thuiller; Miguel B. Araújo; Enrique Martinez‐Meyer; Lluís Brotons; Colin McClean; Lera Miles; Pedro Segurado; Terence P. Dawson; David C. Lees (Journal of Biogeography, 2006)
Aim Many attempts to predict the potential range of species rely on environmental niche (or ‘bioclimate envelope’) modelling, yet the effects of using different niche‐based methodologies require further investigation. Here we investigate the impact that the choice of model can have on predictions, identify key reasons why model output may differ and discuss the implications that model uncertainty has for policy‐guiding applications. Location The Western Cape of South Africa. Methods We applied nine of the most widely used modelling techniques to model potential distributions under current and predicted future climate for four species (including two subspecies) of Proteaceae. Each model was built using an identical set of five input variables and distribution data for 3996 sampled sites. We compare model predictions by testing agreement between observed and simulated distributions for the present day (using the area under the receiver operating characteristic curve (AUC) and kappa statistics) and by assessing consistency in predictions of range size changes under future climate (using cluster analysis). Results Our analyses show significant differences between predictions from different models, with predicted changes in range size by 2030 differing in both magnitude and direction (e.g. from 92% loss to 322% gain). We explain differences with reference to two characteristics of the modelling techniques: data input requirements (presence/absence vs. presence‐only approaches) and assumptions made by each algorithm when extrapolating beyond the range of data used to build the model. The effects of these factors should be carefully considered when using this modelling approach to predict species ranges. Main conclusions We highlight an important source of uncertainty in assessments of the impacts of climate change on biodiversity and emphasize that model predictions should be interpreted in policy‐guiding applications along with a full appreciation of uncertainty.

RTS, a rice anther-specific gene is required for male fertility and its promoter sequence directs tissue-specific gene expression in different plant species - Hong Luo; Jang-Yong Lee; Qian Hu; Kimberly Nelson-Vasilchik; Timothy K. Eitas; Colin Lickwar; Albert P. Kausch; Joel M. Chandlee; Thomas K. Hodges (Plant Molecular Biology, 2006)

Tarsius lariang: A New Primate Species from Western Central Sulawesi - Stefan Merker; Colin P. Groves (International Journal of Primatology, 2006)

Residency and movement patterns of bonnethead sharks, Sphyrna tiburo, in a large Florida estuary - Michelle R. Heupel; Colin A. Simpfendorfer; Angela B. Collins; John P. Tyminski (Environmental Biology of Fishes, 2006)

Large-Scale Temporal Changes in Spatial Pattern During Declines of Abundance and Occupancy in a Common Moth - Kelvin F. Conrad; Joe N. Perry; Ian P. Woiwod; Colin J. Alexander (Journal of Insect Conservation, 2006)

Modeling the Effects of Limiting the Number of Visitors on Failure Rates of Seabird Nests - COLIN M. BEALE; P. MONAGHAN (Conservation Biology, 2005)
Most attempts to manage disturbance by visitors to nature reserves concentrate on limiting visitor access in some way, which is often unpopular with both visitors and managers. In a few nature reserves the daily numbers of visitors are limited, an action that need not necessarily reduce the total number of visitors. As a test of the assumptions that underlie this management practice, we examined the relationship between daily visitor numbers and daily failure rates of nests in two species of seabirds. Daily failure rates for Black‐legged Kittiwakes (Rissa tridactyla) were weakly correlated with daily visitor numbers but indicated that capping daily visitor numbers slightly reduced overall breeding success. This was not the case for Common Murres (Uria aalge), where failure rate declined seasonally but was not significantly correlated with visitor numbers. For some species, it appears that capping daily visitor numbers may have small conservation costs.

Ecosystem dynamics based on plankton functional types for global ocean biogeochemistry models - Corinne Le Quéré; Sandy P. Harrison; I. Colin Prentice; Erik T. Buitenhuis; Olivier Aumont; Laurent Bopp; Hervé Claustre; Leticia Cotrim Da Cunha; Richard Geider; Xavier Giraud; Christine Klaas; Karen E. Kohfeld; et al. (Global Change Biology, 2005)
Ecosystem processes are important determinants of the biogeochemistry of the ocean, and they can be profoundly affected by changes in climate. Ocean models currently express ecosystem processes through empirically derived parameterizations that tightly link key geochemical tracers to ocean physics. The explicit inclusion of ecosystem processes in models will permit ecological changes to be taken into account, and will allow us to address several important questions, including the causes of observed glacial–interglacial changes in atmospheric trace gases and aerosols, and how the oceanic uptake of CO 2 is likely to change in the future. There is an urgent need to assess our mechanistic understanding of the environmental factors that exert control over marine ecosystems, and to represent their natural complexity based on theoretical understanding. We present a prototype design for a Dynamic Green Ocean Model (DGOM) based on the identification of (a) key plankton functional types that need to be simulated explicitly to capture important biogeochemical processes in the ocean; (b) key processes controlling the growth and mortality of these functional types and hence their interactions; and (c) sources of information necessary to parameterize each of these processes within a modeling framework. We also develop a strategy for model evaluation, based on simulation of both past and present mean state and variability, and identify potential sources of validation data for each. Finally, we present a DGOM‐based strategy for addressing key questions in ocean biogeochemistry. This paper thus presents ongoing work in ocean biogeochemical modeling, which, it is hoped will motivate international collaborations to improve our understanding of the role of the ocean in the climate system.

The Encyclopedia of Animals: A Complete Visual Guide - Colin P. Groves (International Journal of Primatology, 2005)

Chloroplast and microsatellite DNA diversities reveal the introduction history of Brazilian peppertree ( Schinus terebinthifolius ) in Florida - DEAN A. WILLIAMS; WILLIAM A. OVERHOLT; JAMES P. CUDA; COLIN R. HUGHES (Molecular Ecology, 2005)
Brazilian peppertree ( Schinus terebinthifolius ) is a woody perennial that has invaded much of Florida. This native of northeastern Argentina, Paraguay, and Brazil was brought as an ornamental to both the west and east coasts of Florida at the end of the 19th century. It was recorded as an invader of natural areas in the 1950s, and has since extended its range to cover over 280 000 ha. Our goals were to understand the history of this invasion, as one step toward understanding why this exotic was so successful, and ultimately to improve development of biological control agents. We sampled plants from the native and exotic ranges, particularly Florida, and genotyped these individuals at nuclear and chloroplast loci. Nuclear microsatellite and cpDNA loci reveal strong genetic population structure consistent with limited dispersal in the introduced and native ranges. Bayesian clustering of microsatellite data separates the east and west coast plants in Florida into distinct populations. The two chloroplast haplotypes found in Florida are also concordant with this separation: one predominates on the east coast, the other on the west coast. Analysis of samples collected in South America shows that haplotypes as distinct as the two in Florida are unlikely to have come from a single source population. We conclude that the genetic evidence supports two introductions of Brazilian peppertree into Florida and extensive hybridization between them. The west coast genotype likely came from coastal Brazil at about 27° south, whereas the east coast genotype probably originated from another, as yet unidentified site. As a result of hybridization, the Florida population does not exhibit low genetic variation compared to populations in the native range, possibly increasing its ability to adapt to novel environments. Hybridization also has important consequences for the selection of biocontrol agents since it will not be possible to identify closely co‐adapted natural enemies in the native range, necessitating more extensive host testing.

A bacteriophytochrome regulates the synthesis of LH4 complexesin Rhodopseudomonas palustris - Katie Evans; Anthony P. Fordham-Skelton; Hiten Mistry; Colin D. Reynolds; Anna M. Lawless; Miroslav Z. Papiz (Photosynthesis Research, 2005)

Testing for resistance of pelagic marine copepods to a toxic dinoflagellate - Sean P. Colin; Hans G. Dam (Evolutionary Ecology, 2005)

Evaluation of Flood and Landslide Risk to the Population of Italy - Fausto Guzzetti; Colin P. Stark; Paola Salvati (Environmental Management, 2005)

Bacterial diversity in the bacterioneuston (sea surface microlayer): the bacterioneuston through the looking glass - Mark P. Franklin; Ian R. McDonald; David G. Bourne; Nicholas J. P. Owens; Robert C. Upstill‐Goddard; J. Colin Murrell (Environmental Microbiology, 2005)
Summary The bacterioneuston is defined as the community of bacteria present within the neuston or sea surface microlayer. Bacteria within this layer were sampled using a membrane filter technique and bacterial diversity was compared with that in the underlying pelagic coastal seawater using molecular ecological techniques. 16S rRNA gene libraries of ≈ 500 clones were constructed from both bacterioneuston and the pelagic water samples and representative clones from each library were sequenced for comparison of bacterial diversity. The bacterioneuston was found to have a significantly lower bacterial diversity than the pelagic seawater, with only nine clone types (ecotaxa) as opposed to 46 ecotaxa in the pelagic seawater library. Surprisingly, the bacterioneuston clone library was dominated by 16S rRNA gene sequences affiliated to two groups of organisms, Vibrio spp. which accounted for over 68% of clones and Pseudoalteromonas spp. accounting for 21% of the library. The dominance of these two 16S rRNA gene sequence types within the bacterioneuston clone library was confirmed in a subsequent gene probing experiment. 16S rRNA gene probes specific for these groups of bacteria were designed and used to probe new libraries of 1000 clones from both the bacterioneuston and pelagic seawater DNA samples. This revealed that 57% of clones from the bacterioneuston library hybridized to a Vibrio sp.‐specific 16S rRNA gene probe and 32% hybridized to a Pseudoalteromonas sp.‐specific 16S rRNA gene probe. In contrast, the pelagic seawater library resulted in only 13% and 8% of 16S rRNA gene clones hybridizing to the Vibrio sp. and Pseudoalteromonas sp. probes respectively. Results from this study suggest that the bacterioneuston contains a distinct population of bacteria and warrants further detailed study at the molecular level.

Influence of land use on the integrity of marsh bird communities of Chesapeake Bay, USA - William V. DeLuca; Colin E. Studds; Larry L. Rockwood; Peter P. Marra (Wetlands, 2004)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Y chromosome haplogroups of elite Ethiopian endurance runners - Colin N. Moran; Robert A. Scott; Susan M. Adams; Samantha J. Warrington; Mark A. Jobling; Richard H. Wilson; William H. Goodwin; Evelina Georgiades; Bezabhe Wolde; Yannis P. Pitsiladis (Human Genetics, 2004)

Familial aggregation of melanoma risks in a large population-based sample of melanoma cases - Colin B. Begg; Amanda Hummer; Urvi Mujumdar; Bruce K. Armstrong; Anne Kricker; Loraine D. Marrett; Robert C. Millikan; Stephen B. Gruber; Hoda Anton-Culver; Judith B. Klotz; Roberto Zanetti; Richard P. Gallagher; et al. (Cancer Causes & Control, 2004)

Familial aggregation of melanoma risks in a large population-based sample of melanoma cases - Colin B. Begg; Amanda Hummer; Urvi Mujumdar; Bruce K. Armstrong; Anne Kricker; Loraine D. Marrett; Robert C. Millikan; Stephen B. Gruber; Hoda Anton-Culver; Judith B. Klotz; Roberto Zanetti; Richard P. Gallagher; et al. (Cancer Causes & Control, 2004)

A Method to Quantify and Analyze the Foraging Activity of Honey Bees: Relevance to the Sublethal Effects Induced by Systemic Insecticides - M. E. Colin; J. M. Bonmatin; I. Moineau; C. Gaimon; S. Brun; J. P. Vermandere (Archives of Environmental Contamination and Toxicology, 2004)

Pollen‐based reconstructions of biome distributions for Australia, Southeast Asia and the Pacific (SEAPAC region) at 0, 6000 and 18,000 14 C yr BP - Elizabeth J. Pickett; Sandy P. Harrison; Geoff Hope; Kate Harle; John R. Dodson; A. Peter Kershaw; I. Colin Prentice; John Backhouse; Eric A. Colhoun; Donna D'Costa; John Flenley; John Grindrod; et al. (Journal of Biogeography, 2004)
Aim This paper documents reconstructions of the vegetation patterns in Australia, Southeast Asia and the Pacific (SEAPAC region) in the mid‐Holocene and at the last glacial maximum (LGM). Methods Vegetation patterns were reconstructed from pollen data using an objective biomization scheme based on plant functional types. The biomization scheme was first tested using 535 modern pollen samples from 377 sites, and then applied unchanged to fossil pollen samples dating to 6000 ± 500 or 18,000 ± 1000 14 C yr bp . Results 1. Tests using surface pollen sample sites showed that the biomization scheme is capable of reproducing the modern broad‐scale patterns of vegetation distribution. The north–south gradient in temperature, reflected in transitions from cool evergreen needleleaf forest in the extreme south through temperate rain forest or wet sclerophyll forest (WSFW) and into tropical forests, is well reconstructed. The transitions from xerophytic through sclerophyll woodlands and open forests to closed‐canopy forests, which reflect the gradient in plant available moisture from the continental interior towards the coast, are reconstructed with less geographical precision but nevertheless the broad‐scale pattern emerges. 2. Differences between the modern and mid‐Holocene vegetation patterns in mainland Australia are comparatively small and reflect changes in moisture availability rather than temperature. In south‐eastern Australia some sites show a shift towards more moisture‐stressed vegetation in the mid‐Holocene with xerophytic woods/scrub and temperate sclerophyll woodland and shrubland at sites characterized today by WSFW or warm‐temperate rain forest (WTRF). However, sites in the Snowy Mountains, on the Southern Tablelands and east of the Great Dividing Range have more moisture‐demanding vegetation in the mid‐Holocene than today. South‐western Australia was slightly drier than today. The single site in north‐western Australia also shows conditions drier than today in the mid‐Holocene. Changes in the tropics are also comparatively small, but the presence of WTRF and tropical deciduous broadleaf forest and woodland in the mid‐Holocene, in sites occupied today by cool‐temperate rain forest, indicate warmer conditions. 3. Expansion of xerophytic vegetation in the south and tropical deciduous broadleaf forest and woodland in the north indicate drier conditions across mainland Australia at the LGM. None of these changes are informative about the degree of cooling. However the evidence from the tropics, showing lowering of the treeline and forest belts, indicates that conditions were between 1 and 9 °C (depending on elevation) colder. The encroachment of tropical deciduous broadleaf forest and woodland into lowland evergreen broadleaf forest implies greater aridity. Main conclusions This study provides the first continental‐scale reconstruction of mid‐Holocene and LGM vegetation patterns from Australia, Southeast Asia and the Pacific (SEAPAC region) using an objective biomization scheme. These data will provide a benchmark for evaluation of palaeoclimate simulations within the framework of the Palaeoclimate Modelling Intercomparison Project.

Identity and diversity of coral endosymbionts (zooxanthellae) from three Palauan reefs with contrasting bleaching, temperature and shading histories - K. E. FABRICIUS; J. C. MIEOG; P. L. COLIN; D. IDIP; M. J. H. VAN OPPEN (Molecular Ecology, 2004)
The potential of corals to associate with more temperature‐tolerant strains of algae (zooxanthellae, Symbiodinium ) can have important implications for the future of coral reefs in an era of global climate change. In this study, the genetic identity and diversity of zooxanthellae was investigated at three reefs with contrasting histories of bleaching mortality, water temperature and shading, in the Republic of Palau (Micronesia). Single‐stranded conformation polymorphism and sequence analysis of the ribosomal DNA internal transcribed spacer (ITS)1 region was used for genotyping. A chronically warm but partly shaded coral reef in a marine lake that is hydrographically well connected to the surrounding waters harboured only two single‐stranded conformation polymorphism profiles (i.e. zooxanthella communities). It consisted only of Symbiodinium D in all 13 nonporitid species and two Porites species investigated, with the remaining five Porites harbouring C•. Despite the high temperature in this lake (> 0.5° above ambient), this reef did not suffer coral mortality during the (1998) bleaching event, however, no bleaching‐sensitive coral families and genera occur in the coral community. This setting contrasts strongly with two other reefs with generally lower temperatures, in which 10 and 12 zooxanthella communities with moderate to low proportions of clade D zooxanthellae were found. The data indicate that whole coral assemblages, when growing in elevated seawater temperatures and at reduced irradiance, can be composed of colonies associated with the more thermo‐tolerant clade D zooxanthellae. Future increases in seawater temperature might, therefore, result in an increasing prevalence of Symbiodinium phylotype D in scleractinian corals, possibly associated with a loss of diversity in both zooxanthellae and corals.

Assessment of the Diversity of African Primates - Peter Grubb; Thomas M. Butynski; John F. Oates; Simon K. Bearder; Todd R. Disotell; Colin P. Groves; Thomas T. Struhsaker (International Journal of Primatology, 2003)

USE OF A PETHIDINE AND MIDAZOLAM COMBINATION FOR THE REVERSIBLE SEDATION OF CRABEATER SEALS (LOBODON CARCINOPHAGUS) - Mark A. Tahmindjis; Damien P. Higgins; Michael J. Lynch; Julie A. Barnes; Colin J. Southwell (Marine Mammal Science, 2003)
A bstract Between October and December of 1996–1999, off eastern Antarctica (60°‐150°E), we darted 31 crabeater seals with midazolam and pethidine at estimated dose rates of 0.15–0.4 mg/kg and 1–3 mg/kg, respectively. Maximum sedation was reached at 23 ± 9 min (n = 18) and first signs of recovery were noted at 54 ± 24 min (n = 4). Seals greater than 250 kg body‐mass were sedated by administration of approximately 90–100 mg midazolam and 600 mg pethidine, but the degree of sedation was unpredictable and did not permit invasive procedures in some cases. Behavior of the seal and adjacent conspecifics affected the success of procedures and our ability to monitor vital signs. Naloxone and flumazenil reversed sedation, making this combination attractive for use in animals adjacent to water. Additional ketamine was administered to two seals, resulting in improved restraint.

Climate and CO 2 controls on global vegetation distribution at the last glacial maximum: analysis based on palaeovegetation data, biome modelling and palaeoclimate simulations - SANDY P. HARRISON; COLIN I. PRENTICE (Global Change Biology, 2003)
The global vegetation response to climate and atmospheric CO 2 changes between the last glacial maximum and recent times is examined using an equilibrium vegetation model (BIOME4), driven by output from 17 climate simulations from the Palaeoclimate Modelling Intercomparison Project. Features common to all of the simulations include expansion of treeless vegetation in high northern latitudes; southward displacement and fragmentation of boreal and temperate forests; and expansion of drought‐tolerant biomes in the tropics. These features are broadly consistent with pollen‐based reconstructions of vegetation distribution at the last glacial maximum. Glacial vegetation in high latitudes reflects cold and dry conditions due to the low CO 2 concentration and the presence of large continental ice sheets. The extent of drought‐tolerant vegetation in tropical and subtropical latitudes reflects a generally drier low‐latitude climate. Comparisons of the observations with BIOME4 simulations, with and without consideration of the direct physiological effect of CO 2 concentration on C 3 photosynthesis, suggest an important additional role of low CO 2 concentration in restricting the extent of forests, especially in the tropics. Global forest cover was overestimated by all models when climate change alone was used to drive BIOME4, and estimated more accurately when physiological effects of CO 2 concentration were included. This result suggests that both CO 2 effects and climate effects were important in determining glacial‐interglacial changes in vegetation. More realistic simulations of glacial vegetation and climate will need to take into account the feedback effects of these structural and physiological changes on the climate.

Risks from Competitively Inferior Immigrant Populations: Implications of Mass Effects for Species Conservation - Colin J. Thompson; Ben J. P. Thompson; Mark A. Burgman (Conservation Biology, 2003)
Many species are maintained by a rain of propagules from a source population and thereby persist in a location from which they would ordinarily be excluded by competition. This is one explanation for the persistence of competitively inferior domestic species in natural environments. The purpose of our study was to estimate the effect of immigrant populations on competitively superior wild species in terms of the risks of decline—the quasiextinction risk—of the wild population and the quasiexplosion risk of the immigrant population. A simple mathematical model of escape and competition demonstrates that the risks to a wild population may be appreciable. We found that even when the species maintained by mass effects is not viable in the absence of competition and immigration, low escape rates ( e.g., enough to give the invasive population a net positive growth rate ) can make a wild‐competing species vulnerable within 10 years. The probability that the immigrant population will exceed lower bounds increases rapidly with rates of escape and growth.

Fish Faunal Resurgence in Lake Nabugabo, East Africa - Lauren J. Chapman; Colin A. Chapman; Pamela J. Schofield; John P. Olowo; Les Kaufman; Ole Seehausen; Richard Ogutu‐Ohwayo (Conservation Biology, 2003)
In Lake Nabugabo, Uganda, a small satellite of the equatorial Lake Victoria, approximately 50% of the indigenous fish species disappeared from the open waters subsequent to establishment of the introduced predatory Nile perch ( Lates niloticus ). However, several of these species persisted in wetland refugia. Over the past decade, Nile perch in Lake Nabugabo have been intensively fished. Herein we report a resurgence of some indigenous species in open waters. In a multiyear study, we used annual transects in inshore and offshore waters of exposed ( no wetland ) and wetland habitats to document the pattern of resurgence. In 1995, haplochromine cichlids were largely confined to inshore areas, particularly wetland ecotones, and were rare in Nile perch stomachs, as were most other indigenous species. By 2000 haplochromine cichlids were abundant in inshore and offshore areas of both exposed and wetland transects. Several indigenous noncichlids also reappeared in the main lake, including three of the four original mormyrid species. Between 1995 and 1999, there was a dramatic increase in the proportion of haplochromines in the diet of Nile perch. When haplochromines were rare ( 1995 ), Nile perch switched from an invertebrate‐dominated diet to piscivory at a large size ( 30 cm total length ). In 2000, however, Nile perch were strongly piscivorous by 5–10 cm total length. The pattern of faunal loss and recovery in Lake Nabugabo demonstrates the importance of refugia in providing the seeds of resurgence and provides a model with which to understand some changes in Lake Victoria.

Growth of sulfate-reducing bacteria and methanogenic archaea with methylated sulfur compounds: a commentary on the thermodynamic aspects - Johannes C. M. Scholten; J. Colin Murrell; Donovan P. Kelly (Archives of Microbiology, 2003)

Growth of sulfate-reducing bacteria and methanogenic archaea with methylated sulfur compounds: a commentary on the thermodynamic aspects - Johannes C. M. Scholten; J. Colin Murrell; Donovan P. Kelly (Archives of Microbiology, 2003)

Characterization of Microbial Communities from Coastal Waters using Microarrays - O. Colin Stine; Amy Carnahan; Ruby Singh; Jan Powell; Jon P. Furuno; Alicia Dorsey; Ellen Silbergeld; Henry N. Williams; J. Glenn Morris (Environmental Monitoring and Assessment, 2003)

DDC and COBL, flanking the imprinted GRB10 gene on 7p12, are biallelically expressed - Megan P. Hitchins; Louise Bentley; David Monk; Colin Beechey; Jo Peters; Gavin Kelsey; Fumitoshi Ishino; Michael A. Preece; Philip Stanier; Gudrun E. Moore (Mammalian Genome, 2002)

Testing for toxic effects of prey on zooplankton using sole versus mixed diets - Sean P. Colin; Hans G. Dam (Limnology and Oceanography, 2002)
Negative effects of prey species on consumers could be due to deterrence, nutritional insufficiency, or toxicity of the prey. These effects can be discerned in experiments in which the suspect prey is offered to the consumers in a food mixture containing another prey item that is not toxic and in which the ingestion rates on the prey and the grazers’ responses (e.g., egg production) are measured. We used this framework to determine whether several algae that have been reported to have harmful effects on grazers ( Prorocentrum minimum , low‐and high‐toxin Alexandrium sp., Heterosigma carterae , Thalassiosira rotula , and Phaeodactylum tricornutum ) are toxic to females of the calanoid copepod Acartia tonsa . Ingestion, egg production, and egg‐hatching rates were measured for A. tonsa offered sole diets of the suspect alga and mixed diets containing the suspect alga and a control alga (the green flagellate Tetraselmis sp.) at an ecologically relevant concentration (250 µg C L -1 ) and duration (3 d). With the exception of the Alexandrium strain with the high‐toxin content (16.3 pgSaxitoxin [pgSTX] equivalents cell21), none of the diets studied can be considered toxic. The high‐toxin Alexandrium reduced A. tonsa ’s total ingestion rate, and thus egg production, as the proportion of Alexandrium increased in the diet. A. tonsa exhibited significantly reduced ingestion and egg production rates when feeding on sole food diets of H. carterae and P. tricornutum relative to the mixed food diets. However, a comparison of ingestion rates among the diet mixtures revealed that H. carterae and P. tricornutum acted as feeding deterrents when provided as sole foods. These results stress the importance of using mixed food diets when examining putative toxic effects of preys on consumers.

Prey resource use by coexistent hydromedusae from Friday Harbor, Washington - J. H. Costello; S. P. Colin (Limnology and Oceanography, 2002)
Prey selection patterns were quantified for a sympatric group of hydromedusae from Friday Harbor, WA. Selection patterns varied between species, but were largely replicable between sample dates and resembled dietary patterns found in similar studies from neighboring regions. Ambush‐foraging medusae ( Aglantha digitale , Sarsia tubulosa , and Proboscidactyla flavicirrata ) fed primarily on crustacean and ciliated prey but the dietary niches of these hydromedusan species centered on different fractions of the available plankton. Consequently, little dietary overlap occurred between the ambush foraging hydromedusae. In contrast, the dietary niches of cruising predators ( Aequorea victoria , Mitrocoma cellularia , and Phialidium gregarium ) overlapped substantially because those species all fed on similar soft‐bodied prey such as eggs and appendicularians. These results have two important implications for trophic patterns involving medusae. First, different mechanisms of prey encounter and capture used by hydromedusae (ambush vs. cruising patterns) result in important interspecific dietary differences and, hence, trophic roles of the medusae. Second, whereas cruising medusae may consume similar prey and hence form a feeding guild, ambush‐foraging medusae may experience substantially less prey overlap and, for the community examined here, do not experience potentially strong feeding competition from other medusan species.

Physicochemical Characterization of Hexetidine-Impregnated Endotracheal Tube Poly(vinyl Chloride) and Resistance to Adherence of Respiratory Bacterial Pathogens - David S. Jones; James G. McGovern; A. David Woolfson; Colin G. Adair; Sean P. Gorman (Pharmaceutical Research, 2002)

The Relationship Between Spatial Distribution and Diet of Arctic Charr, Salvelinus Alpinus, In Loch Ness, U.K. - Ian J. Winfield; Colin W. Bean; Diane P. Hewitt (Environmental Biology of Fishes, 2002)

The ribulose-1,5-bisphosphate carboxylase/oxygenase gene cluster of Methylococcus capsulatus (Bath) - Nardia J. Baxter; Robert P. Hirt; Levente Bodrossy; Kornel L. Kovacs; Martin T. Embley; James I. Prosser; J. Colin Murrell (Archives of Microbiology, 2002)

Taking a world view - Colin P Osborne (Journal of Biogeography, 2002)

Searching for the early benthic phase (EBP) of the European lobster: a trans-European study of cobble fauna - Adrian Linnane; Brendan Ball; John P. Mercer; Ronan Browne; Gro van der Meeren; Halldis Ringvold; Colin Bannister; David Mazzoni; Brian Munday (Hydrobiologia, 2001)

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

Molecular cloning and characterisation of banana fruit polyphenol oxidase - Paul S. Gooding; Colin Bird; Simon P. Robinson (Planta, 2001)

Genetic, physical, and phenotypic characterization of the Del(13)Svea36H mouse - Ruth M. Arkell; Matthew Cadman; Tracy Marsland; Anne Southwell; Caroline Thaung; Jennifer R. Davies; Toni Clay; Colin V. Beechey; Edward P. Evans; Mark A. Strivens; Steve D.M. Brown; Paul Denny (Mammalian Genome, 2001)

El Niño related coral bleaching in Palau, Western Caroline Islands - J. Bruno; C. Siddon; J. Witman; P. Colin; M. Toscano (Coral Reefs, 2001)

Behavioural and physiological responses of infective juveniles of the entomopathogenic nematode Heterorhabditis to desiccation - Sean A. O'Leary; Austin P. Power; Colin M. Stack; Ann M. Burnell (BioControl, 2001)

Molecular analysis of microbial community structure in an arsenite‐oxidizing acidic thermal spring - Colin R. Jackson; Heiko W. Langner; Jessica Donahoe‐Christiansen; William P. Inskeep; Timothy R. McDermott (Environmental Microbiology, 2001)
Electron microscopy (EM), denaturing gradient gel electrophoresis (DGGE) and 16S rDNA sequencing were used to examine the structure and diversity of microbial mats present in an acid‐sulphate–chloride (pH 3.1) thermal (58–62°C) spring in Norris Basin, Yellowstone National Park, WY, USA, exhibiting rapid rates of arsenite oxidation. Initial visual assessments, scanning EM and geochemical measurements revealed the presence of three distinct mat types. Analysis of 16S rDNA fragments with DGGE confirmed the presence of different bacterial and archaeal communities within these zones. Changes in the microbial community appeared to coincide with arsenite oxidation activity. Phylogenetic analysis of 1400 bp 16S rDNA sequences revealed that clone libraries prepared from both arsenic redox active and inactive bacterial communities were dominated by sequences phylogenetically related to Hydrogenobacter acidophilus and Desulphurella sp. The appearance of archaeal 16S rDNA sequences coincided with the start of arsenite oxidation, and sequences were obtained showing affiliation with both Crenarchaeota and Euryarchaeota . The majority of archaeal sequences were most similar to sequences obtained from marine hydrothermal vents and other acidic hot springs, although the level of similarity was typically just 90%. Arsenite oxidation in this system may result from the activities of these unknown archaeal taxa and/or the previously unreported arsenic redox activity of H. acidophilus ‐ or Desulphurella ‐like organisms. If the latter, arsenite oxidation must be inhibited in the initial high‐sulphide zone of the spring, where no change in the distribution of arsenite versus arsenate was observed.

Book Review: Walker's Primates of the World. By Ronald M. Nowak, Johns Hopkins University Press, Baltimore, MD, 2000, 224 pp., $19.95 (paperback) - Colin P. Groves (International Journal of Primatology, 2000)

The Genus Cheirogaleus: Unrecognized Biodiversity in Dwarf Lemurs - Colin P. Groves (International Journal of Primatology, 2000)

Lipid-to-gibberellin metabolic switching in Fusarium moniliforme via the action of sesamol - Alix Jacklin; Colin Ratledge; James P. Wynn (Biotechnology Letters, 2000)

Long‐Term Effects of Logging on African Primate Communities: a 28‐Year Comparison From Kibale National Park, Uganda - Colin A. Chapman; Sophia R. Balcomb; Thomas R. Gillespie; Joseph P. Skorupa; Thomas T. Struhsaker (Conservation Biology, 2000)
If logging is to be compatible with primate conservation, primate populations must be expected to recover from the disturbance and eventually return to their former densities. Surveys conducted over 28 years were used to quantify the long‐term effects of both low‐ and high‐intensity selective logging on the density of the five common primates in Kibale National Park, Uganda. The most dramatic exception to the expectation that primate populations will recover following logging was that group densities of Cercopithecus mitis and C. ascanius in the heavily logged area continued to decline decades after logging. Procolobus tephrosceles populations were recovering in the heavily logged areas, but the rate of increase appeared to be slow (0.005 groups/km 2 per year). Colobus guereza appeared to do well in some disturbed habitats and were found at higher group densities in the logged areas than in the unlogged area. There was no evidence of an increase in Lophocebus albigena group density in the heavily logged area since the time of logging, and there was a tendency for its population to be lower in heavily logged areas than in lightly logged areas. In contrast to the findings from the heavily logged area, none of the species were found at a lower group density in the lightly logged area than in the unlogged area, and group densities in this area were not changing at a statistically significant rate. The results of our study suggest that, in this region, low‐intensity selective logging could be one component of conservation plans for primates; high‐intensity logging, however, which is typical of most logging operations throughout Africa, is incompatible with primate conservation.

Characterization of a mouse laminin receptor gene homologous to the human blood group Lutheran gene - C. Rahuel; Y. Colin; D. Goossens; P. Gane; W. El Nemer; J. P. Cartron; C. Le Van Kim (Immunogenetics, 1999)

Developing applications for lactococcal bacteriocins - R. Paul Ross; Mary Galvin; Olivia McAuliffe; Sheila M. Morgan; Maire P. Ryan; Denis P. Twomey; William J. Meaney; Colin Hill (Antonie van Leeuwenhoek, 1999)

Application of near-field scanning optical microscopy in photosynthesis research - Vladimir P. Shinkarev; Robert Brunner; Colin A. Wraight (Photosynthesis Research, 1999)

Characterisation of the PsbX protein from Photosystem II and light regulation of its gene expression in higher plants - Lan-Xin Shi; Soo J. Kim; Alan Marchant; Colin Robinson; Wolfgang P. Schröder (Plant Molecular Biology, 1999)

Reduced satiating effect of d -fenfluramine in serotonin 5-HT 2C receptor mutant mice - Steven P. Vickers; Peter G. Clifton; Colin T. Dourish; Laurence H. Tecott (Psychopharmacology, 1999)

Characterisation of an Arabidopsis thaliana cDNA encoding a novel thylakoid lumen protein imported by the ΔpH-dependent pathway - Alexandra Mant; Thomas Kieselbach; Wolfgang P. Schröder; Colin Robinson (Planta, 1999)

Influence of Continental Sources on Oceanic Air Composition at the Eastern Edge of the North Atlantic Ocean, TOR 1992–1995 - I. Fenneteaux; P. Colin; A. Etienne; H. Boudries; A. L. Dutot; P. E. Perros; G. Toupance (Journal of Atmospheric Chemistry, 1999)

Present‐day and mid‐Holocene biomes reconstructed from pollen and plant macrofossil data from the former Soviet Union and Mongolia - Pavel E. Tarasov; Thompson Webb III; Andrei A. Andreev; Natalya B. Afanas’eva; Natalya A. Berezina; Ludmila G. Bezusko; Tatyana A. Blyakharchuk; Natalia S. Bolikhovskaya; Rachid Cheddadi; Margarita M. Chernavskaya; Galina M. Chernova; Nadezhda I. Dorofeyuk; et al. (Journal of Biogeography, 1998)
Fossil pollen data supplemented by tree macrofossil records were used to reconstruct the vegetation of the Former Soviet Union and Mongolia at 6000 years. Pollen spectra were assigned to biomes using the plant‐functional‐type method developed by Prentice et al . (1996). Surface pollen data and a modern vegetation map provided a test of the method. This is the first time such a broad‐scale vegetation reconstruction for the greater part of northern Eurasia has been attempted with objective techniques. The new results confirm previous regional palaeoenvironmental studies of the mid‐Holocene while providing a comprehensive synopsis and firmer conclusions. West of the Ural Mountains temperate deciduous forest extended both northward and southward from its modern range. The northern limits of cool mixed and cool conifer forests were also further north than present. Taiga was reduced in European Russia, but was extended into Yakutia where now there is cold deciduous forest. The northern limit of taiga was extended (as shown by increased Picea pollen percentages, and by tree macrofossil records north of the present‐day forest limit) but tundra was still present in north‐eastern Siberia. The boundary between forest and steppe in the continental interior did not shift substantially, and dry conditions similar to present existed in western Mongolia and north of the Aral Sea.

Pollen‐based biome reconstructions for China at 0 and 6000 years - Ge Yu; I. Colin Prentice; Sandy P. Harrison; Xiangjun Sun (Journal of Biogeography, 1998)
Biomization provides an objective and robust method of assigning pollen spectra to biomes so that pollen data can be mapped and compared directly with the output of biomgeographic models. We have tested the applicability of this procedure, originally developed for Europe, to assign modern surface samples from China to biomes. The procedure successfully delineated the major vegetation types of China. When the same procedure was applied to fossil pollen samples for 6000 years ago, the reconstructions showed systematic differences from present, consistent with previous interpretations of vegetation changes since the mid‐Holocene. In eastern China, the forest zones were systematically shifted northwards, such that cool mixed forests displaced taiga in northeastern China, while broad‐leaved evergreen forest extended c . 300 km and temperate deciduous forest c . 500–600 km beyond their present northern limits. In northwestern China, the area of desert and steppe vegetation was reduced compared to present. On the Tibetan Plateau, forest vegetation extended to higher elevations than today and the area of tundra was reduced. These shifts in biome distributions imply significant changes in climate since 6000 years ago that can be interpreted qualitatively as a response to orbital forcing and its secondary effects on the Asian monsoon.

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Obituary: Prudence Hero Napier (1916–1997) - Colin P. Groves (International Journal of Primatology, 1998)

A novel pink-pigmented facultative methylotroph, Methylobacterium thiocyanatum sp. nov., capable of growth on thiocyanate or cyanate as sole nitrogen sources - A. P. Wood; Donovan P. Kelly; I. R. McDonald; Sarah L. Jordan; Thomas D. Morgan; Sajdah Khan; J. Colin Murrell; Elena Borodina (Archives of Microbiology, 1998)

Autotrophic growth on carbon disulfide is a property of novel strains of Paracoccus denitrificans - Sarah L. Jordan; I. R. McDonald; Anna J. Kraczkiewicz-Dowjat; Donovan P. Kelly; Frederick A. Rainey; J. Colin Murrell; A. P. Wood (Archives of Microbiology, 1997)

Scale-up of Adhesive Transdermal Drug Delivery Systems - Glenn A. Van Buskirk; Mario A. González; Vinod P. Shah; Scott Barnhardt; Colin Barrett; Stephen Berge; Gary Cleary; Keith Chan; Gordon Flynn; Thomas Foster; Robert Gale; Raymond Garrison; et al. (Pharmaceutical Research, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Cost-effectiveness of screening blood donors for hepatitis C and non-A, non-B, non-C hepatitis - C. Colin; P. Vergnon; A. M. Jullien; S. Excoffier; Y. Matillon; C. Trepo; J. P. Aymard; D. Bastit; M. L. Bidet; R. Breviere; F. Chenais; F. Hau; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Methylosulfonomonas methylovora gen. nov., sp. nov., and Marinosulfonomonas methylotropha gen. nov., sp. nov.: novel methylotrophs able to grow on methanesulfonic acid - Andrew J. Holmes; D. P. Kelly; Simon C. Baker; A. S. Thompson; Paolo De Marco; Elizabeth M. Kenna; J. Colin Murrell (Archives of Microbiology, 1997)

Taxonomic relationships of Thiobacillus halophilus , T. aquaesulis , and other species of Thiobacillus , as determined using 16S rDNA sequencing - I. R. McDonald; Donovan P. Kelly; J. Colin Murrell; A. P. Wood (Archives of Microbiology, 1997)

Kinetics of the oxygen evolution step in plants determined from flash-induced chlorophyll t a fluorescence - Vladimir P. Shinkarev; Chunhe Xu; Govindjee; Colin A. Wraight (Photosynthesis Research, 1997)

The physiological response of the turbot to multiple net confinements - Colin P. Waring; Michael G. Poxton; Ronald M. Stagg (Aquaculture International, 1997)

Taxonomic relationships ofThiobacillus halophilus, T. aquaesulis, and other species ofThiobacillus, as determined using 16S rDNA sequencing - Ian R. McDonald; Donovan P. Kelly; J. Colin Murrell; Ann P. Wood (Archives of Microbiology, 1996)

Molecular genetics of chimpanzee Rh-related genes: Their relationship with the R-C-E-F blood group system, the chimpanzee counterpart of the human rhesus system - I. Salvignol; A. Blancher; P. Calvas; J. Clayton; W. W. Socha; Y. Colin; J. Ruffi (Biochemical Genetics, 1994)

Molecular analysis of methane monooxygenase from Methylococcus capsulatus (Bath) - Andrew C. Stainthorpe; J. Colin Murrell; George P. C. Salmond; Howard Dalton; Veronica Lees (Archives of Microbiology, 1989)